Biochemical changes in blood and allantoic fluid during late pregnancy of cloned embryos in Nellore cows - Luciano Andrade Silva; Adrielle Levatti; Izabelle Baldi Jardim; Fábio Luís Valério Pinaffi; Marcelo de Luna Freire Oliveira; Ana Paula da Silva; Flávio Vieira Meirelles; Juliano Rodrigues Sangalli (Theriogenology, 2026)

Dietary fiber sources modulate short-chain fatty acid profiles and the fecal microbiota in sows during late gestation - Idael Matheus Góes Lopes; Marcelo Dourado de Lima; Soraia Viana Ferreira; Rafaela Jorge Sarsur de Freitas Ribeiro; Lesleyane Dâmaris Teixeira Santos; Artur Cavalcanti de Souza; Luisa Lopes da Rocha dos Santos; Celmo Guedes Sant'Ana Filho; Murilo José Marques Maia; Karine Aparecida Rodrigues de Souza; Walter Motta Ferreira; Dalton de Oliveira Fontes (Bioactive Carbohydrates and Dietary Fibre, 2026)

Acinetobacter venetianus AMO1502: a strain isolated from an oil spill capable of degrading diesel and producing active surface compounds - Marcelo Pereira de Oliveira; Alan Portal D’Almeida; Tiago Lima de Albuquerque; Vânia Maria Maciel Melo; Tigressa Helena Soares Rodrigues; Maria Valderez Ponte Rocha (Brazilian Journal of Microbiology, 2026)

Short-term air exposure triggers redox metabolic shifts in the reef-building coral Pavona cactus - Luiza de Castro Mastrangelo Dias; Marina Minari; Carol Cristina Vágula de Almeida Silva; Beatriz Rodrigues Guarinão; Luís Felipe Barcena Albertoni; Lucas do Nascimento Lima; Daniel C. Moreira; Marcelo Hermes-Lima; Helen Sadauskas-Henrique (Journal of Experimental Marine Biology and Ecology, 2026)

Topography- and depth-driven variability of β-glucosidase activity in Amazonian Forest soils (Brazil): A machine learning and structural equation modeling approach - Gizachew Ayalew Tiruneh; Ciro Abbud Righi; Jefferson Lordello Polizel; Vinicius Gonçalves; Carlos Rodrigues Pereira; Fernando Dini Andreote; Rafael Lima Oliveira; Jean Jesus Macedo Novais; Marcelo Henrique Procópio Pelegrino; Jose Alexandre Melo Dematte; Marcelino Carneiro Guedes; Ranjith P. Udawatta (CATENA, 2026)

A Retrospective Molecular Epidemiology Study: Emergence and dissemination of Azole-Resistant Candida parapsilosis Sensu Stricto in Southern Brazil - Luiza Souza Rodrigues; Sabrina da Conceição Barbosa; Ana Paula Santiago Chacon; Adriele Celine Siqueira; Gisele Aparecida Bernardi; Marcelo Pillonetto; Vania Aparecida Vicente; Lavinia Nery Villa Stangler Arend; Terezinha Inez Estivalet Svidzinski; Libera Maria Dalla-Costa (Mycopathologia, 2026)
Candida parapsilosis sensu stricto has emerged as a major cause of healthcare-associated candidemia, with increasing reports of fluconazole resistance worldwide. This resistance is most commonly associated with amino acid substitutions in Erg11p, particularly Y132F; however, regional variation in resistance mechanisms and clonal dissemination remains not fully understood. This study investigated the molecular epidemiology and genomic landscape of fluconazole-resistant C. parapsilosis in Paraná, Southern Brazil, over a 10-year period. A total of 54 resistant isolates identified between 2014 and 2024 were retrospectively analyzed; 51 viable isolates were confirmed by species identification, antifungal susceptibility testing, and microsatellite genotyping. A subset of 18 representative isolates underwent whole-genome sequencing for phylogenomic analysis. Variants in genes associated with azole resistance, including ERG11 , MRR1 , TAC1 , CDR1 , MDR1 , ERG3 , and ERG6 , were characterized. Fluconazole resistance emerged in 2018 and increased thereafter. Phylogenomic analysis revealed two geographically structured lineages: a dominant clone circulating across multiple healthcare institutions in the Curitiba metropolitan area and a second lineage restricted to the northern region of the state. The dominant clone showed minimal genomic diversity (0–5 SNPs), consistent with long-term persistence. A conserved resistance profile was observed, with 17 of 18 sequenced isolates harboring the K143R substitution in Erg11p, while all retained the wild-type residue at position 132. The single isolate lacking ERG11 mutations carried a novel C849Y substitution in the Mrr1p regulator. These findings demonstrate the emergence and persistence of a highly clonal fluconazole-resistant C. parapsilosis lineage in Southern Brazil, characterized by a conserved K143R substitution independent of Y132F. The detection of closely related isolates across different hospitals underscores the need for regional genomic surveillance of hospital-adapted fungal pathogens.

Microplastics and warming: dual threats to planktonic protist communities in freshwater ecosystems - Matheus Henrique de Oliveira de Matos; João Vitor Bredariol; Yasmin Rodrigues de Souza; João Vitor Fonseca da Silva; Vinícius Marcelo Souza Castro; Felipe Morais Zanon; Loiani Oliveira Santana; Gabriel Arthur Lopes da Silva; Juliana Regina Kloss; Thomaz Aurélio Pagioro; Luiz Felipe Machado Velho (Hydrobiologia, 2026)

Ractopamine under dietary protein adjustment improves growth performance and carcass traits of immunocastrated and surgically castrated pigs slaughtered 21 days after vaccination - Diego Duran Araujo; Matheus de Almeida Ferreira; Lucas Alves Rodrigues; Idael Matheus Góes Lopes; Marcelo Dourado de Lima; Luíza de Almeida Ramos; Rafaela Jorge Sarsur de Freitas Ribeiro; Hemille Antunes Ferreira Miranda; Isabel Luísa Ribeiro de Abreu Teixeira; Francisco Carlos de Oliveira Silva; Walter Motta Ferreira; Dalton de Oliveira Fontes (Tropical Animal Health and Production, 2026)
The objective of this study was to evaluate the effects of immunocastration and ractopamine hydrochloride (RAC) supplementation on growth performance and carcass traits of male pigs slaughtered 21 days after the second immunization. Sixty-four pigs (Landrace × Large White, initial body weight 103.05 ± 0.67 kg) were individually tagged and randomly assigned to a 2 × 2 factorial arrangement in a completely randomized design, consisting of two castration methods (immunocastrated vs. surgically castrated) and two dietary RAC levels (0 or 10 ppm). No castration method × RAC interactions were observed for any variable ( P > 0.05). Immunocastrated (IM) pigs exhibited 19.5% greater average daily gain (ADG) and 13% lower feed-to-gain ratio (FG) compared with surgically castrated (SC) pigs ( P < 0.05). IM pigs also showed reduced backfat thickness across all measurement sites and greater lean meat percentage, whereas SC pigs had higher carcass yield ( P < 0.05). Ractopamine supplementation under increased amino acid supply increased ADG by 13.6%, improved hot carcass weight by 3.1%, and reduced FG by 13% ( P < 0.05). Overall, immunocastration improved growth performance and carcass leanness, while RAC supplementation increased average daily gain by 13.6%, confirming its additive effect under a shortened 21-day post-immunization interval. Immunization against GnRH combined with RAC feeding represents an effective strategy for producing heavy-weight finishing pigs with improved efficiency.

A mechanistic approach about oxidative, mutagenic, and cytotoxic effects of an organotellurane - Felipe Emannuel Alvino de Jesus; Octávio Augusto de Carvalho Maia; Antonielly Campinho dos Reis; Audinei de Sousa Moura; Anderson Nogueira Mendes; Glissia Lysandra dos Santos Marciel; Jefferson da Cruz Esteves; Shamya Gabriella Corrêa Coêlho; Isabela Ribeiro de Sá Guimarães Nolêto; Maria Luísa Lima Barreto do Nascimento; Adriana Maria Viana Nunes; Débora Caroline do Nascimento Rodrigues; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Organotellurium (OTe) compounds have pharmacological properties, including leishmanicidal, antimalarial, and antifungal activities. Herein, we assessed cytotoxicity effects of OTe RF07 in a panel of tumor cell lines, as well as its oxidative, toxicity, and hemolytic actions. The toxicity was evaluated on Allium cepa and Artemia salina larvae. Cell viability was also assessed by resazurin in murine cells (Sarcoma 180), human cells (HL-60, leukemia; AGP01, gastric adenocarcinoma; SKMEL-28, human melanoma; MRC-5, normal fibroblasts), and dog erythrocytes. The oxidative capacity of RF07 was evaluated by wild-type and antioxidant-mutated enzyme strains of Saccharomyces cerevisiae . RF07 presented cytotoxic action on all normal and tumor cells, whose IC 50 ranged from 0.07 μg/mL (HL-60) to 73.45 μg/mL (Sarcoma 180) and toxicological activity on A. salina nauplii in a concentration-dependent manner after exposure for 24 h and 48 h (LC 50 values of 15.02 and 5.43 μg/mL for 24 h and 48 h, respectively). Moreover, RF07 reduced mitotic index of meristematic A. cepa cells at 5, 10 and 20 μg/mL, caused arrest in interphase, and increased chromosomal changes, including micronucleus, c -metaphases, and chromosomal bridges, loss, and delays. In summary, RF07 exhibits antiproliferative action on animal cells, high toxicity on Artemia salina nauplii, as well as clastogenic effects on growing roots. This antimitotic action is not related to direct membrane damage, although it relies on chromosomal injuries and may be related to the induction of oxidative stress as observed in yeast cells.

Environmental variables in regulatory models: Lessons from electricity distribution in Brazil - Tatielle Menolli Longhini; Marcelo Azevedo Costa; Bruno de Almeida Vilela; Ana Beatriz Rodrigues Alves Branquinho Barbosa (Utilities Policy, 2026)

Regional patterns of environmental variability in mangrove ecosystems along the southeastern Brazilian coast - Marcelo Antonio Amaro Pinheiro; Luis Felipe de Almeida Duarte; Caio Rodrigues Nobre; Esli Emanoel Domingues Mosna; Rodrigo dos Santos Rodriguez-Lopes; Todor Petkov; Aleksandar Dimitrov; Dimitrinka Ivanova (Regional Studies in Marine Science, 2026)

A Kappaphycus alvarezii aqueous extract improves yield and kernel quality in barley (Hordeum vulgare L.) - Felipe Souza Dutra; Eva Regina Oliveira; Aline Nunes; Alex Ricardo Schneider; Gadiel Zilto Azevedo; Luana Vanessa Peretti Minello; Lohan Rodrigues Brandão Santos; Isabella Feijão de Araújo; Sidnei Moura; Marcelo Maraschin (Journal of Applied Phycology, 2026)
The search for sustainable agricultural inputs has increased the interest in biostimulants based on macroalgae. An aqueous extract of Kappaphycus alvarezii , a red seaweed rich in bioactive compounds, has emerged as a promising biostimulant for various crops, in Brazil, but its effects on barley ( Hordeum vulgare L.) remain underexplored. This study investigated the influence of foliar application of different concentrations, i.e., 0, 1, 2, 5, and 10% v/v, of a crude aqueous extract, derived from biomass cultivated in Santa Catarina, southern Brazil. The morphology, yield, and biochemical parameters of leaves and kernels, from treated plants in pots, in a greenhouse were measured. In contrast to the growth-promoting effects reported for other extracts of seaweeds, this Kappaphycus extract did not alter the plant architecture, but selectively enhanced reproductive output, suggesting an optimization of resource allocation towards grain development. It was seen that grain set increased at lower concentrations (1–2%) and the thousand-kernel weight at higher doses (5–10%). Biochemically, this specific extract elevated leaf amino acids by up to 47.4% at the 1% concentration, as compared to control. In addition, treatments selectively enhanced kernel qualities, including starch (+ 19.3%, at 5%), protein (+ 10.3%, at 10%), and amino acids (+ 56.6%, at 1–2%), while maintaining germination viability above 98.5%. PCAs revealed a clear segregation, isolating the control from all treatments, which formed distinct clusters in all parameters. The results demonstrated that the K. alvarezii extract used in this study could be an effective tool for enhancing barley kernel quality, particularly for the malting industry, by optimizing reserve accumulation, without compromising plant morphology and seed germination.

Age-specific climate sensitivity of respiratory hospitalizations in a tropical coastal city: 20-year Random Forest forecasts - Marcos Paulo Santos Pereira; Rafaela Lisboa Costa; Fabricio Daniel dos Santos Silva; Glauber Lopes Mariano; Heliofabio Barros Gomes; Helber Barros Gomes; Djane Fonseca da Silva; João Otávio Alves Accioly; Jean Souza dos Reis; Eva Maria Mollinedo Veneros; Bruno Coelho Bulcão; Marcelo Félix Alonso; et al. (International Journal of Biometeorology, 2026)
Respiratory diseases remain a major public health challenge in tropical coastal cities, where persistent heat-humidity interactions and climate variability shape population vulnerability. This study quantified associations between atmospheric conditions and respiratory hospitalizations in Maceió, Brazil, using a 20-years time series (2000–2019). Weekly hospitalization rates stratified by age (children 0–4 years, adults 5–59 years, elderly ≥ 60 years), were modeled against meteorological variables—including temperature, relative humidity, precipitation, atmospheric pressure, and solar radiation—considering lag structure of 0, 1, and 2 weeks. Random Forest regression models were applied to capture nonlinear relationships and forecast hospitalization rates. Minimum temperature was the dominant predictor, exhibiting strong inverse associations across all age groups (ρ = − 0.65, p < 0.001), with effects persisting up to two weeks. Age-specific patterns were observed: children showed immediate sensitivity to thermal and precipitation variables, whereas elderly populations exhibited delayed responses to barometric pressure and evaporation. Model performance was high for children and adults (R 2 = 0.83–0.90) and moderate for the elderly, with Symmetric Mean Absolute Percentage Error ranging from 13 to 25% across groups. Long-term trends revealed declining hospitalization rates among children and adults, contrasted by stabilization and subsequent increases in the elderly after 2010, consistent with demographic aging and increased climate sensitivity. These findings demonstrate the value of machine learning approaches for modeling complex climate-health relationships and provide a transferable framework for climate-informed respiratory risk assessment and early warning systems in tropical coastal environments.

Application of FT-IR spectroscopy using the IR Biotyper® for Leptospira: protocol optimization and first spectral insights - Amanda Maria Jesus Bertani; Elaine Santos Lima; Natalia da Cunha Nobrega; Marcelo Sansone; Juliana Alves Garcia; Daniela Leite; Gisele Oliveira de Souza; Tamires Santos de Arruda; Ricardo Polatto; Eliete Calo Romero; Tania Sueli de Andrade; Karoline Rodrigues Campos; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Genomic analysis of Streptococcus pyogenes emm1-type isolates reveals M1UK circulation and a genetically distinct Brazilian sublineage - Gisele Aparecida Bernardi; Luiza Souza Rodrigues; José Ferreira da Cunha Neto; Geiziane Aparecida Gonçalves; Lavinia Nery Villa Stangler Arend; Sabrina da Conceição Barbosa; Marcelo Pillonetto; Tadayoshi Ikebe; Yukihiro Akeda; Norihiko Takemoto; Felipe Francisco Tuon (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Background Streptococcus pyogenes (GAS) causes diseases ranging from mild pharyngitis to severe invasive infections. The emm 1 type is the most prevalent worldwide, and a highly transmissible variant, M1 UK , characterized by increased speA expression, has recently emerged and spread globally. Objective To characterize the genomic diversity of invasive GAS isolates collected from severe cases and epidemiologically important outbreaks in Brazil. Methods Whole-genome sequencing was performed on 229 invasive GAS isolates collected in Brazil between January 2023 and November 2024. Genomes were analyzed for emm typing, lineage assignment, and virulence gene profiling. Comparative genomic analyses, including global M1 global and M1 UK genomes, were performed to contextualize the Brazilian isolates within the global population structure. Results Thirty-four distinct emm types were identified, with emm 1 accounting for 52.4%. Of these, 14% were confirmed as M1 UK clones, detected across multiple Brazilian regions. Comparative genomic analysis showed that the remaining emm 1 isolates clustered into a well-supported group representing a genetically distinct Brazilian sublineage (Br clade). Conclusion The detection of M1 UK isolates in multiple Brazilian states indicates that this lineage is circulating in the country. Most emm 1 isolates analyzed in this study belonged to the Br clade rather than the M1 UK lineage, suggesting that the distribution of emm 1 sublineages in this selected dataset differs from patterns reported in countries where M1 UK has become predominant. These findings highlight the importance of genomic and public health surveillance to monitor and control the spread of invasive GAS infections.

Improving drought tolerance in pre-sprouted sugarcane through inoculation with plant growth-promoting bacteria: assessment of biochemical activity, nutrient uptake, and physiological performance - Carlos Henrique de Castro Nogueira; Hariane Luiz Santos; Lusiane de Sousa Ferreira; Melina Rodrigues Alves Carnietto; Marcelo de Almeida Silva (Plant and Soil, 2026)
Background and aims Pre-sprouted sugarcane seedlings are increasingly used to ensure uniform crop establishment; however, their performance is highly constrained by water deficit under climate change scenarios. This research evaluated whether a consortium of Bacillus licheniformis (FMCH001) and Bacillus subtilis (FMCH002) could mitigate drought stress by improving root development, soil microbial activity, and plant nutritional and physiological responses under different water regimes. Methods The experiment was conducted in a randomized block design using a 4 × 2 factorial scheme, with four water regimes (20, 40, 60, and 80% of field capacity) and two inoculation treatments (with and without bacteria), with four replicates. Results Bacillus inoculation alleviated the adverse effects of water deficit, particularly under severe water restriction (20, 40, and 60% of field capacity), by increasing root length, surface area, volume, and diameter. Inoculated treatments showed higher arylsulfatase, β-glucosidase, acid phosphatase, and urease activities, indicating enhanced soil microbial functioning. These responses were associated with increased leaf concentrations of N, P, K, Ca, Fe, and Zn. Furthermore, inoculated plants exhibited improved photosynthetic performance, including higher PSII efficiency, electron transport rate, net CO 2 assimilation, water use efficiency, and carboxylation efficiency, contributing to better establishment and development throughout the sugarcane growth cycle. Conclusion Inoculation with Bacillus subtilis and Bacillus licheniformis mitigated the effects of water deficit in pre-sprouted sugarcane seedlings by promoting root development, enhancing soil microbial activity, and increasing nutrient acquisition, thereby improving plant mineral nutrition and photosynthetic performance.

Late Quaternary change in sources and burial of organic carbon off Northeastern Brazil - Alice Maria da S. Rodrigues; Rodrigo de L. Sobrinho; Patrícia Piacsek; Ioanna Bouloubassi; Arnaud Huguet; Ana Luiza S. Albuquerque; Igor M. Venancio; Thiago P. Santos; Joana F. Cruz; Marcelo C. Bernardes (Quaternary Science Reviews, 2026)

Effects of dried distillers grains supplementation on intake, digestibility, metabolism, and performance of suckling beef calves on pasture - Edinael Rodrigues de Almeida; Johnnatan Castro Cabral Gonçalves; Jean Marcelo Albuquerque; Luanna Carla Coelho; Patrícia Siqueira Leite; Lilian Yukie Pacheco Toma; José Augusto Moura Godinho; Laura Ferrarez Ricardo; Julia Liliane Vieira; Cláudia Batista Sampaio; Edenio Detmann; Ériton Egídio Lisboa Valente; et al. (Tropical Animal Health and Production, 2026)
The supply of metabolizable nutrients to suckling beef calves on pasture can improve their performance, increasing weaning weight and productivity in cow–calf systems. The objective was to evaluate the effects of dried distillers grains (DDG) inclusion on intake, digestibility, metabolism, and performance of suckling beef calves grazing tropical pastures. Forty-eight Nellore calves, 120 ± 35 days of age and 135 ± 23.4 kg of body weight (BW), were used. During 117 days, calves received one of the following treatments under a creep-feeding strategy: mineral mixture only, provided ad libitum (CONTROL); or concentrate supplementation (SUP, 6 g/kg BW, containing 225 g/kg crude protein) with 0% (SUP0), 48.4% (SUP48), or 96.8% (SUP96) DDG inclusion. Concentrate supplementation increased intake of dry matter (DM), crude protein (CP), non-fibrous carbohydrates (NFC), total digestible nutrients (TDN), and the CP/digestible organic matter ratio ( P < 0.10). Digestibility of DM, CP, and NFC decreased linearly with increasing DDG inclusion. Serum glucose, insulin-like growth factor 1, and blood urea nitrogen concentrations were higher in calves on concentrate supplementation ( P < 0.10). Concentrate supplementation increased average daily gain, weaning BW, and ribeye area ( P < 0.10), with no differences related to DDG inclusion ( P > 0.10). Supplementation improves beef calves nutritional characteristics, metabolism and performance. Additionally, DDG can be included in supplements for suckling beef calves grazing tropical pastures, with potential to replace traditional feedstuffs such as corn and soybean meal, without negatively affecting performance and serum metabolism.

Synthesis and characterization of chitosan-functionalized nanostructured lipid carriers with temozolomide: cytotoxic effects and chromosomal instability in human glioblastoma cells - Helber Alves Negreiros; João Pedro Alves Damaceno do Lago; Victor Alves de Oliveira; Lia Raquel Alves Silva; Ana Carolina Lima de Melo; Igor Gabriel Barbosa de Sousa; Jefferson da Cruz Esteves; Sérgio Eduardo Matos Cazarotti Francisco; Samuel Lemos Paiva; João Pedro Crispim Guerra Rodrigues; Lucas Medeiros Martins Carvalho; Pedro Henricke Oliveira de Souza; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Multiform glioblastoma (GBM) is the most aggressive primary brain tumor, associated with high heterogeneity, treatment resistance, and poor survival. Temozolomide (TMZ), although the main chemotherapeutic agent used, shows limited efficacy due to low solubility, chemical instability, and acquired resistance. In this context, nanostructured systems can enhance their antitumor efficacy. This study aimed to develop and characterize chitosan-functionalized nanostructured lipid carriers loaded with Temozolomide (NLCTQ), as well as to assess their biological activity in human glioblastoma cells (U87-MG). Lipid nanoparticles functionalized with chitosan were prepared by hot emulsification and sonication. Physicochemical characterization included DLS, zeta potential, FTIR, and HPLC for drug quantification and encapsulation efficiency. Biological activity was evaluated in U87-MG cells using the cell viability assay MTT and trypan blue, the comet assay, the spheroid model, fluorescence cell death, and the CBMN assay. The formulation presented a homogeneous nanometric size and positive zeta potential, although with moderate encapsulation efficiency (39%). Biological assays demonstrated that NLCTQ significantly reduced cell viability, overcoming the U87-MG cell line’s resistance to TMZ by achieving cytotoxicity at doses up to 20 times lower than free TMZ. Additionally, NLCTQ promoted the formation of biomarkers of chromosomal instability, such as micronuclei, bridges, and nuclear buds, which may explain the observed cytotoxic effects. Together, the results indicate that TMZ nanoencapsulation in NLCTQ enhances its antitumor efficacy, representing a promising strategy to overcome the limitations of conventional chemotherapy in glioblastoma treatment.

The Role of Gene Flow in the Diversification of the Monkey Treefrog Complex Across the South American Dry Diagonal - Felipe Camurugi; Vinícius A. São Pedro; Felipe Magalhães; Marcelo Gehara; Eliana F. Oliveira; Gabriel C. Costa; Frank T. Burbrink; Edward A. Myers; Guarino R. Colli; Miguel T. Rodrigues; Adrian A. Garda (Zoologica Scripta, 2026)
Understanding Neotropical megadiversity remains challenging due to fundamental taxonomic issues, including identifying and describing cryptic species and their distribution, and the limited knowledge of key factors driving biological diversification. Such challenges are especially prominent in diverse clades with high levels of cryptic species, such as many Neotropical frogs. Herein, we conduct a mitochondrial phylogenetic study on monkey treefrogs in the genus Pithecopus and a multilocus analysis of the P. hypochondrialis species group throughout its distribution in the South American dry diagonal (DD). Our goals were to infer the main lineages and identify historical factors that led to their divergence. Among nine currently recognised species, we found 14 well‐structured mitochondrial lineages in two main clades, which diversified during the Paleogene/Neogene transition. The lowland clade is widely distributed in the DD, and our multilocus analysis suggests it comprises seven geographically structured lineages: P. azureus , two lineages of P. hypochondrialis , two species and one lineage for the P. nordestinus complex, and Pithecopus sp. Considering the geomorphological history of the region, diversification may have been promoted by allopatric speciation during Miocene paleogeographic events, especially the Brazilian Plateau compartmentalization and fluctuations in the São Francisco River water volume. Furthermore, gene flow between some lineages may be explained by niche conservatism and demographic expansions during the late Pleistocene, a period marked by climatic fluctuations and biome shifts. Our results reinforce the importance of both Neogene tectonic activity and Quaternary climatic fluctuations in shaping the Neotropical biota.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Cyanidin-3-glucoside reduces cell migration and inflammatory profile of acute leukemia cells - Luciene Assaf; Edson Naoto Makyiama; Beatriz Almeida; Jeremias Martins de Almeida Junior; Carlos Eduardo da Silva Gonçalves; Sumara de Freitas; Rosana Lopes Rodrigues Amon; Bruna Roberta Oliveira Neves; Marcelo Macedo Rogero; Ricardo Ambrosio Fock (Natural Product Research, 2026)

Microscale sealed vessel (MSSV) technique in petroleum systems: a review - Sandra B. Jorge; André L.S. Pestilho; Juliana M. Sousa; Antônia M. Corrêa; Hemmely G. de S. Severino; Alice Maria S. Rodrigues; Kátia Z. Leal; Cleverson J.F. de Oliveira; Daniel S. Dubois; Marcelo C. Bernardes (Organic Geochemistry, 2026)

A stepwise methodology for developing fish sperm cryopreservation protocols: application to the endangered Pogonias courbina - Jhony Lisbôa Benato; Nathalia dos Santos Teixeira; Rômulo Batista Rodrigues; Karel Torres Lozano; Renata Villar Dantas; Eduardo Thomé Nicoleti; Gregory Valdivia-Gutiérrez; Leonardo Queiroz de Alencar; Wik Maik Santos Barros; Marcelo Hideo Okamoto; Ricardo Vieira Rodrigues; Luis Andre Sampaio; et al. (Cryobiology, 2026)

Negative impacts of zinc molybdate nanoparticles on multiple endpoints of a freshwater Chlorophyceae - Lays de Oliveira Gonçalves Alho; Renan Castelhano Gebara; Cínthia Bruno de Abreu; Giseli Swerts Rocha; Marcelo Assis; Ana Luiza de Carmargo Doimo; Mayra Luiza Rodrigues Gonçalves; Marisa Carvalho de Oliveira; Júlia Mendonça Margatho; Juliana Cancino Bernardi; Júlio César Reis Martins da Silva; Renan Augusto Pontes Ribeiro; et al. (Aquatic Toxicology, 2026)

Diagnosing Quality Management Maturity in Sugar Mill Evaporation Systems: An Integrated Approach - Eder Cezano Gonçalves; Marcelo Girotto Rebelato; Andréia Marize Rodrigues; Leonardo Lucas Madaleno (Sugar Tech, 2026)
Quality management in continuous process industries requires systemic approaches capable of integrating strategy, operational control, information governance, and organizational learning. In sugar mills, the evaporation sector plays a critical role in thermal efficiency, operational stability, and product quality, yet managerial maturity in this area remains insufficiently structured in the literature. This study proposes and applies an integrated diagnostic framework to assess the maturity of quality management in the evaporation sector of a large sugarcane processing plant. The framework was structured into nine interdependent subsystems and operationalized through a 96-question instrument. Question weights were determined using the Improved Analytic Hierarchy Process, and inter-rater reliability was assessed through the Intraclass Correlation Coefficient. The results indicated good agreement among experts in the weighting stage and statistically adequate reliability. The evaluated sector presented intermediate maturity, with strengths in strategic alignment and quality planning, and limitations in information governance, analytical use of indicators, documentation standardization, and structured human resource development. The findings suggest that improving the integration between data analysis, decision-making, and continuous learning is more critical than increasing isolated control mechanisms. The proposed framework contributes a structured and replicable tool for diagnosing managerial maturity in continuous process environments and supports prioritization of improvement actions aligned with operational performance and long-term sustainability.

Bioabsorbable anti-infection system for orthopedic implants - Marcelo Augusto Brito Madureira; Rodrigo César Gomes; Arnaldo Rodrigues dos Santos; Adriana Cristina Motta; Cecilia Amélia de Carvalho Zavaglia (In vitro models, 2026)

The emergence of pathogens on fish in an impacted estuary and the role of non‐native piranhas in a potential bacterial infectious outbreak - Ryan Andrades; Helder C. Guabiroba; Kathiani V. Bastos; Vítor L. A. Rodrigues; Marcelo R. D. Santos; Clarisse M. Arpini; Mayra Cunha Flecher; Helen A. Pichler; Ciro C. Vilar; Maurício Hostim‐Silva; Jean‐Christophe Joyeux (Journal of Fish Biology, 2026)
As many tropical aquatic ecosystems worldwide, the Doce River estuary (DRE, southeastern Brazil) has increasingly faced multiple anthropogenic threats, including deforestation, mining, species introduction and water management. The 2015 collapse of the Fundão iron ore tailings dam severely changed water properties and increased heavy metal concentration in sediment. However, the potential synergistic effects of the observed threats on fish populations remain largely unknown. After detecting an elevated number of fin lesions in DRE fishes, we used the catfish Genidens genidens (Cuvier, 1829) to investigate whether such mutilations originated from fin‐nipping by non‐native piranha or emerged as a result of fin rot disease through bacterial infection. One third of the examined individuals had fin lesions in the DRE, whereas no conspecific exhibited such lesions in two control estuaries where piranhas are absent; lesions were restricted to the caudal fin, a region known to be targeted by fin‐nipping piranhas. Independently of the presence of fin lesion, culture of fins and livers indicated higher prevalence and variety of bacterial strains in DRE individuals than in a control area. Piranhas likely contribute to the fin lesions in DRE fishes. However, the higher prevalence and variety of bacterial pathogens as well as of liver and kidney disorders identified in fin‐healthy and mutilated fishes of the DRE suggest that the heavily metal‐polluted conditions in the DRE may be associated with the emergence of bacterial infections in fish.

Low doses of ascorbic acid modulate the effect of chemotherapy agents in sarcoma 180 tumor-bearing mice - Josemar José da Silva Júnior; Leonardo da Rocha Sousa; Victor Alves de Oliveira; Antonio Lima Braga; Ag-Anne Pereira Melo de Meneses; Ricardo Melo de Carvalho; Joedna Cavalcante Pereira; Reyca Rodrigues e Silva; Raí Pablo Sousa de Aguiar; Antonielly Campinho dos Reis; Sérgio Eduardo Matos Cazarotti Francisco; Shamya Gabriella Corrêa Coêlho; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Multi-site evaluation of phosphorus fertilization with bio-inputs in sugarcane: Yield and soil P fractions - Gabriel Pinheiro Silva; Sarah Mello Leite Moretti; Ingrid Martins Stelutti; Paulo Sergio Pavinato; Otávio Gonçalves Cesário; Marcelo Grijalva Carneiro Barros; Johnny Rodrigues Soares; Rafael Otto (Field Crops Research, 2026)

Phylogenetic diversity recovery along Atlantic Forest succession: The potential for conserving evolutionary history - Alex Josélio Pires Coelho; Carlos Mário Galván-Cisneros; Pedro Manuel Villa; Heitor Mancini Teixeira; Fabio Antônio Ribeiro Matos; Alice Cristina Rodrigues; Nayara Mesquita Mota; Fernando da Costa Britod Lacerda; Fábia Maria dos Santos Souza; Nathália Vieira Hissa Safar; Nathália Silva; Fabiana Bonani; et al. (Biological Conservation, 2026)

A survey of vector-borne bacteria in bat-associated mites (Mesostigmata: Macronyssidae and Spinturnicidae) from Brazil reveals the presence of Ehrlichia spp. - Luís Fernando da Cruz; Victor de Souza Mello-Oliveira; Maria Eduarda Moraes das Chagas; Gabriella Soares; Ana Cláudia Calchi; Ana Carolina Castro-Santiago; Leormando Fortunato Dornelas-Júnior; Érica Munhoz de Mello; Igor Massahiro de Souza Suguiura; Elizabete Captivo Lourenço; João Carlos Marocco; Letícia Dorigoni; et al. (Veterinary Research Communications, 2026)

Hyperdominant Trees Reveal Savanna Vulnerability Under Climate Change - Facundo Alvarez; Ben Hur Marimon‐Junior; Beatriz Schwantes Marimon; Wesley Jonatar Alves da Cruz; Norberto Gomes Ribeiro Júnior; Raiane Gonçalves Béu; Polyanna da Conceição Bispo; Aldair de Souza Medeiros; Glécio Machado Siqueira; Marcelo Leandro Bueno; Fabiana de Gois Aquino; Frederico Augusto Guimarães Guilherme; et al. (Global Change Biology, 2026)
The Cerrado biome, spanning ~2 million km 2 , is one of the most extensive and biodiverse tropical savannas, yet it is paradoxically dominated by only 30 hyperdominant tree species (~2% of all species, > 50% of all stems). However, their vulnerability to climate change and the effectiveness of current conservation efforts remain uncertain. By combining (i) species distribution models calibrated with edaphic‐climatic predictors and occurrence data for hyperdominant Cerrado trees with (ii) functional‐trait analyses related to ecological strategies (leaf economics, bark investment, ecophysiology, drought tolerance, regeneration, and dispersal), we identified the biomass production and reproductive traits that best predict species persistence under high‐emission scenarios (RCP8.5). Currently, only 427,980 km 2 (~17.4%) of the modeled potential environmental suitability falls within protected areas; under future climate scenarios, this protected suitable area is projected to decline by ~45.9% to 231,377 km 2 (~18.1%). This loss, resulting from land conversion with the expansion of agricultural frontiers and fire events, highlights a mismatch in current regional conservation priorities, overlooking the needs of the Cerrado and its associated biodiversity. Given ongoing land‐use change and that 58% of remaining native vegetation occurs on private lands, this mismatch highlights the urgent need to align conservation and agricultural policy. Functional trait analyses revealed a clear gradient from acquisitive “fast” to conservative “slow” strategies, reflecting trade‐offs in water‐use efficiency and biomass allocation, with leaf structural and reproductive traits best predicting species resilience to climate change. Our results indicate that a small subset of hyperdominant species not only forms current community structure but also signals the biome's resilience/vulnerability to climate change. Conservation planning should prioritize identified climate refuges and be based on functional traits to buffer the loss of functional and structural integrity in one of the world's richest and most threatened savanna ecosystems.

Immune Mediator Profile in the Inflammatory Microenvironment Reveals Potential Biomarkers of Wound Healing in Localized Cutaneous Leishmaniasis - Jaqueline Paulino de Souza; Célia Maria Ferreira-Gontijo; Francislane Ramalho Varella Pereira; Marcela Tavares Caldas Eller; Matheus Figueiredo Garrocho Ottoni-Vieira; Julia Pereira-Martins; Maryana Prates Rodrigues; Joaquim Pedro Brito-de-Sousa; Ariane Soares Nascimento; Maria Nilza Pereira de Brito; Bruno Oliveira Souza e Silva; Thadeu Ramalho da Silva; et al. (Current Tissue Microenvironment Reports, 2026)
Localized cutaneous leishmaniasis (LCL) is the most prevalent form of leishmaniasis, with infection control primarily dependent on cell-mediated immunity. Lesion healing results from a complex interplay among immune cells and soluble mediators. Using Luminex technology, we evaluated circulating and lesion microenvironment immune mediators, including chemokines, cytokines, and growth factors, in patients with LCL and nonspecific dermatitis. A robust proinflammatory response was observed in the lesion microenvironment of LCL patients, characterized by elevated levels of growth factors, important immune mediators potentially involved in tissue repair. Predictive modeling identified FGF, G-CSF, GM-CSF, IL-2, and IL-9 as key immune mediators distinguishing LCL from nonspecific dermatitis. Our results reveal that LCL presents a distinct soluble immune mediator signature from nonspecific dermatitis, exhibiting a set of biomarkers that not only define its immune mediator signature but also signal a possible role in the tissue repair process. Furthermore, we characterized the profile of soluble immune mediators of LCL patients, categorized according to the time evolution lesion. Our analysis revealed a predominance of biomarkers within the lesion microenvironment in patients with recent lesions (< 2 months of evolution). On the other hand, in late lesions patients (> 2 months of evolution), our data showed a predominance of biomarkers in the systemic circulation. Collectively, these findings provide novel insights into the immunopathogenesis of LCL and highlight candidate immune mediators for targeted prognostic evaluation.

Phenotypic plasticity of Gliricidia sepium in response to planting densities - Eduardo Bazan Machado; Marcelo Rodrigues; Eduardo João Pereira Junior; Flávio Hiroshi Kaneko; Vanessa Cury Galati; Gervásio Pegoraro; José Carlos Batista Dubeux Jr; Evandro Neves Muniz; Lucas Davi Soares de Oliveira; Flavia de Oliveira Scarpino van Cleef; Eric Haydt Castello Branco van Cleef (Brazilian Journal of Botany, 2026)

Origin, viability, and cell cycle status of seminal somatic cells for potential application in cattle cloning via nuclear transfer - Higor da Silva Ferreira; Gabriella Borba de Oliveira; Eduardo de Oliveira Sanguinet; Ana Laura da Silva Feijó; César Augusto Pinzón-Osorio; Verônica Rafaela Benvenutti; Louise Fontoura Köhler; Marianna Bertolini; Fernando Almeida-Souza; Felipe de Jesus Moraes Junior; David Driemeier; Ana Lúcia Abreu-Silva; et al. (Reproductive Biology, 2026)

A Holistic Assessment of Climate Change, Land Use, and Water Governance Through Complex Water Systems - Carolina Stager Quaggio; Lucas Vituri Santarosa; Philip Moffatt; Marcelo Donadelli Sacchi; Bruno Valdambrini; Amanda Rodrigues Soares; Jan Boll; Didier Gastmans (Water Resources Management, 2026)

A sequential post-selection testing procedure for univariate congruence models with nested and non-nested hypotheses - Vinicius Francisco Rofatto; Ivandro Klein; Jhonatta Willyan Miato Assunção; Lincon Rodrigues Silva; Paulo de Oliveira Camargo; Mauricio Roberto Veronez; Luiz Gonzaga da Silveira; Marcelo Tomio Matsuoka (Journal of Geodesy, 2026)
Least-squares-based testing procedures for unstable-point identification in geodetic monitoring networks are vulnerable to the smear effect, whereby the influence of a true displacement spreads over several coordinate differences. This leads to a displaced point classified as stable (masking) and a stable point classified as unstable (swamping), a problem that becomes more severe when several points move simultaneously. Recent sequential and combinatorial procedures reduce these effects, but they often lack explicit control of the stepwise false-alarm rate and do not treat post-selection in a formal way. This paper presents SEQCUP, a sequential combinatorial post-selection testing procedure for univariate congruence models when the number and location of displaced points are unknown. The method uses two-epoch observation differences, remains invariant with respect to datum definition, and retains a strictly linear congruence model. At each stage, SEQCUP compares the current null model with higher-dimensional alternatives by means of a quadratic-form statistic built from the difference between their orthogonal projection matrices. The critical value is calibrated with Monte Carlo simulations under the parameterized null displacement model, conditional on the data-driven model selected at the previous stage, so that the resulting test remains valid for both nested and non-nested hypotheses within a unified framework. A stopping rule also limits the maximum number of points inspected in the sequential procedure. It relies on the network topology, excludes models that share the same projector, and uses a normalized distance between projectors to avoid stages with potentially weak separability and pronounced smear effects. Numerical experiments with trilateration, GNSS baseline, and levelling networks, together with literature-based scenarios, show that SEQCUP controls false alarms effectively and attains high mean success rates for model identification over a wide range of signal-to-noise ratios. The method performs at least as well as classical procedures and remains comparable to contemporary combinatorial and information-criterion-based methods, with clear advantages in several scenarios involving multiple displaced points and low-to-moderate signal-to-noise ratios.

Metabolic profiling of Metternichia macrocalyx and Metternichia principis (Solanaceae) using LC-ESI-Q-TOF-MS/MS data in molecular networking and chemometric analysis - Thiago Araújo de Medeiros Brito; Anauara Lima e Silva; Yasmin Ferreira de Araújo; Natyele Rodrigues Fonseca; Giulia Cavalcanti Ottino; Domingos Benício Oliveira Silva Cardoso; Josean Fechine Tavares; Lucas Silva Abreu; Marcelo Sobral da Silva (Natural Product Research, 2026)

IMTA Production of Pacific White Shrimp Integrated with Mullet, Sea Cucumber, Oyster, and Salicornia in a Biofloc System - Enrique A. Estévez Hernández; Ivanilson Santos; Laura Moraes; Morena Salala Kashane; Marcelo H. Okamoto; Luís André Sampaio; Dariano Krummenauer; César S. B. Costa; Ricardo V. Rodrigues; Silvia Martínez-Llorens; Luís H. Poersch (Fishes, 2026)
Integrated multitrophic aquaculture (IMTA) emerges as a sustainable strategy to control the excess of solids and inorganic nutrients that tend to increase in the biofloc system (BFT) cycle, since the model integrates organisms from different trophic levels sharing the same system and nutrients. Thus, this study compared a Penaeus vannamei monoculture system with an integrated biofloc system including Mugil liza, Holothuria grisea, Crassostrea tulipa, and Salicornia neei, focusing on water quality and the performance of organisms and systems. This study consisted of three monoculture systems (16 m3; 375 shrimp m−3) and three IMTA systems, composed of a shrimp tank (16 m3), a mullet tank (4 m3; 30 ind m−3), a combined tank (3 m3) for oysters (45 ind m−3) and sea cucumbers (3 ind m−2), and a Salicornia neei bed (2.78 m2; 37 ind m−2). All IMTA systems operated in recirculation without water exchange, using 10% of the established biofloc inoculum. The IMTA system had half the hydrated lime use (2.13 vs. 4.29 kg), lower solids (299.56 vs. 373.33 mg L−1), and reduced sludge production (9.37 vs. 15.87 kg). Shrimp growth was similar in both systems. Mullet grew adequately with a survival rate of 95.8%, but oysters showed a survival rate of 45.7%. Sea cucumber had a survival rate of 100% until day 28, when a marked decline appeared, strongly correlated with rising temperature (>28 °C; r = −0.71). This resulted in a significant increase in solids in the last weeks, suggesting that the population decline reduces solids control capacity. Furthermore, the biofloc in IMTA was dominated by coccoid forms, with lower proportions of filamentous and cyanobacterial forms.

Simulation, technical-economic evaluation and risk analysis of the purification of eucalyptus bark bio-oil obtained by the fast pyrolysis process - Stéphani Caroline de Lana Arêdes; Fábio de Ávila Rodrigues; Marcelo Moreira da Costa (Biomass and Bioenergy, 2026)

Diversity and Predicted Impact of miRNAs in Human MSCs-derived Extracellular Vesicles - Thaynan Escarião da Nóbrega; Hellen Ferreira de Souza Sobrinho; Camila da Silva Menezes; Giovani Bressan Fogalli; Ana Paula de Souza; Douglas Victorino Esposito; Larissa Lopes Rodrigues; Haiyan Hu; Marcelo Rocha Marques (Stem Cell Reviews and Reports, 2026)

Exploring Lamiaceae diterpenoids as potential multitarget therapeutics for leishmaniasis and chagas disease - Renata Priscila Barros de Menezes; Edileuza Bezerra de Assis; Natália Ferreira de Sousa; Jullyanne Maria Saraiva de Souza; Klinger Antônio da França Rodrigues; Luciana Scotti; Josean Fechine Tavares; Marcelo Sobral da Silva; Marcus Tullius Scotti (Molecular Diversity, 2026)

Suboptimal responses to E2/P4-based timed AI protocols compromise pregnancy outcomes in fertile beef cattle: Roles of ovulation timing and semen viability - César Augusto Pinzón-Osorio; Thomaz Kranen Cunha; German Holguin-Sanabria; Marco Alves Machado; Favorino José de Freitas Collares; Luís Henrique de Aguiar; Paula Rodriguez-Villamil; Felipe Ledur Ongaratto; Eduardo Pradebom da Silva; Eduardo de Oliveira Sanguinet; Carolina Silveira da Silva; Daiane Mentz; et al. (Animal Reproduction Science, 2026)

Determination of soil organic carbon and nutrients by diffuse spectrorradiometry in the Cerrado Mineiro region, Brazil: evaluation of strategies for calibration of hyperspectral models - Everson Cezar; Tatiane Amancio Alberton; Evandro Freire Lemos; Nicole Ghinzelli Vedana; Karym Mayara de Oliveira; Luís Guilherme Teixeira Crusiol; Marlon Rodrigues; Renan Falcioni; Jose Alexandre Melo Demattê; Marcelo Henrique Procópio Pelegrino; Marcos Rafael Nanni (International Journal of Remote Sensing, 2026)

Assessment of mercury (Hg) contamination in tropical areas of the Eastern Pacific and Southwestern Atlantic oceans using two species of sea turtles - César Augusto Barrios-Rodriguez; Moisés F. Bezerra; Eric Enrique Flores; Carlos Antonio Vigil-González; Wilfredo Poveda-Pineda; Joelbin de la Cruz; Carlos Eduardo de Rezende; Marcelo Gomes de Almeida; Wanderley Rodrigues Bastos; Luiz Drude de Lacerda (Marine Pollution Bulletin, 2026)

Oocyte competence: A systematic review of omics studies and the state of art - Fernanda Amarante Mendes de Oliveira; Gabriela Rodrigues de Paula; Pamela Mara Celestino Soares; Amanda Fonseca Zangirolamo; Fábio Morotti; Anne Kemmer Souza; Fabiana de Andrade Melo-Sterza; Marcelo Marcondes Seneda (Theriogenology, 2026)

Industrial-scale fermentation of Arara coffee in A 15,000 L bioreactor: Impacts of process variables on quality and sensory profiles - Laila Alonso; Gisele Xavier Ribeiro Costa; Karolina Prisco Borba; Luiza Manuela Alves Braga Cardoso; Marcelo Antônio Duarte da Cruz; Christiano Vieira Pires; Pedro Luiz Lima Bertarini; Matheus de Souza Gomes; Laurence Rodrigues Amaral; Renata Abadia Reis Rocha; Liliane Maciel de Oliveira; Líbia Diniz Santos (Food Research International, 2026)

All Reforestation Methods Can Support Tropical Tree Diversity Recovery, but Drivers and Species Composition Vary - Laura E. Boeschoten; Joannès Guillemot; Juliano van Melis; Lourens Poorter; Ricardo R. Rodrigues; Frans Bongers; Paulo G. Molin; Marielos Peña‐Claros; Vinicius C. Souza; Cássio A. P. Toledo; Patrick Faria Fernandes; Marcelo P. Ferreira; et al. (Global Change Biology, 2026)
Tropical landscapes are undergoing rapid transformation due to human activities and global change. Forest restoration has emerged as a key strategy to mitigate biodiversity loss and climate warming. However, a standardized assessment of how different restoration methods contribute to biodiversity recovery and conservation remains lacking. Here, we present the first comprehensive comparison of tree diversity restoration and the drivers of recovery across five main reforestation methods (naturally regenerating forests, biodiverse restoration plantings, short‐ and long‐rotation tree monocultures, agroforests) relative to three reference systems (agropastoral lands, degraded and conserved forest remnants). Tree inventories were conducted in 519 plots (900 m 2 each) across two forest types (rainforest and seasonally dry forest) in the Atlantic forest of São Paulo state, Brazil, encompassing over 39,000 trees and 869 species. We found that: (1) all reforestation methods except short‐rotation monoculture plots supported tree diversity recovery. In the rainforest, conserved remnant plots maintained the highest average Shannon diversity (Hill 1 = 29 ± 14), while naturally regenerating forests and restoration plantings approached the diversity of degraded remnant plots (15 ± 5). In seasonally dry forest, biodiverse restoration plantings and agroforests reached diversity levels comparable to conserved remnants (15 ± 6). Additionally, (2) recovery was influenced by forest age, climate (water availability), soil fertility, and landscape context, though the relative importance of these factors varied by method. Climate and landscape context were more influential for recovery in naturally regenerating forests, while soil conditions played a greater role in biodiverse restoration plantings. Lastly, (3) species composition in naturally regenerating forests most closely resembled that of conserved remnants. Conversely, restoration plantings and agroforests exhibited high compositional overlap across sites, reducing overall species richness. Our findings underscore the wide variation in biodiversity outcomes among and within reforestation methods, emphasizing that goals and strategies must align with local conditions to maximize benefits in complex tropical landscapes.

Rural dogs (Canis familiaris) as sentinels to ectoparasites and tick borne pathogens around six Atlantic Forest conservation units in Brazil - Pedro Henrique Cotrin Rodrigues; Nelson Henrique de Almeida Curi; Elizabete Pereira Barbosa; Guilherme Ramos Demétrio; Ana Maria Oliveira Paschoal; Rodrigo Lima Massara; Adriano Garcia Chiarello; Marcelo Passamani; Camila Stefanie Fonseca de Oliveira; Daniel Sobreira Rodrigues; Júlia Angélica Gonçalves Silveira (Veterinary Parasitology, 2025)

Vitamins B9 and B12 supplementation protects olfactory function and nigral tyrosine hydroxylase expression in a rotenone model of Parkinson's disease - Daniel A. Macedo; Lais S. Rodrigues; Jéssica L. Ilkiw; Evellyn M. de Azevedo; Adriano D.S. Targa; Marcelo M.S. Lima (Next Research, 2025)

Squeeze of Brazilian subtropical mangroves from a Holocene and Anthropocene perspective - Marcelo C.L. Cohen; Neuza A. Fontes; Erika Rodrigues; Luiz C.R. Pessenda; Marlon Carlos França; Ed Garrett; Junghyung Ryu (CATENA, 2025)

A new carbon quantum dot obtained from acerola (Malpighia glabra) seed waste and its application as a corrosion inhibitor of mild steel in hydrochloric acid - Victor Magno Paiva; Sanair Massafra de Oliveira; Agnes Candido Teixeira; Jairo Eduardo Leiva Mateus; Clara Muniz da Silva de Almeida; Joyce Rodrigues de Araújo; Marcelo Eduardo Huguenin Maia da Costa; Natasha Midori Suguihiro; Eliane D'Elia (Biomass and Bioenergy, 2025)

Antimicrobial resistance in bacteria from pig production chain: a systematic review and meta-analyses focused on the Brazilian context - Gracielle Rodrigues Pereira; Ana Beatriz Portes; Carlos Adam Conte; Marcelo Luiz Lima Brandão; Bernardete Ferraz Spisso (Critical Reviews in Food Science and Nutrition, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Reactive Oxygen Species Regulation Across Retinitis Pigmentosa Animal Models: A 25-Year Systematized Review - Rafael de Freitas Azevedo-Repossi; Rafael Brito; Marcelo Cossenza; Alexandre dos Santos-Rodrigues; Gustavo Costa Ferreira; Hilda Petrs-Silva; Karin C. Calaza; Lucianne Fragel-Madeira (Molecular Neurobiology, 2025)

Development of CND and DRIS Standards for High-Quality ‘Hass’ Avocado Seedling Production - Marcelo Almeida de Oliveira Junior; Danilo Eduardo Rozane; Tatiana Cantuarias-Avilés; Simone Rodrigues da Silva (Journal of Soil Science and Plant Nutrition, 2025)

Shallow-to-mesophotic geomorphic habitats influenced by a drowned incised valley in the Western Equatorial Atlantic - Antonio Rodrigues Ximenes Neto; Lidriana de Souza Pinheiro; Regimário Pereira Lima Filho; David Hélio Miranda de Medeiros; Carlos de Araújo Farrapeira Neto; Marcelo Oliveira Soares; Sérgio Rossi; Jáder Onofre de Morais (Geo-Marine Letters, 2025)

Silicon fertilization enhances the drought tolerance of soybean by maintaining leaf thickness - Mônica Sartori Camargo; Paola Soares de Sousa Gomes; Heloisa Leonardi; Caio Cesar Fuline Capuchi; Karolyne Priscila Oliveira dos Santos; Marcelo de Almeida Silva; João Paulo Rodrigues Marques (Plant and Soil, 2025)

Submerged fermentation with autochthonous Pediococcus pentosaceus enhances physicochemical properties, enriches bioactive compounds, and boosts the antioxidant and antibacterial activities of mandacaru (Cereus jamacaru DC.) fruit - Gracy Kelly Vieira de Vasconcelos Medeiros; Ana Cristina Silveira Martins; Mateus Gomes Vasconcelos; Estefânia Fernandes Garcia; Noádia Priscila Araújo Rodrigues; Marcos dos Santos Lima; Yuri Mangueira do Nascimento; Evandro Ferreira da Silva; Josean Fechine Tavares; Marcelo Sobral da Silva; Thatyane Mariano Rodrigues de Albuquerque; Vanessa Bordin Viera; et al. (Food Chemistry, 2025)

Spatiotemporal patterns of fire foci in the municipality of Rio de Janeiro (Brazil) using satellite data - Givanildo de Gois; Paulo Miguel de Bodas Terassi; Josimar da Silva Freitas; Bruno Serafini Sobral; Edson Rodrigues Pereira Junior; Welington Kiffer de Freitas; Geraldo de Carvalho Neto; Marcelo Alves Muniz; Eliane de Oliveira; Roberta Fernanda da Paz de Souza Paiva; Juaneza Barroso Falcão; Núbia Valéria Ferreira (Stochastic Environmental Research and Risk Assessment, 2025)

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Corrigendum to “Evaluation of the toxic and genotoxic effects of exposure of Drosophila melanogaster to the glutathione-capped AgIn5Se8@ZnS nanocrystals” [Chemosphere, (2025), vol. 381, pages 144482] - Antônio Marcos de Oliveira dos Santos; Danilo Gustavo Rodrigues Silva; Maria Gislaine Pereira; Adrielle Rodrigues Costa; Claudia Rohde; Camila Caroline Lopes Arruda; Antônia Eliene Duarte; Lizandra Ferraz da Silva; Denilson Vasconcelos Freitas; Marcelo Navarro; Maríndia Deprá; Daniela Maria do Amaral Ferraz Navarro; et al. (Chemosphere, 2025)

Long-term vertebrate roadkill monitoring in Central Amazon: Vehicle traffic effect and hotspot inconstancy over time - Aline Souza de Menezes Medeiros; Cintia Cornelius; Edson Rodrigues Costa; Eduardo Venticinque; Paruwe Mario Atroari; Sawa Aldo Waimiri; Ewepe Marcelo Atroari; Tuwadja Joanico Waimiri; Antônio Carlos Andrade do Nascimento; Denice Silva Lima; Marcelo Gordo (Journal of Environmental Management, 2025)

Genome-wide gene expression changes in breast cancer cells following very low-dose exposure to pesticides (glyphosate and atrazine) at drinking water levels - Carolina Panis; Altair Rodrigues Pires de Paula Filho; Stephen Flint Smith; José Oviedo; Marla Karine Amarante; Virginia Concato; Wander Rogério Pavanelli; Marcelo Estevam; Renata Santos Rabelo; Ohanna Maria Menezes Madeiro da Costa; Maiara Ferreira Terra; Bernardo Lemos (Environmental Toxicology and Pharmacology, 2025)

Correction: Distributional projections of an Amazonian fish in native and non-native watersheds of South America in response to climate change - Vitor Gois Ferreira; Eliezer de Oliveira da Conceição; Tatiane Mantovano; Rejane Guimarães Melo; Jonathan Rosa; Ana Paula dos Santos Bertoncin; Leidiane Pereira Diniz; Leonardo Antunes Pessoa; Marcelo Henrique Schmitz; Rafaela Giacomel Rauber; Rosana Müller Padilha Feitosa; Vanessa Ernandes de Amo; et al. (Biological Invasions, 2025)

Assessing DNA damage in sentinel crabs as indicators of tourist impact in the Fernando de Noronha Archipelago, a Marine Protected Area and World Natural Heritage Site in Brazil - Mônica Lúcia Adam; Anderson Rodrigues Balbino de Lima; Marcelo Antônio Amaro Pinheiro; Harry Boos; Rodrigo Augusto Torres (Environmental Monitoring and Assessment, 2025)

Gestational success in a female dog following early repair of an inguinal gravid hysterocele - Gisele Almeida Lima da Veiga; Mariana Semião Francisco Talib; Marcelo Faustino; Roberto Rodrigues da Rosa Filho; Monike Alves Lopes; Guilherme Santos Souza; Laura Lima do Val Carneiro Machado; Camila Infantosi Vannucchi (Research in Veterinary Science, 2025)

Ontogenic, Immunological, and Behavioral Changes of Crack Cocaine Exposure During the Gestational Period - Yngrid Mickaelli Oliveira dos Santos; Igor Santana-Melo; Amanda Larissa Dias Pacheco; Milenna Maria Jatoba Hasten Reiter; Maisa de Araújo Costa; Keyla Silva Nobre Pires; Fernanda Maria Araújo de Souza; Jucilene Freitas-Santos; Mayara Rodrigues Barbosa; Jeferson Santana Ursulino; Marvin Paulo Lins; Rayssa Gabriely Duarte Torres; et al. (Molecular Neurobiology, 2025)

Distributional projections of an Amazonian fish in native and non-native watersheds of South America in response to climate change - Vitor Gois Ferreira; Eliezer de Oliveira da Conceição; Tatiane Mantovano; Rejane Guimarães Melo; Jonathan Rosa; Ana Paula dos Santos Bertoncin; Leidiane Pereira Diniz; Leonardo Antunes Pessoa; Marcelo Henrique Schmitz; Rafaela Giacomel Rauber; Rosana Müller Padilha Feitosa; Vanessa Ernandes de Amo; et al. (Biological Invasions, 2025)

Three new quinones from Senna pluribracteata (Fabaceae) and investigation of their bioactivity in BV-2 microglial cells - Ranna Beatris de Lima Souza; Ana Rita Rodrigues de Almeida Silva Brilhante; Marianna Vieira Sobral; Paulo Bruno Araujo Loureiro; Geraldo Moisés Wanderley Amorim; Maria de Fátima Agra; Ana Carolina Ferreira de Albuquerque; Fernando Martins dos Santos Junior; Marcelo Sobral da Silva; Raimundo Braz-Filho; Josean F. Tavares (Natural Product Research, 2025)

Basalt rock dust as a soil remineralizer in upland rice grown in tropical soils: residual effects on soil fertility, Si availability, and leaf anatomy - Mariana de Carvalho Ribeiro; Aline Redondo Martins; Rodrigo Silva Alves; Luís Gustavo Frediani Lessa; Hamilton Seron Pereira; Fernando Shintate Galindo; Marcelo Carvalho Minhoto Teixeira Filho; Cassio Hamilton Abreu–Junior; Arun Dilipkumar Jani; Gian Franco Capra; Antonio Ganga; Thiago Assis Rodrigues Nogueira (Journal of Cleaner Production, 2025)

Systemic isosporosis in three species of passerine birds - Camila Issa Amaral; Ayisa Rodrigues de Oliveira; Eric Santos Oliveira; Marcelo Coelho Lopes; Maira dos Santos Carneiro Lacerda; Marcelo Pires Nogueira de Carvalho; Roselene Ecco (Veterinary Research Communications, 2025)

Effect of papaya ringspot virus infection in Brazilian Carica papaya accessions under controlled conditions - Catiane dos Santos Braga; Helaine Christine Cancela Ramos; Juliana Saltires Santos; Alex Souza Rodrigues; Renato Santa Catarina; Rosieli Barboza Bispo; Ronaldiane Pereira da Silva; Marcela Santana Bastos Boechat; Marcelo Eiras; Silvaldo Felipe da Silveira; Messias Gonzaga Pereira (Genetic Resources and Crop Evolution, 2025)

Population structure of endemic Atlantic forest spiny rats Trinomys dimidiatus and Trinomys iheringi (Echimyidae) - Marcelo de Assis Passos Oliveira; Anderson Vilasboa; Marcione Brito de Oliveira; Cibele Rodrigues Bonvicino (Conservation Genetics, 2025)

Evaluation of the toxic and genotoxic effects of exposure of Drosophila melanogaster to the glutathione-capped AgIn5Se8@ZnS nanocrystals - Antônio Marcos de Oliveira dos Santos; Danilo Gustavo Rodrigues Silva; Maria Gislaine Pereira; Adrielle Rodrigues Costa; Claudia Rohde; Camila Caroline Lopes Arruda; Antônia Eliene Duarte; Lizandra Ferraz da Silva; Denilson Vasconcelos Freitas; Marcelo Navarro; Maríndia Deprá; Daniela Maria do Amaral Ferraz Navarro; et al. (Chemosphere, 2025)

Deep convolutional networks based on lightweight YOLOv8 to detect and estimate peanut losses from images in post-harvesting environments - Armando Lopes de Brito Filho; Franciele Morlin Carneiro; Vinicius dos Santos Carreira; Danilo Tedesco; Jarlyson Brunno Costa Souza; Marcelo Rodrigues Barbosa Júnior; Rouverson Pereira da Silva (Computers and Electronics in Agriculture, 2025)

The early Aptian marine stratigraphic record in the interior of Gondwana: New insights from the Araripe Basin, Northeastern Brazil - Henrique Parisi Kern; Jorge Villegas-Martín; Gerson Fauth; Fernanda Luft-Souza; Oscar Strohschoen; Lilian Maia Leandro; Alessandra Santos; Mauro Daniel Rodrigues Bruno; Edna de Jesus Francisco Tungo; Marcos Antonio Batista dos Santos Filho; Daiane Ceolin; Simone Baecker-Fauth; et al. (Marine and Petroleum Geology, 2025)

Dynamics of arid desert coastal ecosystem in response to tsunami, tropical cyclone, and drought: A pollen and geochemical study from Baja California Sur, Mexico - Qiang Yao; Kam-biu Liu; Alejandro Antonio Aragón-Moreno; Erika Rodrigues; Marcelo Cohen; Shubo Fang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A physical parameterization for cloudy-sky downward longwave radiation: Validation for tropical and subtropical regions in Brazil - José Marcelo Lopes Júnior; Juan Carlos Ceballos; Simone Marilene Sievert da Costa; Francisco Luiz Leitão de Mesquita; Hallan Souza de Jesus; André Rodrigues Gonçalves (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Socioeconomic, political and environmental consequences on the use of fossil energy in road transport: A case study of the truck drivers’ strike in São Paulo, Brazil - Marcelo Silva Sthel; Leonardo Mota; Fernanda Gomes Linhares; Marcenilda Amorim Lima; Guilherme Rodrigues Lima (Environmental Development, 2025)

Purines and purinergic receptors in primary tumors of the central nervous system - Adinei Abadio Soares; Helamã Moraes dos Santos; Keyllor Nunes Domann; Natália Pratis Rocha Alves; Bernardo Ribeiro Böhm; Carolina Maliska Haack; Kailane Paula Pretto; Emily Sanini Guimarães; Guilherme Francisquini Rocha; Igor Rodrigues de Paula; Lucas Efraim de Alcântara Guimarães; Harlan Cleyton de Ávila Pessoa; et al. (Purinergic Signalling, 2025)

Survival of Xanthomonas phaseoli pv. phaseoli in the soil and the phyllosphere and rhizosphere of crops and weeds - Daniele Maria do Nascimento; Letícia Rodrigues Oliveira; Bianca Cristina Costa Géa; Luana Laurindo de Melo; José Marcelo Soman; Tadeu Antônio Fernandes da Silva Júnior; Antonio Carlos Maringoni (Plant and Soil, 2025)

UVR regulation of photoprotection in Phaeodactylum tricornutum (Bacillariophyceae): roles of light energy doses - Herculano Cella; José Bonomi-Barufi; Camila Lisarb Velasquez Bastolla; Camila Nader; Carlos Yure Oliveira; Rafael Garcia Lopes; Jacó Joaquim Mattos; Paulo Antunes Horta Junior; Henrique Cesar Venâncio; Eva Regina de Oliveira Rodrigues; Marcelo Maraschin; Leonardo Rubi Rörig; et al. (Photosynthesis Research, 2025)

Mass spectrometry-based identification reveals the polymicrobial nature of canine urinary tract infections - Natália Rodrigues Paschoal; Fábio Vinícius Ramos Portilho; Beatriz Oliveira de Almeida; Marcelo Fagali Arabe Filho; Carolina Aparecida Rodrigues; Thaís Spessotto Bello; Patrik Júnior de Lima Paz; Fernando José Paganini Listoni; Márcio Garcia Ribeiro (Brazilian Journal of Microbiology, 2025)

Phenotypical and molecular characterization of Rhodococcus equi isolated from foals in the Agreste region of Pernambuco - Brazil - Alysson Paulo dos Santos Godoi; Gilvannya Gonçalves Sobral; Júlio César da Silva Vieira; Gustavo Ferrer Carneiro; Fabricio Rochedo Conceição; Elizabete Rodrigues da Silva; Marcelo Mendonça (Brazilian Journal of Microbiology, 2025)

Distinct responses of Scytonema hyalinum and Leptolyngbya sp. to water availability and biocrust formation - Vanessa Cristina Rodrigues Ferreira; Luana Gabryella de Sá Lima; Luis Henrique Zanini Branco; Kleber Régis Santoro; Marcelo Metri Corrêa; Renato José Reis Molica (Brazilian Journal of Microbiology, 2025)

‘Carmen Hass’: A New ‘Hass’-Like Avocado Option in Southeast Brazil - Lígia Broglio Micheletti; Tatiana Cantuarias-Avilés; Marcelo Almeida de Oliveira Junior; Edypol Guilherme Baptista; Guilherme Nacata; Simone Rodrigues da Silva (Applied Fruit Science, 2025)

Anatomical traits of epicarp and pericarp in Eugenia involucrata and Eugenia pyriformis: potential implications for postharvest behavior - Marcelo Almeida de Oliveira Junior; Bruna do Amaral Brogio Colli; Liliane Cristina Libório Stipp; Sandra Maria Carmello-Guerreiro; Simone Rodrigues da Silva; Francisco de Assis Alves Mourão Filho (Brazilian Journal of Botany, 2025)

Oral supplementation of probiotic blends for low and high birth weight piglets - Amanda Rodrigues Fernandes; Dayanne Kelly Oliveira Pires; Soraia Viana Ferreira; Guilherme de Moraes Chaves; Idael Matheus Góes Lopes; Marcelo Dourado de Lima; Luisa Lopes da Rocha dos Santos; Dalton de Oliveira Fontes (Tropical Animal Health and Production, 2025)

Efficacy of a formulation of chlorfenvinphos and dichlorvos on Rhipicephalus microplus in vivo test in Bahia, Brazil - Aline Kelly Araújo Costa Velame Ferreira; Wagner Carvalho e Silva Neto; Igor de Castro Oliveira; Maria Clara Bastos Rodrigues; Ângela Cristina de Oliveira Lima; Tiago Velame Ferreira; Carolina Carneiro de Matos; Ana Karina da Silva Cavalcante; Lorendane Millena de Carvalho; Wendell Marcelo de Souza Perinotto (Tropical Animal Health and Production, 2025)

Woody vegetation on tropical inselbergs: floristic-structural characterization and aboveground carbon storage - Dayvid Rodrigues Couto; Talitha Mayumi Francisco; Luiza F. A. De Paula; Ranieri Ribeiro Paula; Marcelo Trindade Nascimento (Journal of Mountain Science, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Gibberellin biosynthesis inhibitors distinctly affect sunflower morphometric and growth dynamics - Carolina Ruv Lemes Gonçalves Mendes; Lusiane de Sousa Ferreira; Melina Rodrigues Alves Carnietto; Laura Costa Oliveira Almeida; Gustavo Ferreira da Silva; Hariane Luiz Santos; Carmen Sílvia Fernandes Boaro; Marcelo de Almeida Silva (South African Journal of Botany, 2025)

How the commercialization of live bait impacts the profitability of artisanal fishing in a Brazilian estuary: A proximity economy approach - Suellen Mariano da Silva; Alberto Ferreira de Amorim; Leonardo Castilho-Barros; Newton José Rodrigues da Silva; Marcelo Barbosa Henriques (Regional Studies in Marine Science, 2025)

A neural network approach employed to classify soybean plants using multi-sensor images - Flávia Luize Pereira de Souza; Luciano Shozo Shiratsuchi; Maurício Acconcia Dias; Marcelo Rodrigues Barbosa Júnior; Tri Deri Setiyono; Sérgio Campos; Haiying Tao (Precision Agriculture, 2025)

Are flash droughts intensifying in Brazil? - Javier Tomasella; Marcelo Zeri; Ana Paula Martins do Amaral Cunha; Roger Rodrigues Torres; Nancy Laura Rios Gamarra; Lidiane C. O. Costa (Climate Dynamics, 2025)

Effects of deforestation on multitaxa community similarity in the Brazilian Atlantic Forest - Daniel Maurenza; Renato Crouzeilles; Jayme Augusto Prevedello; Mauricio Almeida‐Gomes; Marina Schmoeler; Renata Pardini; Cristina Banks‐Leite; Marcus Vinicius Vieira; Jean Paul Metzger; Carlos Roberto Fonseca; Marina Zanin; Alex Fernando Mendes; et al. (Conservation Biology, 2025)
Habitat loss can lead to biotic homogenization (decrease in β diversity) or differentiation (increase in β diversity) of biological communities. However, it is unclear which of these ecological processes predominates in human‐modified landscapes. We used data on vertebrates, invertebrates, and plants to quantify β diversity based on species occurrence and abundance among communities in 1367 landscapes with varying amounts of habitat ( 60% of forest cover) throughout the Brazilian Atlantic Forest. Decreases in habitat amount below 30% led to increased compositional similarity of vertebrate and invertebrate communities, which may indicate a process of biotic homogenization throughout the Brazilian Atlantic Forest. No pattern was detected in plant communities. We found that habitat loss was associated with a deterministic increase in faunal community similarity, which is consistent with a selected subset of species being capable of thriving in human‐modified landscapes. The lack of pattern found in plants was consistent with known variation between taxa in community responses to habitat amount. Brazilian legislation requiring the preservation of 20% of Atlantic Forest native vegetation may be insufficient to prevent the biotic homogenization of faunal communities. Our results highlight the importance of preserving large amounts of habitat, providing source areas for the recolonization of deforested landscapes, and avoiding large‐scale impacts of homogenization of the Brazilian Atlantic Forest.

Brazilian Green Propolis Extract-Loaded Poly(Ε-Caprolactone) Nanoparticles Coated with Hyaluronic Acid: Antifungal Activity in a Murine Model of Vulvovaginal Candidiasis - Aniely Dos Reis Teixeira; Amanda De Vasconcelos Quaresma; Renata Tupinambá Branquinho; Patrícia Capelari De Oliveira; Jorge Andrés García Suárez; Geraldo Célio Brandão; Ana Paula Moreira Barboza; Marcelo Gonzaga De Freitas Araújo; Juliana Teixeira De Magalhães; Sandra Aparecida Lima De Moura; Gisele Rodrigues Da Silva (AAPS PharmSciTech, 2025)

Detection of Rocahepevirus ratti in Bivalve Mollusks from São Luís Island, Maranhão, Brazil: A Potential Transmission Route of an Emerging Zoonotic Pathogen? - Andreza Soriano Figueiredo; Isabella Rodrigues Negreiros; Aldaleia do Nascimento e Silva; Caroline Roberta Soares Salgado; Natália Lourenço dos Santos; Marcelo Alves Pinto; Alcina Vieira de Carvalho Neta; José Paulo Gagliardi Leite; Carina Pacheco Cantelli (Food and Environmental Virology, 2025)

Correction: Tilapia venturing into high-salinity environments: A cause for concern? - Ana Clara Sampaio Franco; Valter M. Azevedo-Santos; Marluce Aparecida Mattos de Paula Nogueira; Tommaso Giarrizzo; Rachel Ann Hauser-Davis; Erick Cristofore Guimarães; Roger Henrique Dalcin; Marcelo Soeth; Matheus Oliveira Freitas; Áthila A. Bertoncini; Vinícius Abilhoa; Almir Manoel Cunico; et al. (Aquatic Ecology, 2025)

First report of Brassica napus RNA virus 1 infecting brassicas in Brazil - Agatha Mota Oliveira; Alexandre Levi Rodrigues Chaves; Ricardo Harakava; Pedro L. Ramos-González; Marcelo Eiras (Journal of Plant Pathology, 2025)

A systematic review of the molecular mechanisms related to anthelmintic resistance in Haemonchus contortus: A contemporary narrative - Janaelia Ferreira Vasconcelos Rodrigues; Jomar Patricio Monteiro; Thayany Magalhães Almeida; Marcelo Beltrão Molento (Veterinary Parasitology, 2025)

Addressing the urgent climate and biodiversity crisis through strategic ecosystem restoration in Brazil - Luisa Fernanda Liévano-Latorre; Juliana M. de Almeida-Rocha; Alberto Akama; Hernani Alves Almeida; Ricardo Teixeira Gregório Andrade; Marcelo Rodrigues dos Anjos; Yasmine Antonini; Thaise de Oliveira Bahia; Flavia Rodrigues Barbosa; Reinaldo Imbrozio Barbosa; Claudia Franca Barros; Helena Godoy Bergallo; et al. (Biological Conservation, 2025)

Different approaches to sugarcane vinasse use and management in Brazil: A technical, economic, and environmental analysis - Ana Carolina Medina Jimenez; Igor Lucas Rodrigues Dias; Terezinha de Fatima Cardoso; João Luíz Nunes Carvalho; Tassia Lopes Junqueira; Nathalia Meschiatti Magioli; Mateus Ferreira Chagas; Adriano Pinto Mariano; Marcelo Pereira da Cunha; Antonio Bonomi (Biomass and Bioenergy, 2025)

Laboratory and physiological aspects of substitute metazoan models for in vivo pharmacotoxicological analysis - Paulo Michel Pinheiro Ferreira; Carla Lorena Silva Ramos; José Ivo Araújo Beserra Filho; Micaely Lorrana Pereira Conceição; Mateus Lima Almeida; Débora Caroline do Nascimento Rodrigues; Jhonatas Cley Santos Porto; João Marcelo de Castro e Sousa; Ana Paula Peron (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Molecular Tracking of Emerging Fusarium Species in Keratitis: F. veterinarium, F. contaminatum, and F. curvatum - Ruan Campos Monteiro; Maria Cecília Zorat Yu; Somayeh Dolatabadi; Ferry Hagen; Marcelo Sandoval-Denis; Elaine Cristina Francisco; Denise de Freitas; Zoilo Pires De Camargo; Ana Luisa Höfling-Lima; Anderson Messias Rodrigues (Mycopathologia, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Shark-on-a-dish: Elasmobranch cell cultures as a promising tool for the conservation of threatened species - Maria Carolina Peixoto-Rodrigues; Daniel Adesse; Marcelo Vianna; Rachel Ann Hauser-Davis (Marine Pollution Bulletin, 2025)

Flotation of carbonates from dolomitic iron ore: synthesis, characterization and application of a novel N,N-bis(2-hydroxyethyl)oleamide collector - Guilherme Otávio dos Santos; Aline Alves da Silva; Lucas José da Silva Nascimento; Maria Fernanda Reis Souza; Rafaela de Oliveira Teixeira Menezes; Francielle Christine Cunha Andrade; Marcelo Siqueira Valle; Antônio Eduardo Clark Peres; Gilberto Rodrigues da Silva (Minerals Engineering, 2025)

Modeling the protective effect of water activity of a meat emulsion matrix model on Listeria monocytogenes inactivation by high pressure processing - Natália Brunna Moresco Ferreira; Maria Isabel Rodrigues; Marcelo Cristianini (Food Control, 2025)

Addressing climate change in Berlin's local land-use plans through strategic environmental assessment and knowledge brokering - Tiago Rodrigues; Gesa Geißler; Marcelo Montaño (Environmental Impact Assessment Review, 2025)

Pollonein-LAAO unveiling anti-angiogenic effects through oxidative stress: Insights from mimetic tumor angiogenesis environment in a 3D co-culture model - Lorena Polloni; Tássia Rafaella Costa; Lorena Pinheiro Morais; Bruna Cristina Borges; Samuel Cota Teixeira; Thales Alves de Melo Fernandes; Lucas Ian Veloso Correia; Luciana Machado Bastos; Andreimar Martins Soares; Marcelo José Barbosa Silva; Eloisa Amália Vieira Ferro; Daiana Silva Lopes; et al. (Chemico-Biological Interactions, 2025)

The small-scale fisheries sector in a developing country: assessing SWOT and recommendations for sustainability in Namibe (Angola) - Pinto Leonidio Hanamulamba; Tierry Val de Medeiros; Igor Hister Lourenço; Marcelo Rodrigues dos Anjos; Luis Felipe de Almeida Duarte (Fisheries Science, 2025)

Integrative species delimitation and biogeography of the Rhinella margaritifera species group (Amphibia, Anura, Bufonidae) suggest an intense diversification throughout Amazonia during the last 10 million years - Antoine Fouquet; Miqueias Ferrão; Miguel T. Rodrigues; Fernanda P. Werneck; Ivan Prates; Leandro J.C.L. Moraes; Tomas Hrbek; Juan C. Chaparro; Albertina P. Lima; Renata Perez; Andre Pansonato; Vinicius T. Carvalho; et al. (Systematics and Biodiversity, 2024)

Phthalate ester and cholesterol profiles of blubber samples of the free-ranging Amazon River dolphin (Cetacea: Iniidae: Inia geoffrensis) in the Brazilian Amazon - Lucas Fazardo de Lima; Isadora Nicole Lara Piccinin; Giulia Galani Martha; Susane Lopes; Thaís Carneiro Santos Rodrigues; Miriam Marmontel; Cristiane Kiyomi Miyaji Kolesnikovas; Marcelo Maraschin (Marine Pollution Bulletin, 2024)

Florida mangrove dieback on a decadal and centennial timescales - Marcelo C.L. Cohen; Diana Paola Cardenas Ruiz; Erika Rodrigues; Qiang Yao; Adriana V. de Souza; Kam-biu Liu; Luiz C.R. Pessenda; Alejandro Antonio Aragón-Moreno; Junghyung Ryu; Sérgio Nunes (Science of The Total Environment, 2024)

Blood mercury concentrations in preschool children and potential risk factors in São Paulo, Brazil - Fernanda Junqueira Salles; Elizeu Chiodi Pereira; Allan Santos de Oliveira; Eric A.C. da Costa; Thiago Nogueira; Marcelo de Oliveira Lima; João Paulo Góes Pereira; Thais Karolina Lisboa Queiroz; Brenda Rodrigues Chagas; Iracina Maura de Jesus; Agnes Soares da Silva; Maria Regina Alves Cardoso; et al. (Environmental Pollution, 2024)

Structured lipids from fish viscera and coconut oils improve weight gain and intestinal morphology of piglets at nursery phase - Rennan Rômullo Silva Pinheiro; Pedro Henrique Watanabe; Lina Raquel Santos Araújo; Ingrid Barbosa de Mendonça; João José de Mesquita Sales; Marcelo Emersom Costa Santos; Leonardo Augusto Fonseca Pascoal; Ricardo Romão Guerra; Jonathan Madson dos Santos Almeida; Ednardo Rodrigues Freitas (Tropical Animal Health and Production, 2024)

Alkalizing potentials for recirculating systems with clear water in the Rhamdia quelen juvenile cultivation - Emilene Rodrigues de Souza; Talita Andrade Ferreira; Afonso Pelli; Nathália Fernandino Moreira; Lucas Lima Verardo; Marcelo Mattos Pedreira (Aquaculture International, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Disruption of exploratory behavior and olfactory memory in cockroaches exposed to sublethal doses of the neonicotinoid Thiamethoxam - Letícia Campos Ferreira; Maria Eduarda Rosa; Luis Guilherme Silva Rodrigues; Diego Roberto Colombo Dias; Marcelo de Paiva Guimarães; Chiara Valsecchi; Velci Queiroz de Souza; Renata de Faria Barbosa; Lucia Helena Vinadé; Stephen Hyslop; João Batista Teixeira da Rocha; Cháriston André Dal Belo (Pesticide Biochemistry and Physiology, 2024)

Multichannel Analysis of Surface Waves based on Common Virtual Source Gathers of Seismic Ambient Noise Cross-Correlations: A Case Study at an Earth Dam in Brazil - Victor José Cavalcanti Bezerra Guedes; Susanne Tainá Ramalho Maciel; Marcelo Peres Rocha; Welitom Rodrigues Borges; Luciano Soares da Cunha (Journal of Applied Geophysics, 2024)

Supplementation of high doses of vitamin D during the gestational period do not cause reproductive, teratogenic and genotoxic damage in mice - Silvia Cordeiro das Neves; Sarah Alves Auharek; Roberto da Silva Gomes; Marcelo Luiz Brandão Vilela; Valter Aragão do Nascimento; Henrique Rodrigues Scherer Coelho; Karuppusamy Arunachalam; Andréia Conceição Milan Brochado Antoniolli-Silva; Rodrigo Juliano Oliveira (Food and Chemical Toxicology, 2024)

Innovative system to maximize methane production from fruit and vegetable waste - Camila Aparecida de Menezes; Daniel Rodrigues dos Santos; Willame de Araújo Cavalcante; Priscilla de Souza Almeida; Thobias Pereira Silva; Francisco das Chagas Gomes da Silva Júnior; Tito Augusto Gehring; Marcelo Zaiat; André Bezerra dos Santos; Renato Carrhá Leitão (Environmental Science and Pollution Research, 2024)

Clomazone exposure-driven photosynthetic responses plasticity of Pontederia crassipes - Bianca Jaqueline Santos Rodrigues; Igor Alexander de Moura Silva; Marcelo dos Santos Silva; Douglas Antonio Posso; Cristina Moll Hüther; Luciano do Amarante; Marcos Antonio Bacarin; Junior Borella (Environmental Science and Pollution Research, 2024)

Hydrocarbon composition of oils spilt on the Brazilian coast in 2019 and 2022 - Antônia M. Corrêa; Felipe F. Campos; Marcus F. Tenório; Alice M.S. Rodrigues; Carlos D. Pérez; Fabiano Thompson; Andressa S. Batista; Pedro V. Gatts; Carlos E. de Rezende; Kátia Z. Leal; Marcelo C. Bernardes (Marine Pollution Bulletin, 2024)

Anthocyanin expressed in leaves boosting chlorophyll-based dye-sensitized solar cells performance - Marcelo Alatzatianou Rodrigues (Next Research, 2024)

Green supply chain management in the Southern Brazilian rice industry: A survey and structural analysis - Miguel Afonso Sellitto; Felipe Fehlberg Herrmann; Marcelo Fernandes Pacheco Dias; Gislene Salim Rodrigues; Maria Angela Butturi (Journal of Cleaner Production, 2024)

Exploiting tropical fruit processing coproducts as circular resources to promote the growth and maintain the culturability and functionality of probiotic lactobacilli - Caroliny Mesquita Araújo; Karoliny Brito Sampaio; Jaielison Yandro Pereira da Silva; Jordana Nunes de Oliveira; Thatyane Mariano Rodrigues de Albuquerque; Maiara da Costa Lima; Marcos dos Santos Lima; Yuri Mangueira do Nascimento; Evandro Ferreira da Silva; Marcelo Sobral da Silva; Josean Fechine Tavares; Evandro Leite de Souza; et al. (Food Microbiology, 2024)

Revealing the Potential Impacts of Nutraceuticals Formulated with Freeze-Dried Jabuticaba Peel and Limosilactobacillus fermentum Strains Candidates for Probiotic Use on Human Intestinal Microbiota - Jaielison Yandro Pereira da Silva; Heloísa Maria Almeida do Nascimento; Thatyane Mariano Rodrigues de Albuquerque; Karoliny Brito Sampaio; Marcos dos Santos Lima; Mariana Monteiro; Iris Batista Leite; Evandro Ferreira da Silva; Yuri Mangueira do Nascimento; Marcelo Sobral da Silva; Josean Fechine Tavares; José Luiz de Brito Alves; et al. (Probiotics and Antimicrobial Proteins, 2024)

First report of angular leaf spot in Acmella oleracea caused by the foliar nematode Aphelenchoides pseudobesseyi - Marcela de Freitas Silva; Felipe Castro Faccioli; Amanda Pereira Honório; Andressa Rodrigues Fonseca; Alessandra de Jesus Boari; Cláudio Marcelo Gonçalves de Oliveira; Dalila Sêni Buonicontro (Journal of Plant Diseases and Protection, 2024)

Assessment of water quality and identification of priority areas for intervention in Guanabara Bay basin, Rio de Janeiro, Brazil, using nonparametric and multivariate statistical methods - Dayane Andrade da Silva; Micael de Souza Fraga; Gustavo Bastos Lyra; Roberto Avelino Cecílio; Carlos Rodrigues Pereira; Gisleine Cunha-Zeri; Marcelo Zeri; Marcel Carvalho Abreu (Environmental Monitoring and Assessment, 2024)

Effect of duration of estradiol exposure on embryo survival and endometrial gene expression in anestrous embryo recipient mares - Elisa Sant'Anna Monteiro da Silva; Pedro Sanches Oquendo Júnior; Fabiana Maddalena de Gaspari Oquendo; Tom A.E. Stout; Marta de Ruijter-Villani; Tamiris Sabrina Rodrigues; Marcelo Emílio Beletti; Juan Cuervo-Arango (Theriogenology, 2024)

Organ-specific proteomes of Selaginella convoluta provide insights into its desiccation tolerance mechanisms - Fernanda Priscila Santos Reginaldo; Luiz Fernando Rodrigues de Souza; Daisy Sotero Chacon; Marlon Dias Mariano Santos; Taffarel Melo Torres; Ivanice Bezerra da Silva; Alan de Araújo Roque; Carlos André O. Ricart; Mariana S. Castro; Paulo Costa Carvalho; Wagner Fontes; Marcelo Valle de Sousa; et al. (Plant Biosystems, 2024)

Timed-artificial insemination protocols for Bos indicus beef heifers: Evaluation of protocol length and variations in prostaglandin F2α treatments - Rodrigo L.O.R. Alves; Lucas O.e Silva; Mateus A.da Silva; Carlos E.C. Consentini; José R.S. Gonçalves; Leonardo de F. e Melo; Marcelo B. Rodrigues; Roberto Sartori (Theriogenology, 2024)

Influence of the leaf-cutting ant Atta sexdens Linnaeus (1758) on the taxonomic and functional diversity of woody plants in Atlantic Forest fragments - Jéssica Magon Garcia; Larissa Cerqueira Dias Rodrigues; Lya Carolina da Silva Mariano Pereira; Heraldo Luís Vasconcelos; José Marcelo Domingues Torezan (Plant Ecology, 2024)

Functional trait patterns: investigating variation-covariation relationships and the importance of intraspecific variability along distinct vegetation types - Gustavo Viana de Freitas; José Luiz Alves Silva; Douglas Rodrigues Ribeiro; Priscila Simioni; Glaziele Campbell; Saulo Pireda; Alexandre F. Souza; Marcelo Trindade Nascimento; Maura Da Cunha; Angela Pierre Vitória (Community Ecology, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Precision agriculture in the United States: A comprehensive meta-review inspiring further research, innovation, and adoption - Marcelo Rodrigues Barbosa Júnior; Bruno Rafael de Almeida Moreira; Vinicius dos Santos Carreira; Armando Lopes de Brito Filho; Carolina Trentin; Flávia Luize Pereira de Souza; Danilo Tedesco; Tri Setiyono; Joao Paulo Flores; Yiannis Ampatzidis; Rouverson Pereira da Silva; Luciano Shozo Shiratsuchi (Computers and Electronics in Agriculture, 2024)

Stemphylium lycopersici immobilized in mesoporous of type MCM 48 as biocatalyst for ω-transamination reactions - Maria Sandra Ramos Queiroz; Glaciela Cristina Rodrigues da Silva; Nádia Ligianara D. Nyari; Rodrigo O.M.A. de Souza; Rogério Marcos Dallago; Denise Oliveira Guimarães; Marcelo Luis Mignoni; Ivana Correa Ramos Leal (Sustainable Chemistry and Pharmacy, 2024)

Influence of roasting levels on chemical composition and sensory quality of Arabica and Robusta coffee: A comparative study - Valdeir Viana Freitas; Larissa Lorrane Rodrigues Borges; Gabriel Abranches Dias Castro; Lucas Filipe Almeida; Ludmylla Tamara Crepalde; Hélia dos Barros Kobi; Márcia Cristina Teixeira Ribeiro Vidigal; Marcelo Henrique dos Santos; Sergio Antonio Fernandes; Gabriela Piccolo Maitan-Alfenas; Paulo César Stringheta (Food Bioscience, 2024)

A long-term study on free-ranging jaguar-tick interactions, featuring a novel report of Amblyomma incisum adult infestation - Vinícius Baggio-Souza; Joares Adenilson May-Junior; Renata Fagundes-Moreira; Adeyldes Oliveira Reis; Bruno Albuquerque de Almeida; Carlos Eduardo Fragoso; Lilian Elaine Rampim; Leonardo Rodrigues Sartorelo; Mario Bührke Haberfeld; Thiago Fernandes Martins; Marcelo Bahia Labruna; João Fabio Soares (Veterinary Research Communications, 2024)

AI-Driven Prediction of Sugarcane Quality Attributes Using Satellite Imagery - Tatiana Fernanda Canata; Marcelo Rodrigues Barbosa Júnior; Romário Porto de Oliveira; Carlos Eduardo Angeli Furlani; Rouverson Pereira da Silva (Sugar Tech, 2024)

Do hurricanes or freezing events regulate the sustainability of subtropical mangroves on the Gulf of Mexico coast? - Marcelo C. L. Cohen; Qiang Yao; Adriana V. de Souza; Kam-biu Liu; Sergio Nunes; Erika Rodrigues; Luiz C. R. Pessenda; Nicholas Culligan (Regional Environmental Change, 2024)

Ultraviolet light C prototype device against Sporothrix brasiliensis as a potential physical method for surface disinfection - Anderson Luis Terçola; Vanice Rodrigues Poester; Lívia Silveira Munhoz; Daniela Fernandes Ramos; Anderson Favero Porte; Marcelo Moraes Galarça; Melissa Orzechowski Xavier (Brazilian Journal of Microbiology, 2024)

Exposure of small ruminants and humans to Coxiella burnetii in the semi-arid region of Northeastern Brazil - Eline Almeida Rodrigues de Souza; Ila Ferreira Farias; Tainã Ramos Pesqueira; Maria Carolina de Azevedo Serpa; Thaís Souza Cunha; Elenice Andrade Moraes; Paulo Eduardo Brandão; Marcelo Bahia Labruna; Mauricio Claudio Horta (Brazilian Journal of Microbiology, 2024)

Survival analysis as a tool for breeding management of Nile tilapia in an intensive system - Talita Andrade Ferreira; Emilene Rodrigues de Souza; Clarisse Ribeiro Matos; Lucas Lima Verardo; Marcelo Mattos Pedreira (Aquaculture International, 2024)

A densely sampled molecular phylogeny of Tachigali (Leguminosae), an evolutionarily successful lineage of neotropical ant-housing canopy trees - Isau Huamantupa-Chuquimaco; Vitor Hugo Maia; Haroldo Cavalcante de Lima; Maristerra Rodrigues Lemes; Cristiane Snak; Bernarda Gregório; Sérgio Ricardo S. Cardoso; Luciano Paganucci de Queiroz; Charles E. Zartman; Gwilym P. Lewis; Euan K. James; Kyle G. Dexter; et al. (Brazilian Journal of Botany, 2024)

Biosurfactants production by marine yeasts isolated from zoanthids and characterization of an emulsifier produced by Yarrowia lipolytica LMS 24B - Vitória Petra de Oliveira Barros; Júlio Ricardo Macedo Silva; Vânia Maria Maciel Melo; Pâmela Santos Terceiro; Italo Nunes de Oliveira; Johnnatan Duarte de Freitas; Orlando Francisco da Silva Moura; João Xavier de Araújo-Júnior; Erica Erlanny da Silva Rodrigues; Marcelo Maraschin; Fabiano Lopes Thompson; Melissa Fontes Landell (Chemosphere, 2024)

PLA2-MjTX-II from Bothrops moojeni snake venom exhibits antimetastatic and antiangiogenic effects on human lung cancer cells - Luísa Carregosa Santos; Vinícius Queiroz Oliveira; Samuel Cota Teixeira; Thiago Macedo Lopes Correia; Leonardo Oliveira Silva Bastos Andrade; Lorena Polloni; Lucas Miranda Marques; Patrícia Bianca Clissa; Cristiani Baldo; Eloisa Amália Vieira Ferro; Amélia Cristina Mendes de Magalhães Gusmão; Marcelo José Barbosa Silva; et al. (Toxicon, 2024)

Hepatogenic photosensitization in lambs supplemented with different levels of extruded urea in Brachiaria spp. pastures in the Brazilian Cerrado: Case report - Francisca Fernanda da Silva Roberto; Gelson dos Santos Difante; Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Jéssica Gomes Rodrigues; Marislayne de Gusmão Pereira; Marcelo Augusto de Araújo; Diego Gomes Freire Guidolin; Hitalo Rodrigues da Silva; Neila Lidiany Ribeiro (Toxicon, 2024)

Improving coffee capsules recyclability - A combined assessment of circularity and environmental performance of a novel design - Sara M. Pinto; Joana R. Gouveia; Marcelo Sousa; Bruno Rodrigues; José Oliveira; Carlos Pinto; A.J. Baptista (Sustainable Production and Consumption, 2024)

Two decades of clear-cutting threats in the Brazilian Amazonian protected areas around the Jirau, Santo Antônio, and Belo Monte large dams - Silvia Sayuri Mandai; Evandro Albiach Branco; Evandro Mateus Moretto; Jocilene Dantas Barros; Guilherme Prado Alves; Renata Utsunomiya; Gustavo Felipe Balué Arcoverde; Cyro Assahira; Caroline C. Arantes; Guilherme de Sousa Lobo; Miquéias Freitas Calvi; Carolina Rodrigues da Costa Doria; et al. (Journal of Environmental Management, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Heavy metals bioaccumulation in free-ranging South American rattlesnakes (Crotalus durissus) in Southeastern Brazil - Frank August de Oliveira Toledo; Daniel Oliveira dos Santos; Izabela Magalhães Arthuso Vasconcelos; Ayisa Rodrigues Oliveira; Juliana Araújo Gomes Cabral; Rômulo Antônio Righi de Toledo; Pedro Hugo Henriques Cunha; Diego Felipe Alves Batista; Fabiola de Oliveira Paes Leme; Marcelo Pires Nogueira de Carvalho; Tatiane Alves da Paixão; Mariana Machado-Neves; et al. (Environmental Science and Pollution Research, 2024)

Coffee: A comprehensive overview of origin, market, and the quality process - Valdeir Viana Freitas; Larissa Lorrane Rodrigues Borges; Márcia Cristina Teixeira Ribeiro Vidigal; Marcelo Henrique dos Santos; Paulo Cesar Stringheta (Trends in Food Science & Technology, 2024)

Challenges and Operational Strategies to Achieve Partial Nitrification in Biological Wastewater Treatment: A Review - Alice Chiapetti Bolsan; Camila Ester Hollas; Heloisa Campeão Rodrigues; Jadiane Paola Cavaler; Ana Claudia Lazaroto; Naiana Cristine Gabiatti; Marcelo Bortoli; Gracielle Johann; Fabiane Goldschimidt Antes; Airton Kunz; Thiago Edwiges; Marina Celant De Prá (International Journal of Environmental Research, 2024)

CO2 fluxes under different oceanic and atmospheric conditions in the Southwest Atlantic Ocean - Celina Cândida Ferreira Rodrigues; Marcelo Freitas Santini; Nathaniel Alan Brunsell; Luciano Ponzi Pezzi (Journal of Marine Systems, 2024)

Modeling sugarcane development and growth within ECOSMOS biophysical model - Michel Anderson Almeida Colmanetti; Santiago Vianna Cuadra; Rubens Augusto Camargo Lamparelli; Osvaldo Machado Rodrigues Cabral; Daniel de Castro Victoria; José Eduardo Boffino de Almeida Monteiro; Helber Custódio de Freitas; Marcelo Valadares Galdos; Anderson Carlos Marafon; Aderson Soares de Andrade Junior; Sergio Delmar dos Anjos e Silva; Vinicius Bof Buffon; et al. (European Journal of Agronomy, 2024)

Total ozone content, total cloud cover, and aerosol optical depth in CMIP6: simulations performance and projected changes - Ana Letícia Campos Yamamoto; Marcelo de Paula Corrêa; Roger Rodrigues Torres; Fabrina Bolzan Martins; Sophie Godin-Beekmann (Theoretical and Applied Climatology, 2024)

Not all size measures are created equal: different body size proxies are not equivalent fitness predictors in the bat Carollia perspicillata - Breno Mellado; Lucas de Oliveira Carneiro; Marcelo Rodrigues Nogueira; Leandro Rabello Monteiro (Journal of Mammalian Evolution, 2024)

Spatiotemporal variability in human thermal comfort perception in open-air spaces: application to the state of Minas Gerais, Brazil - Lucas Rodrigues Oliveira; Tadayuki Yanagi Junior; Gabriel Araújo e Silva Ferraz; Sílvia de Nazaré Monteiro Yanagi; Marcelo Bahuti (International Journal of Biometeorology, 2024)

Nowcast flood predictions in the Amazon watershed based on the remotely sensed rainfall product PDIRnow and artificial neural networks - Herval Alves Ramos Filho; Eduardo Morgan Uliana; Uilson Ricardo Venâncio Aires; Ibraim Fantin da Cruz; Luana Lisboa; Demetrius David da Silva; Marcelo Ribeiro Viola; Victor Braga Rodrigues Duarte (Environmental Monitoring and Assessment, 2024)

Correction: Synergism between molecules derived from Garcinia brasiliensis and antimicrobial drugs on field isolates of Mycoplasma hyopneumoniae - Bruna Araújo Euzébio Alves Jacob Lopes; Leonardo Teófilo Toledo; Jéssica Lobo Albuquerque Caldeira; Fábio Assad Feres Rodrigues; Mariana de Barros; Luiz Fernando Lino de Souza; Natália Fialho Gonzaga; Marcelo Henrique dos Santos; Abelardo Silva-Júnior; Maria Aparecida Scatamburlo Moreira (Brazilian Journal of Microbiology, 2024)

Synergism between molecules derived from Garcinia brasiliensis and antimicrobial drugs on field isolates of Mycoplasma hyopneumoniae - Bruna Araújo Euzébio Alves Jacob Lopes; Leonardo Teófilo Toledo; Jessica Lobo Albuquerque Caldeira; Fábio Assad Feres Rodrigues; Mariana de Barros; Luiz Fernando Lino de Souza; Natália Fialho Gonzaga; Marcelo Henrique dos Santos; Abelardo Silva-Júnior; Maria Aparecida Scatamburlo Moreira (Brazilian Journal of Microbiology, 2024)

Persea quarciticola (Lauraceae), a new species from Espírito Santo, Brazil - Pedro Luís Rodrigues de Moraes; Marcelo Leandro Brotto (Brittonia, 2024)

Advancements in peanut mechanization: Implications for sustainable agriculture - Bruno Rafael de Almeida Moreira; Tulio Mazetti Marra; Eduardo Arouche da Silva; Armando Lopes de Brito Filho; Marcelo Rodrigues Barbosa Júnior; Adão Felipe dos Santos; Rouverson Pereira da Silva; George Vellidis (Agricultural Systems, 2024)

Tilapia venturing into high-salinity environments: A cause for concern? - Ana Clara Sampaio Franco; Valter M. Azevedo-Santos; Marluce Aparecida Mattos de Paula Nogueira; Tommaso Giarrizzo; Rachel Ann Hauser-Davis; Erick Cristofore Guimarães; Roger Henrique Dalcin; Marcelo Soeth; Matheus Oliveira Freitas; Áthila A. Bertoncini; Vinícius Abilhoa; Almir Manoel Cunico; et al. (Aquatic Ecology, 2024)

Effects of Simulated Gastrointestinal Conditions on Combined Potentially Probiotic Limosilactobacillus fermentum 296, Quercetin, and/or Resveratrol as Bioactive Components of Novel Nutraceuticals - Karoliny Brito Sampaio; José Luiz de Brito Alves; Yuri Mangueira do Nascimento; Josean Fechine Tavares; Marcelo Sobral da Silva; Davi dos Santos Nascimento; Noádia Priscila de Araújo Rodrigues; Mariana Costa Monteiro; Estefânia Fernandes Garcia; Evandro Leite de Souza (Probiotics and Antimicrobial Proteins, 2024)

Essential oils of Ocimum gratissimum, Lippia grata and Lippia origanoides are effective in the control of the acanthocephalan Neoechinorhynchus buttnerae in Colossoma macropomum - Maria Inês Braga Oliveira; Franmir Rodrigues Brandão; Marcos Tavares-Dias; Bruna Carlos Nascimento Barbosa; Maria Juliete Souza Rocha; Lorena Vieira Matos; Damy Caroline Melo Souza; Cláudia Majolo; Marcelo Róseo Oliveira; Francisco Célio Maia Chaves; Edsandra Campos Chagas (Aquaculture, 2024)

Body content and mineral requirements of dairy goats in early lactation - Elvanio José Lopes Mozelli Filho; Elon Souza Aniceto; Ismael Nacarati da Silva; Vicente Ribeiro Rocha Júnior; Marcelo Teixeira Rodrigues; Tadeu Silva de Oliveira (Small Ruminant Research, 2024)

Airborne geophysics, petrophysics, geochemistry and geology of Ni-Cu (Co-Au-PGE) footprints to define exploration targets in mafic-ultramafic rocks - Thiago Lima Mendes; Marcelo Henrique Leão-Santos; Luiz Fernando Cursino Tabosa; Welitom Rodrigues Borges; Cleber dos Santos Alves; Marcos Tadeu de Freitas Suita (Journal of South American Earth Sciences, 2024)

Chromatic discrimination in fixed saturation levels from tufted capuchin monkeys with different color vision genotypes - Luiza Karina Gonçalves Meireles; Leticia Miquilini; Felipe André Costa Brito; Anderson Raiol Rodrigues; Leonardo Dutra Henriques; Einat Hauzman; Daniela Maria Oliveira Bonci; Marcelo Fernandes Costa; Olavo de Faria Galvão; Dora Fix Ventura; Paulo Roney Kilpp Goulart; Givago Silva Souza (Journal of Comparative Physiology A, 2024)

Storm tracks and cyclogenesis over the Southern Ocean: An overview with the HadGEM3‐GC3 .1 model - Marcelo Rodrigues de Souza; Everson Dal Piva (International Journal of Climatology, 2023)
Extratropical cyclones play an important role in shaping the weather and climate over vast regions across the globe. To effectively understand and manage the impact of these meteorological events, it is crucial to explore deeper into their structure and behaviour. Here, we have evaluated the characteristics and spatial distribution of extratropical cyclones that had their genesis in the Southern Ocean (SO) in the present climate, based on data from the HadGEM3‐GC3.1‐MM (HG3) global model and the ERA5 reanalysis. Both in winter and summer, cyclone tracks are spatially structured, forming a belt around the entire Antarctic continent, with greater concentration in the SO sector adjacent to the southern Pacific Ocean. The regions of the Somov, Amundsen and Bellingshausen seas exhibited a higher track density of moderate and strong cyclones, indicating a correlation with the strongest baroclinicity in these areas. In both datasets, the maximum occurrence of cyclogenesis was located over the regions of the Somov Sea and the Antarctic Peninsula, making these regions very important in the general configuration of cyclones along the SO. Despite underestimating the total number of cyclones along the SO, the HG3 model showed a good ability to represent the main patterns of cyclonic activity around the Antarctic continent, as well as its average behaviour. Knowing the characteristics and the behaviour of extratropical cyclones in such an important area for global climate is essential for understanding their role in weather and future climate resulting from climate change.

Methodology for the estimation of an oil spill origin: Analysis of the 2019 Brazilian coast oil spill - Ricardo Sbragio; Odilon Rodrigues Filho; Marcelo Ramos Martins (Marine Pollution Bulletin, 2023)

Blue carbon stock heterogeneity in Brazilian mangrove forests: A systematic review - Natalia Beloto; Luiz C. Cotovicz Jr.; José Vítor Machado Rodrigues; Maria Regina Gmach; Martin Zimmer; Véronique Helfer; Marcelo O. Soares; Luis Ernesto Arruda Bezerra (Marine Pollution Bulletin, 2023)

Impacts on South America moisture transport under Amazon deforestation and 2 °C global warming - Murilo Ruv Lemes; Gilvan Sampaio; Luis Garcia-Carreras; Gilberto Fisch; Lincoln Muniz Alves; Richard Bassett; Richard Betts; Jelena Maksic; Marília Harumi Shimizu; Roger Rodrigues Torres; Marcelo Guatura; Luana Santamaria Basso; et al. (Science of The Total Environment, 2023)

Protecting soybean yields from enrofloxacin toxicity: The role of Bradyrhizobium japonicum inoculation - Raizza Zorman Marques; Lorena Passos Rodrigues; Glaciela Kaschuk; Julio Cesar Moreira Brito; Marcelo Pedrosa Gomes (Rhizosphere, 2023)

Unrevealing the in vitro impacts of Cereus jacamaru DC. cladodes flour on potentially probiotic strains, selected bacterial populations, and metabolic activity of human intestinal microbiota - Ana Cristina Silveira Martins; Gracy Kelly Vieira de Vasconcelos Medeiros; Sônia Paula Alexandrino de Oliveira; Thatyane Mariano Rodrigues de Albuquerque; Karoliny Brito Sampaio; Marcos dos Santos Lima; Yuri Mangueira do Nascimento; Evandro Ferreira da Silva; Josean Fechine Tavares; Marcelo Sobral da Silva; Evandro Leite de Souza; Maria Elieidy Gomes de Oliveira (Food Research International, 2023)

A guide for quality control of honey: Application of UV–vis scanning spectrophotometry and NIR spectroscopy for determination of chemical profiles of floral honey produced in southern Brazil - Aline Nunes; Gadiel Zilto Azevedo; Beatriz Rocha dos Santos; Mariane Souza Melo de Liz; Felipe Silveira de Souza Schneider; Eva Regina de Oliveira Rodrigues; Sidnei Moura; Marcelo Maraschin (Food and Humanity, 2023)

Multisite potassium fertilization effects on sugarcane ratoon yield and economic return in South-Central Brazil - Rafael Otto; Lucas Miguel Altarugio; Sarah Mello Leite Moretti; Sarah Tenelli; Johnny Rodrigues Soares; Marcelo Grijalva Carneiro Barros; Davi Coutinho Moura; Estêvão Vicari Mellis (Nutrient Cycling in Agroecosystems, 2023)

Investigation of landslide hazard areas in the municipality of Cunha (Brazil) and climate projections from 2024 to 2040 - Irving Rodrigues de Souza; Débora Luisa Silva Teixeira; Marcelo Barbio Rosa; Luiz Tadeu da Silva; Jean Pierre Henry Balbaud Ometto; Danúbia Caporusso Bargos; Cristina Andrade; Elsa Paula Figueira Ferreira Morgado de Sampaio; Paulo Valladares Soares; Thiago Bazzan (Urban Climate, 2023)

Do coral reefs act as sinks for microplastics? - Marcelo O. Soares; Lucia Rizzo; Antonio Rodrigues Ximenes Neto; Yasmin Barros; José Eduardo Martinelli Filho; Tommaso Giarrizzo; Emanuelle F. Rabelo (Environmental Pollution, 2023)

Unintended consequences of valuing the contributions of non-native species: misguided conservation initiatives in a megadiverse region - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Carlos Bernardo Mascarenhas Alves; Marlene Sofia Arcifa; Valter M. Azevedo-Santos; Marcelo Fulgêncio Guedes Brito; Pâmella Silva de Brito; Paula Maria Gênova de Castro Campanha; Fernando Rogério Carvalho; Gabriel Costa da Costa; Mario Alberto Cozzuol; Almir Manoel Cunico; et al. (Biodiversity and Conservation, 2023)

Population structure and dynamics of Petrolisthes armatus (Gibbes, 1850) (Anomura: Porcellanidae) in an Amazon estuary - Dalila Costa Silva; Ana Carolina Melo Rodrigues-Inoue; Francielly Alcântara de Lima-Pismel; Jussara Moretto Martinelli-Lemos; Marcelo Petracco (Regional Studies in Marine Science, 2023)

Effect of high pressure processing and water activity on pressure resistant spoilage lactic acid bacteria (Latilactobacillus sakei) in a ready-to-eat meat emulsion model - Natália Brunna Moresco Ferreira; Maria Isabel Rodrigues; Marcelo Cristianini (International Journal of Food Microbiology, 2023)

Environmental and agronomic assessment of soil conditioners produced from bauxite residue and oil palm wastes - Robson da Costa Leite; Adriano Reis Lucheta; Roseanne Barata Holanda; Patricia Magalhães Pereira Silva; André Luiz Vilaça do Carmo; Fernando Gama Gomes; Rubson da Costa Leite; Caio Cesar Amorim de Melo; Raphael Vieira da Costa; Marcelo Montini; Antonio Rodrigues Fernandes (Environmental Research, 2023)

Permissible concentration of mancozeb in Brazilian drinking water elicits oxidative stress and bioenergetic impairments in embryonic zebrafish - Luana Paganotto Leandro; Maria Vitória Takemura Mariano; Karen Kich Gomes; Ana Beatriz dos Santos; Jaciana Sousa dos Anjos; Nelson Rodrigues de Carvalho; Mauro Eugênio Medina Nunes; Marcelo Farina; Thais Posser; Jeferson Luis Franco (Environmental Pollution, 2023)

Correction to: Silicon Fertilization in Sugarcane Drought-Contrasting Cultivars Subjected to Water Deficit at the Ripening Phase - Mônica Sartori Camargo; Gustavo Jonas Baltieri; André Rodrigues dos Reis; Hamilton Seron Pereira; Marcelo de Almeida Silva (Journal of Soil Science and Plant Nutrition, 2023)

Silicon Fertilization in Sugarcane Drought-Contrasting Cultivars Subjected to Water Deficit at the Ripening Phase - Mônica Sartori Camargo; Gustavo Jonas Baltieri; André Rodrigues dos Reis; Hamilton Seron Pereira; Marcelo de Almeida Silva (Journal of Soil Science and Plant Nutrition, 2023)

Pleural effusion-related Nocardia otitidiscaviarum, Anaplasma platys and Ehrlichia canis coinfection in a dog - Márcio Garcia Ribeiro; Carolina Polo Camargo da Silva; Larissa Marry Pchevuzinske; Fábio Vinícius Ramos Portilho; Amanda Keller Siqueira; Regina Kiomi Takahira; Natália Rodrigues Paschoal; Adriana Aparecida Lopes de Souza; Carolina Aparecida Rodrigues; Beatriz Oliveira de Almeida; Thaís Spessotto Bello; Marcelo Fagali Árabe Filho; et al. (Brazilian Journal of Microbiology, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Oxidative effects of consuming microplastics in different tissues of white shrimp Litopenaeus vannamei - Andressa Suanes Seta; Larissa Müller; Ronan Tavella; Flávio Manoel Rodrigues da Silva Júnior; Virgínia Pedrosa; Luis Alberto Romano; Wilson Wasielesky; Marcelo Estrella Josende; Juliane Ventura-Lima (Marine Pollution Bulletin, 2023)

Patterns of mistletoe infestation in neotropical urban areas - Marcelo Oliveira Teles de Menezes; Marcelo Freire Moro; Marina Oliveira de Souza; Jorhan Marinho de Almeida; Dávila Vitória de Freitas Braga; Pedro Lucas Rodrigues de Alencar; Francisca Soares de Araújo (Urban Ecosystems, 2023)

Sustainable management of sweet potatoes: A review on practices, strategies, and opportunities in nutrition-sensitive agriculture, energy security, and quality of life - Danilo Tedesco; Bruno Rafael de Almeida Moreira; Marcelo Rodrigues Barbosa Júnior; Murilo Maeda; Rouverson Pereira da Silva (Agricultural Systems, 2023)

Biochemical characterization and assessment of leishmanicidal effects of a new L-amino acid oxidase from Crotalus durissus collilineatus snake venom (CollinLA AO-I) - Vitor de Freitas; Tássia Rafaella Costa; Amanda Rodrigues Nogueira; Lorena Polloni; Thales Alves de Melo Fernandes; Lucas Ian Veloso Correia; Bruna Cristina Borges; Samuel Cota Teixeira; Marcelo José Barbosa Silva; Fernanda Gobbi Amorim; Loïc Quinton; André Lopes Saraiva; et al. (Toxicon, 2023)

Portfolio-based decision model for enhancing the mitigation of multidimensional risks in hydrogen pipeline sections - Ramon Swell Gomes Rodrigues Casado; Marcelo Hazin Alencar; Adiel Teixeira de Almeida (Process Safety and Environmental Protection, 2023)

Detailed characterization of iron-rich tailings after the Fundão dam failure, Brazil, with inclusion of proximal sensors data, as a secure basis for environmental and agricultural restoration - Rafaella T. Silva de Sá; Marcelo Tesser Antunes Prianti; Renata Andrade; Aline Oliveira Silva; Éder Rodrigues Batista; Jessé Valentim dos Santos; Fernanda Magno Silva; Marco Aurélio Carbone Carneiro; Luiz Roberto Guimarães Guilherme; Somsubhra Chakraborty; David C. Weindorf; Nilton Curi; et al. (Environmental Research, 2023)

Use of a Concerning Sewage Sludge in the Manufacture of Organomineral Fertilizers: Agronomical Implications and Sustainable Disposal - Mayra Maniero Rodrigues; Douglas Gomes Viana; Guilherme Lucio Martins; Adijailton José de Souza; Júlio Flávio Osti; Fernando Carvalho Oliveira; Marcelo Corrêa Alves; Aline Renee Coscione; Jussara Borges Regitano (Journal of Soil Science and Plant Nutrition, 2023)

Eco-morphological evolution of the Bolivar Peninsula (Texas, U.S.A.) during the last 2,000 years: A multi-proxy record of coastal environmental changes - Qiang Yao; Kam-biu Liu; Daidu Fan; Marcelo Cancela Lisboa Cohen; Paulo Eduardo De Oliveira; Erika Rodrigues (Quaternary Science Reviews, 2023)

Multiproxy reconstruction of late quaternary upper ocean temperature in the subtropical southwestern Atlantic - Joana F. Cruz; Ioanna Bouloubassi; Arnaud Huguet; Alice M.S. Rodrigues; Thiago P. Santos; Igor M. Venancio; Douglas Lessa; Rodrigo L. Sobrinho; Rodrigo A. Nascimento; Marcelo C. Bernardes (Quaternary Science Reviews, 2023)

Monitoring the impacts of a mega-dam on Amazonian understorey herbs - Marcelo B. Medeiros; Washington L. Oliveira; Flávio R.O. Rodrigues; Renata D. Silva; Íris J.K. Ferreira; Wellyngton E. Ayala; Suelma R. Silva; Rafaela T. Souza; Marcelo F. Simon (Forest Ecology and Management, 2023)

Mechanical wounding impacts the growth versus defense balance in tomato (Solanum lycopersicum) - Ana Flavia Aparecida Cunha; Pedro Henrique Duarte Rodrigues; Ana Clara Anghinoni; Vinicius Juliani de Paiva; Daniel Gonçalves da Silva Pinheiro; Marcelo Lattarulo Campos (Plant Science, 2023)

Yeast-fermented cassava as a protein source in cattle feed: systematic review and meta-analysis - Arlan Araujo Rodrigues; Sara Silva Reis; Dinah Correia da Cunha Castro Costa; Milena Alves dos Santos; Raniere de Sá Paulino; Marcelo de Oliveira Alves Rufino; Severino Gonzaga Neto (Tropical Animal Health and Production, 2023)

Alterations in the root phenylpropanoid pathway and root–shoot vessel system as main determinants of the drought tolerance of a soybean genotype - Flaviane Silva Coutinho; Rosilene Oliveira Mesquita; Juliano Mendonça Rodrigues; Analú Zanotti; Verônica Aparecida Faustino; Edvaldo Barros; Camilo Elber Vital; Maria Goreti de Almeida Oliveira; Renata Maria Strozi Alves Meira; Thomas Christopher Rhys Williams; Elizabeth Pacheco Batista Fontes; Marcelo Ehlers Loureiro; et al. (Physiology and Molecular Biology of Plants, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Nutrient deficiency lowers photochemical and carboxylation efficiency in tobacco - Renan Falcioni; Thaise Moriwaki; Marlon Rodrigues; Karym Mayara de Oliveira; Renato Herrig Furlanetto; Amanda Silveira dos Reis; Glaucio Leboso Alemparte Abrantes dos Santos; Weslei Augusto Mendonça; Luis Guilherme Teixeira Crusiol; João Vitor Ferreira Gonçalves; Marcelo Luiz Chicati; Roney Berti de Oliveira; et al. (Theoretical and Experimental Plant Physiology, 2023)

Four diterpenes identified in silico were isolated from Hyptidinae and demonstrated in vitro activity against Mycobacterium tuberculosis - Andreza Barbosa Silva Cavalcanti; Mayara dos Santos Maia; Pedro Thiago Ramalho de Figueiredo; Renata Priscila Barros de Menezes; Alex France Messias Monteiro; Roseana Araújo Ramos Meireles; Gabriela Cristina Soares Rodrigues; Ana Rita Rodrigues de Almeida Silva; Jociano da Silva Lins; Laísa Vilar Cordeiro; Valnês S. Rodrigues Junior; Ana Paula O. T. Castelo Branco; et al. (Natural Product Research, 2023)

Morbidity survey of the history of snakebites in different communities in the alto Juruá, western Brazilian Amazon - Thienify dos Santos Nascimento Rodrigues; Ageane Mota-da-Silva; Jessica Gomes da Costa; Jeferson de Souza Dutra; Mateus de Oliveira Gomes; Gardênia Lima Gurgel do Amaral; Givanildo Pereira Ortega; Jessyca Lima da Silva; Wuelton Marcelo Monteiro; Paulo Sérgio Bernarde (Toxicon, 2023)

Bacterial identification in cerebrospinal fluid of domestic species with neurologic signs: a retrospective case-series study in 136 animals (2005–2021) - Márcio Garcia Ribeiro; Thiago Tourinho Pereira; Patrik Júnior de Lima Paz; Beatriz Oliveira de Almeida; Carmen S. Araújo Cerviño; Carolina Aparecida Rodrigues; Gabrielly Terra Sartori Santos; Larissa Maria de Souza Freire; Fábio Vinicius Ramos Portilho; Marcelo Fagali Árabe Filho; Natália Rodrigues Paschoal; Thaís Spessotto Bello; et al. (Brazilian Journal of Microbiology, 2023)

Correction to: The Role of Vicariance and Paleoclimatic Shifts in the Diversification of Uranoscodon superciliosus (Squamata, Tropiduridae) of the Amazonian Floodplains - Manuela V. dos Santos; Ana L. C. Prudente; Miguel T. Rodrigues; Marcelo J. Sturaro (Evolutionary Biology, 2023)

High-Throughput Carbon-Capturing Frameworks by Pelleting Hydrochar of Food Waste and its Residual Ash as a Dopant - Bruno Rafael de Almeida Moreira; Armando Lopes de Brito Filho; Marcelo Rodrigues Barbosa Júnior; Rouverson Pereira da Silva (BioEnergy Research, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Efficacy of the essential oils of Aloysia triphylla, Lippia gracilis and Piper aduncum in the control of Piscinoodinium pillulare (Shaperclaus, 1954) in Colossoma macropomum (Cuvier, 1818) - Paula Ribeiro dos Santos; Sanny Maria de Andrade Porto; Franmir Rodrigues Brandão; Damy Caroline de Melo Souza; Maria Juliete Souza Rocha; Fernanda de Alexandre Sebastião; Marcelo Róseo Oliveira; Francisco Célio Maia Chaves; Edsandra Campos Chagas (Aquaculture, 2023)

Marine carbonate mining in the Southwestern Atlantic: current status, potential impacts, and conservation actions - Sandra Vieira Paiva; Pedro Bastos Macedo Carneiro; Tatiane Martins Garcia; Tallita Cruz Lopes Tavares; Lidriana de Souza Pinheiro; Antonio Rodrigues Ximenes Neto; Tarin Cristino Montalverne; Marcelo O. Soares (Marine Policy, 2023)

Brazil fosters fossil fuel exploitation despite climate crises and the environmental vulnerabilities - Paulo Horta; Marina Sissini; Carolina Melissa Mueller; Fernanda M.M. Soares; Paulo Pagliosa; Leonardo Rörig; José Bonomi-Barufi; Flavio Berchez; Leticia Cotrim da Cunha; Rodrigo Kerr; Sergio Rossi; Marcelo O. Soares; et al. (Marine Policy, 2023)

A palynological record of mangrove biogeography, coastal geomorphological change, and prehistoric human activities from Cedar Keys, Florida, U.S.A. - Qiang Yao; Kam-biu Liu; Erika Rodrigues; Daidu Fan; Marcelo Cohen (Science of The Total Environment, 2023)

Biotic turnover and carbon cycle dynamics in the early Danian event (Dan-C2): New insights from Blake Nose, North Atlantic - Andressa Nauter-Alves; Tom Dunkley-Jones; Mauro Daniel Rodrigues Bruno; Marcelo A. De Lira Mota; Mario Cachão; Guilherme Krahl; Gerson Fauth (Global and Planetary Change, 2023)

Spectral method for macro and micronutrient prediction in soybean leaves using interval partial least squares regression - Glaucio Leboso Alemparte Abrantes dos Santos; Amanda Silveira Reis; Marcos Renan Besen; Renato Herrig Furlanetto; Marlon Rodrigues; Luís Guilherme Teixeira Crusiol; Karym Mayara de Oliveira; Renan Falcioni; Roney Berti de Oliveira; Marcelo Augusto Batista; Marcos Rafael Nanni (European Journal of Agronomy, 2023)

Suckling behavior, performance, and Kleiber index in calves of different genetic groups under shaded and unshaded environments - Letícia Scarelli Rodrigues da Cunha; Marcos Paulo Gonçalves de Resende; Hugo Pereira Flores; Rosana Moreira da Silva de Arruda; Micheline Feitosa de Castro; Maria Carla Elias Queiroz; Lidianny dos Santos Amorim; Juliano César Castro Belmonte; Millena Vitória da Silva; Maria Simara Palermo Hernandes; Marcelo Vedovatto; Dalton Mendes de Oliveira (Tropical Animal Health and Production, 2023)

RELATIONSHIP BETWEEN SELENIUM NUTRITIONAL STATUS AND MARKERS OF LOW-GRADE CHRONIC INFLAMMATION IN OBESE WOMEN - Larissa Cristina Fontenelle; Mickael de Paiva Sousa; Loanne Rocha dos Santos; Bruna Emanuele Pereira Cardoso; Thayanne Gabryelle Visgueira de Sousa; Tamires da Cunha Soares; Stéfany Rodrigues de Sousa Melo; Jennifer Beatriz Silva Morais; Thaline Milany da Silva Dias; Francisco Erasmo de Oliveira; Débora Cavalcante Braz; João Marcelo de Castro e Sousa; et al. (Biological Trace Element Research, 2023)

Precipitation extremes over the tropical Americas under RCP4 .5 and RCP8 .5 climate change scenarios: Results from dynamical downscaling simulations - Alexandre Araújo Costa; Sullyandro Oliveira Guimarães; Domingo Cassain Sales; Francisco das Chagas Vasconcelos Junior; Marcos Wender Santiago Marinho; José Marcelo Rodrigues Pereira; Eduardo Sávio Passos Rodrigues Martins; Emerson Mariano da Silva (International Journal of Climatology, 2023)
The Regional Atmospheric Modelling System (RAMS) driven by data from the CMIP5 Earth System Model HadGEM2‐ES was used to simulate daily precipitation over the tropical Americas for both current and future climate, including distinct scenarios (representative concentration pathways 4.5 and 8.5) and different time horizons (short‐term, mid‐term and long‐term changes). The major objective was to evaluate possible future changes in extreme events, with emphasis on the intensity of precipitation events and the duration of wet and dry spells. According to RAMS, longer dry spells are expected over most regions of the tropical Americas in the future, with indications for Northeast Brazil, Caribbean, Northern Amazon, and shorter wet spells over Central America and Amazon. With the exception of the Caribbean, there is a general tendency towards the increased frequency of intense precipitation in the tropical Americas.

Sustainable fashion: challenges and barriers for advancing the circular economy - Simone Sehnem; Leonice Troiani; Ana Cláudia Lara; Marcelo Guerreiro Crizel; Luciano Carvalho; Vinícius Picanço Rodrigues (Environment, Development and Sustainability, 2023)

Continuous removal of pharmaceutical drug chloroquine and Safranin-O dye from water using agar-graphene oxide hydrogel: Selective adsorption in batch and fixed-bed experiments - Caroline Maria Bezerra de Araujo; Gessica Wernke; Marcos Gomes Ghislandi; Alexandre Diório; Marcelo Fernandes Vieira; Rosângela Bergamasco; Maurício Alves da Motta Sobrinho; Alírio Egídio Rodrigues (Environmental Research, 2023)

Vibration control systems in a building prototype: Application of SMA coil springs in diagonal bracing and TMD - Yuri J.O. Moraes; Marcelo C. Rodrigues; Antonio A. Silva; Estephanie N.D. Grassi; Carlos J. Araújo (Engineering Structures, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Flood pulse as a driving force of Pb variation in four fish guilds from Puruzinho Lake (western Amazon) - Sophia Menezes de Azevedo; Luiza Silva do Nascimento; Layra de Oliveira Silva; Marcelo Gomes de Almeida; Lucas Silva Azevedo; Wendel Dias Constantino; Wanderley Rodrigues Bastos; Inácio Abreu Pestana (Environmental Science and Pollution Research, 2022)

Evaluating total mercury and methylmercury biomagnification using stable isotopes of carbon and nitrogen in fish from the Madeira River basin, Brazilian Amazon - Marília Higino Mussy; Ronaldo de Almeida; Dario Pires de Carvalho; Leidiane Caroline Lauthartte; Igor Bruno Barbosa de Holanda; Marcelo Gomes de Almeida; Izidro Ferreira de Sousa-Filho; Carlos Eduardo de Rezende; Olaf Malm; Wanderley Rodrigues Bastos (Environmental Science and Pollution Research, 2022)

Variability of the β-casein gene polymorphism in Curraleiro Pé-Duro cattle: a geographical genetics approach - Marcelo Corrêa da Silva; Ana Beatriz Bezerra Souza; José Bento Sterman Ferraz; Fernando Oliveira Bussiman; Matheus Henrique Dias Rodrigues; Susana Queiroz Santos Mello; Rachel dos Santos Bueno; Minos Esperandio de Carvalho; Raryanne Dias Folhas; Helcileia Dias Santos; Leandro Lopes Nepomuceno; Jorge Luís Ferreira (Tropical Animal Health and Production, 2022)

In silico design and in vitro assessment of anti-Helicobacter pylori compounds as potential small-molecule arginase inhibitors - Ana Thereza Fiori-Duarte; João Paulo de Oliveira Guarnieri; Jessica Rodrigues Pereira de Oliveira Borlot; Marcelo Lancellotti; Ricardo Pereira Rodrigues; Rodrigo Rezende Kitagawa; Daniel Fábio Kawano (Molecular Diversity, 2022)

Oral Medicine Experience and Attitudes Toward Oral Cancer: An Evaluation of Dentists Working in Primary Health Care - Jéssica Rodriguez Strey; Michelle Roxo-Gonçalves; Bianca Dutra Guzenski; Marco Antonio Trevizani Martins; Juliana Romanini; Maria Antonia Zancanaro de Figueiredo; Otávio Pereira D’Ávila; Marcelo Rodrigues Gonçalves; Roberto Nunes Umpierre; Erno Harzheim; Laura de Campos Hildebrand; Vinicius Coelho Carrard (Journal of Cancer Education, 2022)

Bacteriophages in wastewater treatment: can they be an approach to optimize biological treatment processes? - Alice Chiapetti Bolsan; Heloisa Campeão Rodrigues; Hélen Caroline Zonta Abilhôa; Camila Ester Hollas; Bruno Venturin; Naiana Cristine Gabiatti; Marcelo Bortoli; Airton Kunz; Marina Celant De Prá (Environmental Science and Pollution Research, 2022)

The Role of Vicariance and Paleoclimatic Shifts in the Diversification of Uranoscodon superciliosus (Squamata, Tropiduridae) of the Amazonian Floodplains - Manuela V. dos Santos; Ana L. C. Prudente; Miguel T. Rodrigues; Marcelo J. Sturaro (Evolutionary Biology, 2022)

Interaction predictors of self-perception menstrual symptoms and influence of the menstrual cycle on physical performance of physically active women - Gabriela de Carvalho; Marcelo Papoti; Márcia Caroline Diniz Rodrigues; Yan Figueiredo Foresti; Elaine Caldeira de Oliveira Guirro; Rinaldo Roberto de Jesus Guirro (European Journal of Applied Physiology, 2022)

Cardiac response in tambaqui Colossoma macropomum anaesthetised with Piper divaricatum essential oil - Cecília Soares Vilhena; Renan Amaral da Silva; Brenda Maria Pereira Alho da Costa; Marcelo Ferreira Torres; Vanessa Jóia de Mello; Renata Coelho Rodrigues Noronha; Joyce Kelly do Rosário da Silva; Moisés Hamoy; Luis André Luz Barbas; Luís Adriano Santos do Nascimento (Fish Physiology and Biochemistry, 2022)

Water Quality in a Tropical Estuarine Channel: Current Conditions, Trends, and Trophic Status (1990–2016) - Carlos Noriega; Carmen Medeiros; Humberto L. Varona; Leonardo Rodrigues; Moacyr Araujo; Sury Monteiro; Andrea Xavier da Silva; Newton Antas Pereira; Eduardo Elvino Sales de Lima; Deive S. Teixeira da Silva; Sonali de Campos Pereira; Julia Araujo; et al. (Water, Air, & Soil Pollution, 2022)

Tp0684, Tp0750, and Tp0792 Recombinant Proteins as Antigens for the Serodiagnosis of Syphilis - Júlio Henrique Ferreira de Sá Queiroz; Marcelo dos Santos Barbosa; Lais Gonçalves Ortolani Miranda; Natasha Rodrigues de Oliveira; Odir Antônio Dellagostin; Silvana Beutinger Marchioro; Simone Simionatto (Indian Journal of Microbiology, 2022)

Genetic gains in Passiflora for resistance to cowpea aphid-borne mosaic virus using recurrent selection - Débora Souza Mendes; Alexandre Pio Viana; Eileen Azevedo Santos; Natan Ramos Cavalcante; Cleidiane Alves Rodrigues; Joameson Antunes Lima; Ravena Ferreira Vidal; Fernando Henrique de Barros Walter; Luan Baritiello da Silva Bezerra; Marcelo Eiras; Huarrisson Azevedo Santos (Euphytica, 2022)

Are the current commercially available oximes capable of reactivating acetylcholinesterase inhibited by the nerve agents of the A-series? - Marcelo C. Santos; Fernanda D. Botelho; Arlan S. Gonçalves; Daniel A. S. Kitagawa; Caio V. N. Borges; Taynara Carvalho-Silva; Leandro B. Bernardo; Cíntia N. Ferreira; Rafael B. Rodrigues; Denise C. Ferreira Neto; Eugenie Nepovimova; Kamil Kuča; et al. (Archives of Toxicology, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Are liana communities in linear canopy openings subject to edge effects? - Beatriz Castro Miranda; Jerônimo Boelsums Barreto Sansevero; Thiago de Azevedo Amorim; Pablo José Francisco Pena Rodrigues; Marcelo Trindade Nascimento; João Marcelo Alvarenga Braga (Plant Ecology, 2022)

Numerical simulation of atmospheric transport of Phakopsora pachyrhizi urediniospores in South America using the state of Paraná-Brazil as a model - Eduardo Oliveira Belinelli; Lucas Henrique Fantin; Marcelo Giovanetti Canteri; Karla Braga; Eliandro Rodrigues Cirilo; Neyva Maria Lopes Romeiro; Paulo Laerte Natti (European Journal of Plant Pathology, 2022)

Morphophysiological Changes in Genipa americana Seedlings in Response to Root Deformation and Substrate Attributes - Catriane Sousa-Santos; Amanda Freitas Cerqueira; Ândrea Carla Dalmolin; Álvaro Alves de Almeida; Martielly Santana dos Santos; Natanielly Rodrigues Avelino; Roberta Barreto dos Santos; José Olímpio de Souza Júnior; Marcelo Schramm Mielke (Journal of Soil Science and Plant Nutrition, 2022)

Genotoxicity assessment in two Amazonian estuaries using the Plagioscion squamosissimus as a biomonitor - Claudia Antonia Campos Rodrigues de Oliveira; Paulo Sérgio dos Santos Souto; Dulcidéia da Conceição Palheta; Marcelo de Oliveira Bahia; Lorena da AraújoCunha; Maria de Lourdes Souza Santos; Tatiane do Nascimento Medeiros Rodrigues; Bianca Bentes (Environmental Science and Pollution Research, 2022)

Molecular and physiological aspects of plant responses to aluminum: what do we know about Cerrado plants? - Laísa Maria Resende de Castro; Christina Cleo Vinson; Sheila Maysa Cunha da Gordo; Thomas Christopher Rhys Williams; Natália Faustino Cury; Marcelo Claro de Souza; Luiz Alfredo Rodrigues Pereira (Brazilian Journal of Botany, 2022)

Aurora kinase genetic polymorphisms: an association study in Down syndrome and spontaneous abortion - Carolina Monteiro Leite de Castro; Carolina Oliveto Bastos Pereira; Joissy Aprigio; Marcelo A. Costa Lima; Márcia G. Ribeiro; Márcia Rodrigues Amorim (Human Cell, 2022)

Palatability and nycterohemeral patterns of ingestive behavior of sheep fed different roughage sources - Thamires Damascena Quirino Siqueira; João Paulo Ismério dos Santos Monnerat; Juana Catarina Cariri Chagas; Maria Gabriela da Conceição; Michelle Christina Bernardo de Siqueira; Lucas Rodrigues de Farias; Juliana Paula Felipe de Oliveira; Marcelo de Andrade Ferreira (Tropical Animal Health and Production, 2022)

Genomic, biochemical, and phylogenetic evaluation of bacteria isolated from deep-sea sediment harboring methane hydrates - Audrey Menegaz Proenca; Maiara Monteiro Oliveira; Paula Fernanda Ribas Neves; Adriana Giongo; Rafael Rodrigues de Oliveira; Carolina Telles Ott; Letícia Marconatto; Halesio Milton Correa de Barros Neto; João Marcelo Medina Ketzer; Renata Medina-Silva (Archives of Microbiology, 2022)

Drivers of fish trophic guild composition in lakes of the Upper Paraná River floodplain - Taise Miranda Lopes; Carolina Mendes Muniz; Marcelo Henrique Schmitz; Rosa Maria Dias; Amanda Cantarute Rodrigues; Matheus Gimenez Buzo; Edivando Vitor do Couto; Angelo Antonio Agostinho (Aquatic Sciences, 2022)

NeoBat Interactions: A data set of bat–plant interactions in the Neotropics - Guillermo L. Florez‐Montero; Renata L. Muylaert; Marcelo R. Nogueira; Cullen Geiselman; Sharlene E. Santana; Richard D. Stevens; Marco Tschapka; Francisco A. Rodrigues; Marco A. R. Mello (Ecology, 2022)
Data papers and open databases have revolutionized contemporary science, as they provide the long‐needed incentive to collaborate in large international teams and make natural history information widely available. Nevertheless, most data papers have focused on species occurrence or abundance, whereas interactions have received much less attention. To help fill this gap, we have compiled a georeferenced data set of interactions between 93 bat species of the family Phyllostomidae (Chiroptera) and 501 plant species of 68 families. Data came from 169 studies published between 1957 and 2007 covering the entire Neotropical Region, with most records from Brazil (34.5% of all study sites), Costa Rica (16%), and Mexico (14%). Our data set includes 2571 records of frugivory (75.1% of all records) and nectarivory (24.9%). The best represented bat genera are Artibeus (28% of all records), Carollia (24%), Sturnira (10.1%), and Glossophaga (8.8%). Carollia perspicillata (187), Artibeus lituratus (125), Artibeus jamaicensis (94), Glossophaga soricina (86), and Artibeus planirostris (74) were the bat species with the broadest diets recorded based on the number of plant species. Among the plants, the best represented families were Moraceae (17%), Piperaceae (15.4%), Urticaceae (9.2%), and Solanaceae (9%). Plants of the genera Cecropia (46), Ficus (42), Piper (40), Solanum (31), and Vismia (27) exhibited the largest number of interactions. These data are stored as arrays (records, sites, and studies) organized by logical keys and rich metadata, which helped to compile the information on different ecological and geographic scales, according to how they should be used. Our data set on bat–plant interactions is by far the most extensive, both in geographic and taxonomic terms, and includes abiotic information of study sites, as well as ecological information of plants and bats. It has already facilitated several studies and we hope it will stimulate novel analyses and syntheses, in addition to pointing out important gaps in knowledge. Data are provided under the Creative Commons Attribution 4.0 International License. Please cite this paper when the data are used in any kind of publication related to research, outreach, and teaching activities.

Advances in Brazil Nut Tree Ecophysiology: Linking Abiotic Factors to Tree Growth and Fruit Production - Karen Cristina Pires da Costa; José Francisco de Carvalho Gonçalves; Alexandre Leão Gonçalves; Adamir da Rocha Nina Junior; Roberto Kirmayr Jaquetti; Vinícius Fernandes de Souza; Josiane Celerino de Carvalho; Andreia Varmes Fernandes; Joelma Keith Rodrigues; Gleisson de Oliveira Nascimento; Lúcia Helena de O. Wadt; Karen A. Kainer; et al. (Current Forestry Reports, 2022)

Impact of donor nutritional balance on the growth and development of mesenchymal stem cells from caprine umbilical cord Wharton´s jelly - Juliana Paula Martins Alves; Rafael Rossetto; César Carneiro Linhares Fernandes; Assis Rubens Montenegro; Iolly Tábata Oliveira Marques; Camila Muniz Cavalcanti; Alessandra Façanha Bezerra; Ana Paula Ribeiro Rodrigues; Marcelo Bertolini; Davide Rondina (Veterinary Research Communications, 2022)

Leaf habits and their relationship with leaf and wood traits in tropical dry forests - Douglas Rodrigues Ribeiro; José Luiz Alves Silva; Marcelo Trindade do Nascimento; Angela Pierre Vitória (Trees, 2022)

BRAMS model performance for significant event involving Brazilian platform ship - Karine dos Santos Rodrigues; Luiz Felipe Rodrigues do Carmo; Ana Cristina Pinto de Almeida Palmeira; Marcelo Andrioni (Natural Hazards, 2022)

Early development of pearlside Maurolicus stehmanni off south‐eastern Brazil - Marcelo Rodrigues‐Ribeiro; Kazuko Suzuki; Rodrigo Silvestre Martins (Journal of Fish Biology, 2022)
The pearlside Maurolicus stehmanni is one of the most abundant mesopelagic fishes off south‐eastern Brazil and plays a key role in the regional ecosystem. However, its early life history remains poorly understood. This study examined the M . stehmanni early life stages, from eggs to juveniles, including all developmental changes in external morphology. Larvae are simple in morphology and lack specialized larval structures. Notochord flexion begins at ~5.15 mm body length (BL) and larvae ≥5.95 mm BL are flexed. The relative growth of seven measured larval characters (head length, body depth, snout length, eye diameter, pre‐dorsal length, pre‐ventral length and pre‐anal length) have transition points (allometric inflexion points), indicating biphasic growth patterns which are likely related to shifts in habitat use, feeding and behaviour. Larval development is similar to that of other Maurolicus species. The relatively fast development of the fins, photophores, swimbladder and pigmentation suggests a precocious adoption of a micronektonic lifestyle in the mesopelagic environment.

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Phylogenetic relationships, population demography, and species delimitation of the Alouatta belzebul species complex (Atelidae: Alouattinae) - Cintia Povill; Marcelo de Assis Passos Oliveira; Fabiano Rodrigues de Melo; Cibele Rodrigues Bonvicino (Primates, 2022)

Are we getting closer to the role of one-carbon metabolism and methylation in the onset of Down syndrome? - Márcia Rodrigues Amorim; Marcelo Aguiar Costa Lima (Human Cell, 2022)

Comparing soil-to-plant cadmium (Cd) transfer and potential human intake among rice cultivars with different Cd tolerance levels grown in a tropical contaminated soil - Thiago Assis Rodrigues Nogueira; Takashi Muraoka; Laís Karina Silveira; Jamile Santos da Silva; Cassio Hamilton Abreu-Junior; José Lavres; Adriana Pinheiro Martinelli; Marcelo Carvalho Minhoto Teixeira Filho; Zhenli He; Arun Dilipkumar Jani; Antonio Ganga; Gian Franco Capra (Environmental Monitoring and Assessment, 2022)

Sugarcane Resilience to Recurrent Water Deficit is Dependent on the Systemic Acclimation of Leaf Physiological Traits - Fernando Henrique Silva Garcia; Marcelo Rodrigues; João Paulo Pennacchi; Ane Marcela das Chagas Mendonça; Daynara Aparecida Rodrigues Gonçalves; Nayara Cristina de Melo; João Paulo Rodrigues Alves Delfino Barbosa (Tropical Plant Biology, 2021)

Nest predation by Channel-billed Toucans (Ramphastos vitellinus) on Pale-breasted Thrushes (Turdus leucomelas) in a central Amazonian urban forest fragment - Edson Rodrigues Costa; Leandro Siqueira Fernandes; Aline Souza de Menezes Medeiros; Mario Cohn-Haft; Marcelo Gordo (Ornithology Research, 2021)

Proteome of Erythroxylum pungens (Erythroxylaceae): an endemic species of the semiarid Caatinga - Daisy Sotero Chacon; Ivanice Bezerra da Silva; Taffarel Melo Torres; Gabrielle Macedo Pereira; Letícia Gondim Lambert Moreira; Luiz Fernando Rodrigues de Souza; Fernanda Priscila Santos Reginaldo; Alan de Araújo Roque; José Angelo S. Zuanazzi; Renata Libonati; Julia A. Rodrigues; Filippe L.M Santos; et al. (Plant Biosystems, 2021)

Impact of the antioxidant quercetin on morphological integrity and follicular development in the in vitro culture of Bos indicus female ovarian fragments - Marcela Bortoletto Cerezetti; Suellen Miguez González; Camila Rodrigues Ferraz; Waldiceu Aparecido Verri; Evelyn Andrade Rabelo; Marcelo Marcondes Seneda; Fábio Morotti (In Vitro Cellular & Developmental Biology - Animal, 2021)

Characterisation of turnip mosaic virus isolates reveals high genetic variability and occurrence of pathotype 1 in Brazil - Leilane Karam Rodrigues; Alexandre Levi Rodrigues Chaves; Elliot Watanabe Kitajima; Renata Faier Calegario; Katia Regiane Brunelli; Fabio Nascimento da Silva; Ricardo Harakava; John Anthony Walsh; Marcelo Eiras (European Journal of Plant Pathology, 2021)

Correction to: Exploring the multivariate technique in the discrimination of Coffea arabica L. cultivars regarding the production and quality of grains under the effect of water management - Daniel Soares Ferreira; Guilherme Bravin Canal; Moyses Nascimento; Ana Carolina Campana Nascimento; João Marcos Soares Ferreira; José Francisco Teixeira do Amaral; Lucas Louzada Pereira; Wagner Nunes Rodrigues; Wilian Rodrigues Ribeiro; Dalyse Toledo Castanheira; Marcelo Antônio Tomaz (Euphytica, 2021)

A proposal for an approach to mapping susceptibility to landslides using natural language processing and machine learning - Saulo Guilherme Rodrigues; Maisa Mendonça Silva; Marcelo Hazin Alencar (Landslides, 2021)

Pesticide and trace element bioaccumulation in wild owls in Brazil - Gabriela Elisa Dal Pizzol; Vitória Aquino Rosano; Elinton Rezende; Jonas Claudiomar Kilpp; Marcelo Menezes Ferretto; Enzo Mistura; Arthur Nery da Silva; Charise Dallazem Bertol; Laura Beatriz Rodrigues; Maria Tereza Friedrich; Luciana Grazziotin Rossato-Grando (Environmental Science and Pollution Research, 2021)

Plastic pollution: A focus on freshwater biodiversity - Valter M. Azevedo-Santos; Marcelo F. G. Brito; Pedro S. Manoel; Júlia F. Perroca; Jorge Luiz Rodrigues-Filho; Lucas R. P. Paschoal; Geslaine R. L. Gonçalves; Milena R. Wolf; Martín C. M. Blettler; Marcelo C. Andrade; André B. Nobile; Felipe P. Lima; et al. (Ambio, 2021)

Exploring the multivariate technique in the discrimination of Coffea arabica L. cultivars regarding the production and quality of grains under the effect of water management - Daniel Soares Ferreira; Guilherme Bravin Canal; Moyses Nascimento; Ana Carolina Campana Nascimento; João Marcos Soares Ferreira; José Francisco Teixeira do Amaral; Lucas Louzada Pereira; Wagner Nunes Rodrigues; Wilian Rodrigues Ribeiro; Dalyse Toledo Castanheira; Marcelo Antônio Tomaz (Euphytica, 2021)

Environmental correlates of taxonomic and phylogenetic diversity in the Atlantic Forest - Andrea Paz; Jason L. Brown; Carlos L. O. Cordeiro; Julian Aguirre‐Santoro; Claydson Assis; Renata Cecilia Amaro; Fabio Raposo do Amaral; Thuane Bochorny; Lucas F. Bacci; Mayara K. Caddah; Fernando d’Horta; Miriam Kaehler; et al. (Journal of Biogeography, 2021)
Aim There is little consensus on which environmental variables are best at predicting multiple dimensions of diversity. We ask whether there are common environmental correlates of diversity, despite ecological differences, across nine clades of plants and animals distributed along a single rainforest domain. For that, we compare the environmental correlates of species richness, phylogenetic diversity, and phylogenetic endemism. Location Brazilian Atlantic Forest. Taxon: Five clades of plants (Bromelioideae, Miconieae, Bertolonia , Cambessedesieae, and the Fridericia and allies) and four clades of animals (butterlies in the tribe Ithomiini, frogs in the genera Boana and Proceratophrys , and birds in the subfamily Thraupinae). Methods Using curated occurrence localities and phylogenetic data, we generated maps of (a) species richness, (b) phylogenetic diversity, (c) residuals of phylogenetic diversity regressed on species richness, and (d) phylogenetic endemism for all groups. We also compiled a set of 30 environmental descriptors, including records of current temperature and precipitation, climatic stability over time, and topography. Through a machine learning framework, we explored the environmental correlates of each of these diversity measures for each group. Results The environmental variables used here were strong predictors of diversity for all studied groups. However, models for phylogenetic endemism had lower predictive power. Although patterns of diversity are different among groups, correlates of diversity are consistent across taxa. For both species richness and phylogenetic diversity, current precipitation and precipitation stability over time were consistently ranked among the variables that strongly correlate with diversity patterns. The correlates of phylogenetic endemism were less homogeneous across groups. The results suggest that including climate stability over time is important when predicting diversity measures that reflect historical components. Main conclusions Investigating environmental correlates of diversity for multiple clades and diversity measures in a single geographic area allows for a better understanding of common patterns across taxa. This study shows that environmental conditions, particularly precipitation, are good predictors of the patterns of species richness and phylogenetic diversity‐but not phylogenetic endemism‐across different Atlantic Forest groups.

Survival of Xanthomonas campestris pv. campestris in the phyllosphere and rhizosphere of crops - João César da Silva; Tadeu Antônio Fernandes da Silva Júnior; José Marcelo Soman; Daniele Maria do Nascimento; Luana Laurindo de Melo; Letícia Rodrigues Oliveira; Maria Márcia Pereira Sartori; Antonio Carlos Maringoni (Plant and Soil, 2021)

Human-modified landscapes narrow the isotopic niche of neotropical birds - Ana Beatriz Navarro; Marcelo Magioli; Juliano André Bogoni; Marcelo Zacharias Moreira; Luís Fábio Silveira; Eduardo Roberto Alexandrino; Daniela Tomasio Apolinario da Luz; Marco Aurelio Pizo; Wesley Rodrigues Silva; Vanessa Cristina de Oliveira; Reginaldo José Donatelli; Alexander V. Christianini; et al. (Oecologia, 2021)

The invasion of an alien characiform fish and the decline of a native congener in a Neotropical river-floodplain system - Maria Julia Mileo Ganassin; Emili García-Berthou; Amanda Cantarute Rodrigues; Carolina Pedrozo do Nascimento; Carolina Mendes Muniz; Matheus Tenório Baumgartner; Marcelo Henrique Schmitz; Luiz Carlos Gomes (Hydrobiologia, 2021)

Selection strategy of a Coffea canephora rootstock with simultaneous nematode resistance to Meloidogyne exigua, M. incognita and M. paranaensis - Wallace Gonçalves; Vinicius Teixeira Andrade; Bárbhara Joana dos Reis Fatobene; Larissa de Brito Caixeta; Lilian Padilha; Claudio Marcelo Gonçalves Oliveira; Juliana Magrinelli Osório Rosa; Lucas Mateus Rivero Rodrigues; Oliveiro Guerreiro Filho (European Journal of Plant Pathology, 2021)

Understanding how environmental heterogeneity and elevation drives the distribution of woody communities across vegetation types within the campo rupestre in South America - Marcelo Leandro Bueno; Vanessa Leite Rezende; Luiza Fonseca A. De Paula; João Augusto Alves Meira-Neto; José Roberto Rodrigues Pinto; Andreza Viana Neri; Vanessa Pontara (Journal of Mountain Science, 2021)

Phenotypic and genotypic detection of antibiotic-resistant bacteria in fresh fruit juices from a public hospital in Rio de Janeiro - Nathalia Diogo Trocado; Marcelo Soares de Moraes; Lilian Aveleda; Cristiane Rodrigues Silva; Victor Augustus Marin (Archives of Microbiology, 2021)

A mixture of trehalose derivatives stimulates the antioxidant system and improves photosynthetic efficiency in maize under water deficit - Joice Aparecida de Novais Portugal; Alexandra dos Santos Ambrósio; Kamila Rezende Dázio de Souza; Danielle Ferreira Dias; Plínio Rodrigues dos Santos Filho; Thiago Belarmino de Souza; Marcelo Henrique dos Santos; Antonio Carlos Doriguetto; Paulo César Magalhães; Thiago Corrêa de Souza (Acta Physiologiae Plantarum, 2021)

Nitrogen use efficiency and recovery in a wheat-corn rotation under tropical savannah conditions - Fernando Shintate Galindo; Edson Cabral da Silva; Paulo Humberto Pagliari; Guilherme Carlos Fernandes; Willian Lima Rodrigues; Antônio Leonardo Campos Biagini; Eduardo Bianchi Baratella; Castro Alves da Silva Júnior; Mário João Moretti Neto; Takashi Muraoka; Marcelo Carvalho Minhoto Teixeira Filho (Nutrient Cycling in Agroecosystems, 2021)

Goat performance on pure Andropogon gayanus pastures or associated with legumes - Raniel Lustosa de Moura; Maria Elizabete de Oliveira; Wanderson Fiares de Carvalho; Marconio Martins Rodrigues; Maurilio Souza dos Santos; Ricardo Loiola Edvan; Adibe Luiz Abdalla; Marcelo Zacharias Moreira; Edson Mendes da Silva (Tropical Animal Health and Production, 2021)

Citrus Mealybug Performance and Plant Strata Preference on Different Coffee Varieties - Nilson Rodrigues-Silva; Gerson Adriano Silva; Pablo Costa Gontijo; Tarcísio Vinsintin da Silva Galdino; Arthur Vieira Ribeiro; Marcelo Coutinho Picanço (Neotropical Entomology, 2021)

Influence of microcurrent on the modulation of remodelling genes in a wound healing assay - Daniela Fernanda Dezotti Silva; Lucas de Oliveira Fujii; Gabriela Bortolança Chiarotto; Camila Andrea de Oliveira; Thiago Antônio Moretti de Andrade; Alexandre Leite Rodrigues de Oliveira; Marcelo Augusto Marretto Esquisatto; Fernanda Aparecida Sampaio Mendonça; Gláucia Maria Tech dos Santos; Andrea Aparecida de Aro (Molecular Biology Reports, 2021)

Reliability of evidence‐review methods in restoration ecology - João P. Romanelli; Paula Meli; Rafaela P. Naves; Marcelo C. Alves; Ricardo R. Rodrigues (Conservation Biology, 2021)
In restoration science, evidence reviews play a crucial role in summarizing research findings in practice and policy. However, if unreliable or inappropriate methods are used to review evidence, decisions based on these reviews may not accurately reflect the available evidence base. To assess the current value of restoration reviews, we examined a sample of meta‐analyses and narrative syntheses (n = 91) with the Collaboration for Environmental Evidence Synthesis Assessment Tool (CEESAT), which uses detailed criteria to assesses the method of policy‐relevant evidence synthesis according to elements important for objectivity, transparency, and comprehensiveness. Overall, reviews scored low based on this standard: median score 16 out of 39, modal score 15, and mean 16.6. Meta‐analyses scored higher than narrative syntheses (median 17 vs. 5, respectively), although there were some outlier narrative syntheses that had high scores, suggesting that quantitative synthesis does not solely reflect the reliability of a review. In general, criteria spanning the more fundamental review stages (i.e., searching for studies and including studies) received low scores for both synthesis types. Conversely, criteria comprising the later stages of the review (i.e., critical appraisal, data extraction, and data synthesis) were generally well described in meta‐analyses; thus, these criteria achieved the highest individual CEESAT scores. We argue that restoration ecology is well positioned to advance so‐called evidence‐based restoration, but review authors should elucidate their conceptual understanding of evidence syntheses and recognize that conducting reliable reviews demands the same methodological rigor and reporting standards used in primary research. Given the potential of evidence reviews to inform management, policy, and research, it is of vital importance that the overall methodological reliability of restoration reviews be improved.

Conservation of Brazilian freshwater biodiversity: Thinking about the next 10 years and beyond - Valter M. Azevedo-Santos; Jorge Luiz Rodrigues-Filho; Philip M. Fearnside; Thomas E. Lovejoy; Marcelo F. G. Brito (Biodiversity and Conservation, 2021)

Impaired thermoregulation in spontaneously hypertensive rats during physical exercise is related to reduced hypothalamic neuronal activation - Lucas Rios Drummond; Helton Oliveira Campos; Paulo Marcelo de Andrade Lima; Cletiana Gonçalves da Fonseca; Ana Cançado Kunstetter; Quezia Teixeira Rodrigues; Raphael Escorsim Szawka; Antônio José Natali; Thales Nicolau Prímola-Gomes; Samuel Penna Wanner; Cândido Celso Coimbra (Pflügers Archiv - European Journal of Physiology, 2020)

Investigation of Azospirillum brasilense Inoculation and Silicon Application on Corn Yield Responses - Fernando Shintate Galindo; Paulo Humberto Pagliari; Willian Lima Rodrigues; Maikon Richer de Azambuja Pereira; Salatiér Buzetti; Marcelo Carvalho Minhoto Teixeira Filho (Journal of Soil Science and Plant Nutrition, 2020)

Molecular Inferences on Scomberomorus brasiliensis, From the Western South Atlantic, Based on Two Mitochondrial Genes - Divino B. da Cunha; Luis Fernando S. Rodrigues-Filho; João Braúllio de Luna Sales; Pericles Rêgo; Cleonilde Queiroz; Iracilda Sampaio; Marcelo Vallinoto (Frontiers in Marine Science, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Development of an Index to Evaluate the Environmental Performance of Sugar-Energy Production Plants - Marcelo Girotto Rebelato; Andreia Marize Rodrigues; Luciana Maria Saran; Leonardo Lucas Madaleno; Otávio José de Oliveira (Sugar Tech, 2020)

Sugarcane Juice with Co-encapsulated Bifidobacterium animalis subsp. lactis BLC1 and Proanthocyanidin-Rich Cinnamon Extract - Augusto Tasch Holkem; Edmur José Santos Neto; Megumi Nakayama; Clitor J. F. Souza; Marcelo Thomazini; Fabio Augusto Gallo; Marluci Palazzolli da Silva; Laura de Queiroz Bomdespacho; Carla Giovana Luciano; Izabel Cristina Freitas Moraes; Rodrigo Rodrigues Petrus; Carmen S. Favaro-Trindade (Probiotics and Antimicrobial Proteins, 2020)

Dihydrofolate Reductase (DHFR) del19bp Polymorphism and Down Syndrome Offspring - Marcelo Aguiar Costa-Lima; Hazel Nunes Barboza; Joissy Aprigio; Cláudia de Melo Moura; Thereza Fonseca Quirico-Santos; Márcia Gonçalves Ribeiro; Márcia Rodrigues Amorim (Journal of Molecular Neuroscience, 2020)

Correction to: The Ichnological Record of Araraquara Sidewalks: History, Conservation, and Perspectives from This Urban Paleontological Heritage of Southeastern Brazil - Heitor Francischini; Marcelo Adorna Fernandes; Josiane Kunzler; Robson Rodrigues; Giuseppe Leonardi; Ismar de Souza Carvalho (Geoheritage, 2020)

The Ichnological Record of Araraquara Sidewalks: History, Conservation, and Perspectives from This Urban Paleontological Heritage of Southeastern Brazil - Heitor Francischini; Marcelo Adorna Fernandes; Josiane Kunzler; Robson Rodrigues; Giuseppe Leonardi; Ismar de Souza Carvalho (Geoheritage, 2020)

Novel frameshift variant of the CFTR gene: S511Lfs*2 from phenotype to molecular predictions - Thaiane Rispoli; Grazielle Motta Rodrigues; Mayara Jorgens Prado; Leonardo Araújo Pinto; Marcelo Tadday Rodrigues; Cynthia Rocha Dullius; Tarciana Grandi; Cláudia Maria Dornelles da Silva; José Eduardo Vargas; Maurício Menegatti Rigo; Maria Lucia Rossetti (Molecular Biology Reports, 2020)

Gastroenteric Viruses Detection in a Drinking Water Distribution-to-Consumption System in a Low-Income Community in Rio de Janeiro - Marize Pereira Miagostovich; Mônica Simões Rocha; Fabiane Bertoni dos Reis; Marcelo Santos Sampaio; Renata de Saldanha da Gama Gracie Carrijo; Fabio Correia Malta; Janaína Rodrigues; Amanda Genuino; Matheus Ribeiro da Silva Assis; Tulio Machado Fumian; Paulo Rubens Guimarães Barrocas (Food and Environmental Virology, 2020)

Identification of genes from the general phenylpropanoid and monolignol-specific metabolism in two sugarcane lignin-contrasting genotypes - Douglas Jardim-Messeder; Tatiane da Franca Silva; Jose Pedro Fonseca; José Nicomedes Junior; Lucia Barzilai; Thais Felix-Cordeiro; Joyce Carvalho Pereira; Clara Rodrigues-Ferreira; Isabela Bastos; Tereza Cristina da Silva; Vinicius de Abreu Waldow; Daniela Cassol; et al. (Molecular Genetics and Genomics, 2020)

Morphological Changes in Sugarcane Crop Induced by the Plant Growth-Promoting Bacterium Azospirillum brasilense - Ronaldo da Silva Viana; Bruno Rafael de Almeida Moreira; Lucas Aparecido Manzani Lisboa; Rômulo Sandu Junior; Thiago Assis Rodrigues Nogueira; Paulo Alexandre Monteiro de Figueiredo; Marcelo Carvalho Minhoto Teixeira Filho; Sergio Bispo Ramos (Sugar Tech, 2020)

Correction to: Ecological restoration as a strategy for mitigating and adapting to climate change: lessons and challenges from Brazil - Mercedes M. C. Bustamante; José Salomão Silva; Aldicir Scariot; Alexandre Bonesso Sampaio; Daniel Luis Mascia Vieira; Edenise Garcia; Edson Sano; Geraldo Wilson Fernandes; Giselda Durigan; Iris Roitman; Isabel Figueiredo; Ricardo Ribeiro Rodrigues; et al. (Mitigation and Adaptation Strategies for Global Change, 2020)

Climate change impacts under representative concentration pathway scenarios on streamflow and droughts of basins in the Brazilian Cerrado biome - Jéssica A. M. Rodrigues; Marcelo R. Viola; Lívia A. Alvarenga; Carlos R. de Mello; Sin C. Chou; Vinícius A. de Oliveira; Venkatesh Uddameri; Marco A. V. Morais (International Journal of Climatology, 2020)
Brazilian Cerrado biome is the largest and richest tropical savanna in the world. In order to understand the effects of climate changes on the hydrology of the Cerrado basins, this paper investigates the hydrological impacts of climate change throughout the 21st century under different emissions scenarios on the streamflow and on the droughts in the Sono, Manuel Alves da Natividade and Palma basins, located in the Brazilian Cerrado. For this purpose, the SWAT hydrological model driven by the downscaling of the HadGEM2‐ES and MIROC5 global climate models associated with RCP4.5 and RCP8.5 scenarios were used in three time slices (2011–2040, 2041–2070 and 2071–2099). The Standardized Precipitation Index (SPI) and the Standardized Streamflow Index (SSFI) were used to characterize droughts. In general, the results showed that the duration, intensity and frequency of the meteorological and hydrological droughts are expected to increase during the future periods. However, the hydrological droughts are projected to be larger than the meteorological droughts. Reductions in the streamflow are indicated in all future time slices and under both RCPs, especially, during dry periods, which may cause negative impacts in the ecological functions of the Cerrado biome, risk for reduction of the recharge of aquifers and risk for the electric energy production in northern Brazil.

Increased Mmp/Reck Expression Ratio Is Associated with Increased Recognition Memory Performance in a Parkinson’s Disease Animal Model - Adauto Spindola; Adriano D. S. Targa; Lais Soares Rodrigues; Sheila Maria Brochado Winnischofer; Marcelo M. S. Lima; Mari Cleide Sogayar; Marina Trombetta-Lima (Molecular Neurobiology, 2020)

Functional response of Euseius concordis feeding on Oligonychus ilicis (Acari: Phytoseiidae, Tetranychidae) - Erika Carla da Silveira; Paulo Rebelles Reis; Melina Flávia Siqueira; Melissa Alves Toledo; Gilberto Rodrigues Liska; Marcelo Ângelo Cirillo (Experimental and Applied Acarology, 2020)

The Role of Baccharis dracunculifolia and its Chemical Profile on Green Propolis Production by Apis mellifera - Débora Munhoz Rodrigues; Marcelo Claro De Souza; Caroline Arruda; Rodrigo Augusto Santinelo Pereira; Jairo Kenupp Bastos (Journal of Chemical Ecology, 2020)

Multifaceted antibodies development against synthetic α-dystroglycan mucin glycopeptide as promising tools for dystroglycanopathies diagnostic - Thais Canassa-DeLeo; Vanessa Leiria Campo; Lílian Cataldi Rodrigues; Marcelo Fiori Marchiori; Carlos Fuzo; Marcelo Macedo Brigido; Annamaria Sandomenico; Menotti Ruvo; Andrea Queiroz Maranhão; Marcelo Dias-Baruffi (Glycoconjugate Journal, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Bridging the gap between will and action on climate change adaptation in large cities in Brazil - Gabriela Marques Di Giulio; Roger Rodrigues Torres; David M. Lapola; Ana Maria Bedran-Martins; Maria da Penha Vasconcellos; Diego Rafael Braga; Marcos Paulo Fuck; Yohanna Juk; Veruska Nogueira; Ana Carolina Penna; Tiago Jacaúna; Marcelo Fetz; et al. (Regional Environmental Change, 2019)

Bridging the gap between will and action on climate change adaptation in large cities in Brazil - Gabriela Marques Di Giulio; Roger Rodrigues Torres; David M. Lapola; Ana Maria Bedran-Martins; Maria da Penha Vasconcellos; Diego Rafael Braga; Marcos Paulo Fuck; Yohanna Juk; Veruska Nogueira; Ana Carolina Penna; Tiago Jacaúna; Marcelo Fetz; et al. (Regional Environmental Change, 2019)

Physiological and biochemical impacts of silicon against water deficit in sugarcane - Breno Kennedy Lima Bezerra; Giuseppina Pace Pereira Lima; André Rodrigues dos Reis; Marcelo de Almeida Silva; Mônica Sartori de Camargo (Acta Physiologiae Plantarum, 2019)

Noninferiority field trial for evaluation of efficacy of ciprofloxacin associated with internal teat sealant as dry-off protocol - Cristian Marlon de Magalhães Rodrigues Martins; Bruna Gomes Alves; Camylla Pedrosa Monteiro; Eduardo Souza Campos Pinheiro; Marcelo Arne Feckinghaus; Luiz Gustavo Paranhos; Marcos V. dos Santos (Tropical Animal Health and Production, 2019)

Testing main Amazonian rivers as barriers across time and space within widespread taxa - Renata M. Pirani; Fernanda P. Werneck; Andréa T. Thomaz; Mariah L. Kenney; Marcelo J. Sturaro; Teresa C. S. Ávila‐Pires; Pedro L. V. Peloso; Miguel T. Rodrigues; L. Lacey Knowles (Journal of Biogeography, 2019)
Aim Present Amazonian diversity patterns can result from many different mechanisms and, consequently, the factors contributing to divergence across regions and/or taxa may differ. Nevertheless, the river‐barrier hypothesis is still widely invoked as a causal process in divergence of Amazonian species. Here we use model‐based phylogeographic analyses to test the extent to which major Amazonian rivers act similarly as barriers across time and space in two broadly distributed Amazonian taxa. Local Amazon rain forest. Taxon The lizard Gonatodes humeralis (Sphaerodactylidae) and the tree frog Dendropsophus leucophyllatus (Hylidae). Methods We obtained RADseq data for samples distributed across main river barriers, representing main Areas of Endemism previously proposed for the region. We conduct model‐based phylogeographic and genetic differentiation analyses across each population pair. Results Measures of genetic differentiation (based on F ST calculated from genomic data) show that all rivers are associated with significant genetic differentiation. Parameters estimated under investigated divergence models showed that divergence times for populations separated by each of the 11 bordering rivers were all fairly recent. The degree of differentiation consistently varied between taxa and among rivers, which is not an artifact of any corresponding difference in the genetic diversities of the respective taxa, or to amounts of migration based on analyses of the site‐frequency spectrum. Main conclusions Taken together, our results support a dispersal (rather than vicariance) history, without strong evidence of congruence between these species and rivers. However, once a species crossed a river, populations separated by each and every river have remained isolated—in this sense, rivers act similarly as barriers to any further gene flow. This result suggests differing degrees of persistence and gives rise to the seeming contradiction that the divergence process indeed varies across time, space and species, even though major Amazonian rivers have acted as secondary barriers to gene flow in the focal taxa.

Physiological and thylakoid ultrastructural changes in cyanobacteria in response to toxic manganese concentrations - Karen Ann Ferreira Moura; Claudineia Lizieri; Maione Wittig Franco; Marcelo Gomes Marçal Vieira Vaz; Wagner L. Araújo; Peter Convey; Francisco Antônio Rodrigues Barbosa (Ecotoxicology, 2019)

Detection of Colletotrichum gloeosporioides in native cashew species in Brazil - Gil Rodrigues dos Santos; Jaíza Francisca Ribeiro Chagas; Nilson Rodrigues-Silva; Renato Almeida Sarmento; Evelynne Urzêdo Leão; Ricardo Siqueira da Silva; Marcelo Coutinho Picanço (Brazilian Journal of Microbiology, 2019)

Ecological restoration as a strategy for mitigating and adapting to climate change: lessons and challenges from Brazil - Mercedes M. C. Bustamante; José Salomão Silva; Aldicir Scariot; Alexandre Bonesso Sampaio; Daniel Luis Mascia; Edenise Garcia; Edson Sano; Geraldo Wilson Fernandes; Giselda Durigan; Iris Roitman; Isabel Figueiredo; Ricardo Ribeiro Rodrigues; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

Physiological parameters and plasticity as key factors to understand pioneer and late successional species in the Atlantic Rainforest - Orlando de Oliveira dos Santos; Keila Rego Mendes; Samuel Vitor Cordeiro Martins; Willian Batista-Silva; Marcos André dos Santos; Joselma Maria de Figueirôa; Edivan Rodrigues de Souza; Denise Fernandes; Wagner Luiz Araújo; Marcelo Francisco Pompelli (Acta Physiologiae Plantarum, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Stochastic Estimation of Potential and Depleted Productivity of Soybean Grain and Oil - Marcelo Rodrigues Alambert; Renan Caldas Umburanas; Felipe Schwerz; Klaus Reichardt; Durval Dourado-Neto (International Journal of Plant Production, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Incentives for aquaculture in protected areas: possible consequences for biodiversity and its services in southern Brazil - Jorge L. Rodrigues Filho; Débora Lugli-Bernardes; Lia Mayrink Sabinson; Rodrigo Machado; Harry Boos; Luciano Lorenzi; Marcelo Manoel Domingos; David Valença Dantas (Biodiversity and Conservation, 2019)

Dopaminergic Lesion in the Olfactory Bulb Restores Olfaction and Induces Depressive-Like Behaviors in a 6-OHDA Model of Parkinson’s Disease - Jessica L. Ilkiw; Luana C. Kmita; Adriano D. S. Targa; Ana Carolina D. Noseda; Lais S. Rodrigues; Flávia W. C. Dorieux; Juliane Fagotti; Patrícia dos Santos; Marcelo M. S. Lima (Molecular Neurobiology, 2019)

Clusters of genetic diseases in Brazil - Gabriela Costa Cardoso; Marcelo Zagonel de Oliveira; Vanessa Rodrigues Paixão-Côrtes; Eduardo Enrique Castilla; Lavínia Schuler-Faccini (Journal of Community Genetics, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Diatom responses to environmental changes in the Upper Paraná River floodplain (Brazil) during the last ~ 1000 years - Daiane Trevisan Ruwer; Marcelo Corrêa Bernardes; Liliana Rodrigues (Journal of Paleolimnology, 2018)

Can otoliths of Genidens genidens (Cuvier 1829) (Siluriformes: Ariidae) reveal differences in life strategies of males and females? - Thaís Rodrigues Maciel; André Martins Vaz-dos-Santos; Marcelo Vianna (Environmental Biology of Fishes, 2018)

Phylogeography of Muller's termite frog suggests the vicariant role of the Central Brazilian Plateau - Eliana F. Oliveira; Marcelo Gehara; Vinícius A. São‐Pedro; Gabriel C. Costa; Frank T. Burbrink; Guarino R. Colli; Miguel T. Rodrigues; Adrian A. Garda (Journal of Biogeography, 2018)
Aim To test three different scenarios to account for the geographic distribution of genetic variation in Dermatonotus muelleri , a fossorial frog endemic of the South American diagonal of open formations ( DOF ) formed by Chaco, Cerrado, and Caatinga biomes: (a) The pan‐ DOF hypothesis, where these biomes behave as a single biogeographical unit and DOF species lack population structure; (b) the southwest‐northeast ( SW ‐ NE ) hypothesis, where structured populations along the DOF have either asymmetric or unidirectional gene flow in the northeast direction; (c) the vicariance hypothesis, where a pattern of population structure with no or reduced gene flow is observed. Location Caatinga, Cerrado, and Chaco in South America. Methods We sampled 179 individuals across the species distribution and sequenced one mitochondrial and two nuclear markers. We evaluated population structure, the presence, direction, and asymmetry of gene flow, and demographic changes to test three different phylogeographic hypotheses for D. muelleri using a model‐based simulation approach. Results We found two geographically structured lineages with no gene flow, refuting pan‐ DOF hypothesis. The Southwest lineage occurs in Chaco and western Cerrado and the Northeast lineage in eastern Cerrado and Caatinga. Our results support the model with demographic change for the Northeast lineage and constant size for Southwest lineage. The vicariance model with divergence time estimated around 4 Ma was preferred. Main conclusions Vicariance was the best explanation for the geographic distribution of genetic variation in Dermatonotus . Divergence time supports the role of Neogene orogeny in central Brazil for the splitting of Dermatonotus lineages. The influence of Pleistocene climatic fluctuations seems restricted to changes in one lineage's population size. Therefore, both ancient and recent events shaped the phylogeography of Dermatonotus . Genetic divergence, lack of gene flow, and the presence of a geographic barrier between lineages indicate the existence of a cryptic, undescribed species in northeastern Brazil.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Gas seeps and gas hydrates in the Amazon deep-sea fan - Joao Marcelo Ketzer; Adolpho Augustin; Luiz Frederico Rodrigues; Rafael Oliveira; Daniel Praeg; Maria Alejandra Gomez Pivel; Antonio Tadeu dos Reis; Cleverson Silva; Bruno Leonel (Geo-Marine Letters, 2018)

Lambari fish Deuterodon iguape as an alternative to live bait for estuarine recreational fishing - Marcelo Barbosa Henriques; Lúcio Fagundes; Maria Letizia Petesse; Newton José Rodrigues da Silva; Karina Fernandes Oliveira Rezende; Edison Barbieri (Fisheries Management and Ecology, 2018)
Fishing tourism is growing steadily in Brazil. Artisanal fishers meeting the demand for recreational fishing are capturing live juvenile shrimp in the estuaries and selling them for live bait, preventing the recruitment of a larger contingent into the ocean. This study compares the efficiency of using lambari, Deuterodon iguape Eigenmann, as live bait with the shrimp, Penaeus schmitti Burkenroad , while fishing for common snook ( Centropomus spp.), as well as to evaluate the swimming behaviour of D. iguape in different salinities. The results showed that there was no significant difference between the live baits used ( P. schmitti vs D. iguape ). The month, the period of the day and salinity presented differences. The size of the species did not depend on the type of bait used. There was no statistical difference in swimming behaviour, but there was a trend of increased speed and displacement in the group exposed to a salinity of 10 g/L. In conclusion, D. iguape appears as effective as P. schmitti and can be successfully used as live bait; and from an ecological point of view, it reduces the impact of fishing on juvenile shrimp.

Brain-Derived Neurotrophic Factor Prevents Depressive-Like Behaviors in Early-Symptomatic YAC128 Huntington’s Disease Mice - Victor Silva da Fonsêca; André R. da Silva Colla; Cristine de Paula Nascimento-Castro; Evelini Plácido; Julia Macedo Rosa; Marcelo Farina; Joana Gil-Mohapel; Ana Lúcia S. Rodrigues; Patricia S. Brocardo (Molecular Neurobiology, 2018)

Winds: intensity and power density simulated by RegCM4 over South America in present and future climate - Michelle Simões Reboita; Tatiana Rocha Amaro; Marcelo Rodrigues de Souza (Climate Dynamics, 2018)

Diversification with gene flow and niche divergence in a lizard species along the South American “diagonal of open formations” - Emanuel M. Fonseca; Marcelo Gehara; Fernanda P. Werneck; Flávia M. Lanna; Guarino R. Colli; Jack W. Sites; Miguel T. Rodrigues; Adrian A. Garda (Journal of Biogeography, 2018)
Aim To assess the effects of historical events on the tempo and mode of diversification of the lizard Polychrus acutirostris along the South American diagonal of open formations ( DOF ). Location Caatinga and Cerrado biomes in Brazil. Methods We sequenced fragments of one mt DNA and three nu DNA genes of 68 individuals from 33 localities. We used population assignment methods to access genetic structure and estimate lineage boundaries. Next, we estimated lineage relationships, intraspecific diversity, environmental niche similarity and demographic history. Finally, we tested 12 diversification scenarios using an approximate Bayesian computation ( ABC ) approach. Results We recovered three non‐overlapping, geographically structured lineages corresponding to Caatinga, north‐east Cerrado and south‐west Cerrado, with the major divergence event dating to the Late Neogene. We also recovered a complex scenario of divergence associated with gene flow and niche divergence. Main conclusions We show a complex history of diversification along the South American DOF . Our findings support the role of environmental features as the likely drivers of P. acutirostris intraspecific diversification during the Late Neogene.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Methionine and/or Methionine Sulfoxide Alter Ectoenzymes Activities in Lymphocytes and Inflammatory Parameters in Serum from Young Rats: Acute and Chronic Effects - Mayara Sandrielly Pereira Soares; Marcelo Zanusso Costa; Tatiane Morgana da Silva; Marta Gazal; Carlus Augustu Tavares do Couto; Gabriela Nogueira Debom; Rodrigo Rodrigues; Juliana Hofstätter Azambuja; Emerson André Casali; Cesar Eduardo Jacintho Moritz; Marta Frescura Duarte; Elizandra Braganhol; et al. (Cell Biochemistry and Biophysics, 2018)

Kinetic and thermodynamic parameters, and partial characterization of the crude extract of tannase produced by Saccharomyces cerevisiae CCMB 520 - Lúzia Morgana de Melo Lopes; Larissa Hayannyelly Costa Batista; Marcos Juliano Gouveia; Tonny Cley Campos Leite; Marcelo Rodrigues Figueira de Mello; Sandra Aparecida de Assis; Amanda Reges de Sena (Natural Product Research, 2018)

In Vitro Anti/Pro-oxidant Activities of R. ferruginea Extract and Its Effect on Glioma Cell Viability: Correlation with Phenolic Compound Content and Effects on Membrane Dynamics - Desirée Magalhães dos Santos; Camila Valesca Jardim Rocha; Elita Ferreira da Silveira; Marcelo Augusto Germani Marinho; Marisa Raquel Rodrigues; Nichole Osti Silva; Ailton da Silva Ferreira; Neusa Fernandes de Moura; Gabriel Jorge Sagrera Darelli; Elizandra Braganhol; Ana Paula Horn; Vânia Rodrigues de Lima (The Journal of Membrane Biology, 2018)

Seroepidemiological survey on Leptospira spp. infection in wild and domestic mammals in two distinct areas of the semi-arid region of northeastern Brazil - Laís Ferrari dos Santos; Maíra Freitas Guimarães; Gisele Oliveira de Souza; Ivo Wesley Gomes da Silva; Josenilton Rodrigues Santos; Sérgio Santos Azevedo; Marcelo Bahia Labruna; Marcos Bryan Heinemann; Mauricio Claudio Horta (Tropical Animal Health and Production, 2017)

Role of Dynein Axonemal Heavy Chain 6 Gene Expression as a Possible Biomarker for Huntington’s Disease: a Translational Study - Lorena B. Areal; Lorraine P. Pereira; Fabiola M. Ribeiro; Isabella G. Olmo; Marcelo R. Muniz; Maria do Carmo Rodrigues; Patrik F. Costa; Cristina Martins-Silva; Stephen S. G. Ferguson; Daniela A. M. Guimarães; Rita G. W. Pires (Journal of Molecular Neuroscience, 2017)

Ammonia exposure and subsequent recovery trigger oxidative stress responses in juveniles of Brazilian flounder Paralichthys orbignyanus - Lucas Campos Maltez; Giovanna Rodrigues Stringhetta; Alain Danilo Enamorado; Marcelo Hideo Okamoto; Luis Alberto Romano; José María Monserrat; Luís André Sampaio; Luciano Garcia (Fish Physiology and Biochemistry, 2017)

Molecular phylogenetic diversity in the widespread lizard Cercosaura ocellata (Reptilia: Gymnophthalmidae) in South America - Marcelo José Sturaro; Teresa C. S. Avila-Pires; Miguel T. Rodrigues (Systematics and Biodiversity, 2017)

Molecular responses to recurrent drought in two contrasting rice genotypes - Priscila Ariane Auler; Marcelo Nogueira do Amaral; Gabriela dos Santos Rodrigues; Letícia Carvalho Benitez; Luciano Carlos da Maia; Gustavo Maia Souza; Eugenia Jacira Bolacel Braga (Planta, 2017)

MPP+-Lesioned Mice: an Experimental Model of Motor, Emotional, Memory/Learning, and Striatal Neurochemical Dysfunctions - Mauricio P. Cunha; Francis L. Pazini; Vicente Lieberknecht; Josiane Budni; Ágatha Oliveira; Júlia M. Rosa; Gianni Mancini; Leidiane Mazzardo; André R. Colla; Marina C. Leite; Adair R. S. Santos; Daniel F. Martins; et al. (Molecular Neurobiology, 2017)

Past land-use and ecological resilience in a lowland Brazilian Atlantic Forest: implications for passive restoration - Jerônimo Boelsums Barreto Sansevero; Pablo Viany Prieto; Andrea Sánchez-Tapia; João Marcelo Alvarenga Braga; Pablo José Francisco Pena Rodrigues (New Forests, 2017)

Anticonvulsive activity of (1S)-(−)-verbenone involving RNA expression of BDNF, COX-2, and c-fos - Cynthia Germoglio Farias de Melo; Paula Regina Rodrigues Salgado; Diogo Vilar da Fonsêca; Renan Marinho Braga; Marcelo Ricardo Dutra Caldas Filho; Ingrid Eulália Vieira de Farias; Hilzeth de Luna Freire Pessôa; Eleonidas Moura Lima; Ian Porto Gurgel do Amaral; Damião Pergentino de Sousa; Reinaldo Nóbrega de Almeida (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Cholinergic Oculomotor Nucleus Activity Is Induced by REM Sleep Deprivation Negatively Impacting on Cognition - Patrícia Dos Santos; Adriano D. S. Targa; Ana Carolina D. Noseda; Lais S. Rodrigues; Juliane Fagotti; Marcelo M. S. Lima (Molecular Neurobiology, 2017)

Environmental monitoring of water resources around a municipal landfill of the Rio Grande do Sul state, Brazil - Pâmela de Medeiros Engelmann; Victor Hugo Jacks Mendes dos Santos; Letícia Isabela Moser; Eduardo do Canto Bruzza; Cristina Barazzetti Barbieri; Pâmela Susin Barela; Diogo Pompéu de Moraes; Adolpho Herbert Augustin; Flávio Soares Goudinho; Clarissa Lovato Melo; João Marcelo Medina Ketzer; Luiz Frederico Rodrigues (Environmental Science and Pollution Research, 2017)

Interactive effects of marine heatwaves and eutrophication on the ecophysiology of a widespread and ecologically important macroalga - Lidiane Pires Gouvêa; Nadine Schubert; Cintia Dalcuche Leal Martins; Marina Sissini; Fernanda Ramlov; Eva Regina de Oliveira Rodrigues; Eduardo Oliveira Bastos; Vanessa Carvalho Freire; Marcelo Maraschin; José Carlos Simonassi; Donnangelo A. Varela; Davide Franco; et al. (Limnology and Oceanography, 2017)
Extreme temperature events are becoming more recurrent and are more frequent with major impacts on coastal ecosystems, which are additionally impacted by increasing urbanization, resulting in high nutrient load. So far little is known about cumulative and/or interactive effects of global and local stressors on species' performance. Here, we evaluated the single and combined effects of simulated heatwaves and eutrophication on the ecophysiology of Laurencia catarinensis in a bi‐factorial mesocosm experiment. The algae were exposed for 30 d to three different temperatures (20°C, 24°C, 28°C) and nutrient concentrations (low, intermediate, high) and their nutrient uptake rates, photosynthetic performance, growth rates, pigment and phenolic compound concentrations, as well as antioxidant capacity was determined and compared between treatments. Under low nutrient concentration, physiological performance and growth decreased with increasing temperatures. In contrast, they increased with higher nutrient availability and moderate temperature increase close to the summer average temperature, but largely declined upon exposure to higher temperature (28°C). This decline seemed to be related to oxidative stress, as indicated by an increase of compounds with antioxidant properties (lutein, zeaxanthin, phenols). Our data show that all measured parameters were affected by temperature and nutrient availability, with an interactive effect between these two factors, indicating that increasing temperature will influence macroalgal performance, and even more dramatically in coastal systems that are highly impacted by urbanization. However, the direction of the response will be determined by nutrient availability and will also depend on the magnitude of the temperature increase, that is, whether it surpasses the thermal threshold of the species.

Evaluation of stability and validation of reference genes for RT-qPCR expression studies in rice plants under water deficit - Priscila Ariane Auler; Letícia Carvalho Benitez; Marcelo Nogueira do Amaral; Isabel Lopes Vighi; Gabriela dos Santos Rodrigues; Luciano Carlos da Maia; Eugenia Jacira Bolacel Braga (Journal of Applied Genetics, 2017)

Quantification of the fate of mesotrione applied alone or in a herbicide mixture in two Brazilian arable soils - Kassio Ferreira Mendes; Bianca Assis Barbosa Martins; Marcelo Rodrigues dos Reis; Rodrigo Floriano Pimpinato; Valdemar Luiz Tornisielo (Environmental Science and Pollution Research, 2017)

Fighting Oxidative Stress: Increased Resistance of Male Rat Cerebellum at Weaning Induced by Low Omega 6/Omega 3 Ratio in a Protein-Deficient Diet - Ricielle Lopes Augusto; Alinny Rosendo Isaac; Ivanildo Inácio da Silva-Júnior; David Filipe de Santana; Diorginis José Soares Ferreira; Claudia Jacques Lagranha; Catarina Gonçalves-Pimentel; Marcelo Cairrão Araujo Rodrigues; Belmira Lara da Silveira Andrade-da-Costa (The Cerebellum, 2017)

Methylene Blue Adsorption on Chitosan-g-Poly(Acrylic Acid)/Rice Husk Ash Superabsorbent Composite: Kinetics, Equilibrium, and Thermodynamics - Marcelo G. Vaz; Antonio G. B. Pereira; André R. Fajardo; Antônio C. N. Azevedo; Francisco H. A. Rodrigues (Water, Air, & Soil Pollution, 2017)

Filamentous Fungi Isolates of Contaminated Sediment in the Amazon Region with the Potential for Benzo(a)pyrene Degradation - Hilton Marcelo de Lima Souza; Lara Durães Sette; Adolfo José da Mota; Joaquim Ferreira do Nascimento Neto; André Rodrigues; Tássio Brito de Oliveira; Fernando Mendes de Oliveira; Luiz Antônio de Oliveira; Hileia dos Santos Barroso; Sandra Patricia Zanotto (Water, Air, & Soil Pollution, 2016)

Differential Impact of Acclimation and Acute Water Deprivation in the Expression of Key Transcription Factors in Soybean Roots - Fábia Guimarães-Dias; Anna C. Neves-Borges; Alessandra J. Conforte; Leonardo Giovanella-Kampmann; André V. J. Ferreira; Regina M. S. Amorim; Magda A. Benevent; Maria Eugênia Lisei de Sá; Rosilene O. Mesquita; Fabiana A. Rodrigues; Alexandre L. Nepomuceno; Eduardo Romano; et al. (Plant Molecular Biology Reporter, 2016)

Genome wide association study (GWAS) for grain yield in rice cultivated under water deficit - Gabriel Feresin Pantalião; Marcelo Narciso; Cléber Guimarães; Adriano Castro; José Manoel Colombari; Flavio Breseghello; Luana Rodrigues; Rosana Pereira Vianello; Tereza Oliveira Borba; Claudio Brondani (Genetica, 2016)

Synthetic glycoconjugates inhibitors of tumor-related galectin-3: an update - Vanessa Leiria Campo; Marcelo Fiori Marchiori; Lílian Cataldi Rodrigues; Marcelo Dias-Baruffi (Glycoconjugate Journal, 2016)

Correlation of proline content and gene expression involved in the metabolism of this amino acid under abiotic stress - Letícia Carvalho Benitez; Isabel Lopes Vighi; Priscila Ariane Auler; Marcelo Nogueira do Amaral; Gabriela Peres Moraes; Gabriela dos Santos Rodrigues; Luciano Carlos da Maia; Ariano Martins de Magalhães Júnior; Eugenia Jacira Bolacel Braga (Acta Physiologiae Plantarum, 2016)

Profiling of adhesive-related genes in the freshwater cnidarian Hydra magnipapillata by transcriptomics and proteomics - Marcelo Rodrigues; Thomas Ostermann; Leopold Kremeser; Herbert Lindner; Christian Beisel; Eugene Berezikov; Bert Hobmayer; Peter Ladurner (Biofouling, 2016)

Energy and protein requirements of young Holstein calves in tropical condition - João Paulo Pacheco Rodrigues; Jessika Carolina Moutinho Lima; Marcelo Messias Duarte Castro; Sebastião de Campos Valadares Filho; Mariana Magalhães Campos; Mário Luiz Chizzotti; Marcos Inácio Marcondes (Tropical Animal Health and Production, 2016)

Indomethacin treatment reduces microglia activation and increases numbers of neuroblasts in the subventricular zone and ischaemic striatum after focal ischaemia - Rosana S Lopes; Marcelo M Cardoso; Arthur O Sampaio; Mario Santos Barbosa; Celice C Souza; Michelle C da Silva; Elane Magno N Ferreira; Marco Aurelio M Freire; Rafael Rodrigues Lima; Walace Gomes-Leal (Journal of Biosciences, 2016)

Homologous transplantation with fresh frozen bone for dental implant placement can induce HLA sensitization: a preliminary study - Paulo Eduardo de Lacerda; André Antonio Pelegrine; Marcelo Lucchesi Teixeira; Victor Angelo Martins Montalli; Helcio Rodrigues; Marcelo Henrique Napimoga (Cell and Tissue Banking, 2016)

Connectivity maintain mammal assemblages functional diversity within agricultural and fragmented landscapes - Marcelo Magioli; Katia Maria Paschoaletto Micchi de Ferraz; Eleonore Zulnara Freire Setz; Alexandre Reis Percequillo; Michelle Viviane de Sá Santos Rondon; Vanessa Villanova Kuhnen; Mariana Cristina da Silva Canhoto; Karen Evelyn Almeida dos Santos; Claudia Zukeran Kanda; Gabriela de Lima Fregonezi; Helena Alves do Prado; Mitra Katherina Ferreira; et al. (European Journal of Wildlife Research, 2016)

A new whitish flowered Epidendrum (Laeliinae-Orchidaceae) from the Atlantic Forest of southeastern Brazil - Edlley Pessoa; Marcelo Rodrigues Miranda; Marccus Alves (Brittonia, 2016)

Nutritional and productive performance of dairy cows fed corn silage or sugarcane silage with or without additives - Felipe Leite de Andrade; João Paulo Pacheco Rodrigues; Edenio Detmann; Sebastião de Campos Valadares Filho; Marcelo Messias Duarte Castro; Aline Souza Trece; Tadeu Eder Silva; Vivian Fischer; Kirsten Weiss; Marcos Inácio Marcondes (Tropical Animal Health and Production, 2016)

Intake, performance, and carcass characteristics of lambs fed spineless cactus replacing wheat bran - Sabrina Carla Rodrigues Felix; Ricardo Alexandre Silva Pessoa; Marcelo de Andrade Ferreira; Luciana Felizardo Pereira Soares; Janaina de Lima Silva; Karen Santos Felix de Abreu; Ana Caroline Cerqueira de Melo (Tropical Animal Health and Production, 2016)

The finishing stage in swine production: influences of feed composition on carbon footprint - Edivan Cherubini; Guilherme Marcelo Zanghelini; Jorge Manuel Rodrigues Tavares; Frank Belettini; Sebastião Roberto Soares (Environment, Development and Sustainability, 2015)

Speciation with gene flow in whiptail lizards from a Neotropical xeric biome - Eliana F. Oliveira; Marcelo Gehara; Vinícius A. São‐Pedro; Xin Chen; Edward A. Myers; Frank T. Burbrink; Daniel O. Mesquita; Adrian A. Garda; Guarino R. Colli; Miguel T. Rodrigues; Federico J. Arias; Hussam Zaher; et al. (Molecular Ecology, 2015)
Two main hypotheses have been proposed to explain the diversification of the Caatinga biota. The riverine barrier hypothesis ( RBH ) claims that the São Francisco River ( SFR ) is a major biogeographic barrier to gene flow. The Pleistocene climatic fluctuation hypothesis ( PCH ) states that gene flow, geographic genetic structure and demographic signatures on endemic Caatinga taxa were influenced by Quaternary climate fluctuation cycles. Herein, we analyse genetic diversity and structure, phylogeographic history, and diversification of a widespread Caatinga lizard ( Cnemidophorus ocellifer ) based on large geographical sampling for multiple loci to test the predictions derived from the RBH and PCH . We inferred two well‐delimited lineages (Northeast and Southwest) that have diverged along the Cerrado–Caatinga border during the Mid‐Late Miocene (6–14 Ma) despite the presence of gene flow. We reject both major hypotheses proposed to explain diversification in the Caatinga. Surprisingly, our results revealed a striking complex diversification pattern where the Northeast lineage originated as a founder effect from a few individuals located along the edge of the Southwest lineage that eventually expanded throughout the Caatinga. The Southwest lineage is more diverse, older and associated with the Cerrado–Caatinga boundaries. Finally, we suggest that C. ocellifer from the Caatinga is composed of two distinct species. Our data support speciation in the presence of gene flow and highlight the role of environmental gradients in the diversification process.

Resistance to Cowpea aphid-borne mosaic virus in species and hybrids of Passiflora: advances for the control of the passion fruit woodiness disease in Brazil - Eileen Azevedo Santos; Alexandre Pio Viana; Josie Cloviane de Oliveira Freitas; Fernando Higino de Lima e Silva; Rosana Rodrigues; Marcelo Eiras (European Journal of Plant Pathology, 2015)

Human exposure and risk assessment associated with mercury contamination in artisanal gold mining areas in the Brazilian Amazon - Zuleica Castilhos; Saulo Rodrigues-Filho; Ricardo Cesar; Ana Paula Rodrigues; Roberto Villas-Bôas; Iracina de Jesus; Marcelo Lima; Kleber Faial; Antônio Miranda; Edilson Brabo; Christian Beinhoff; Elisabeth Santos (Environmental Science and Pollution Research, 2015)

Genetics in primary health care and the National Policy on Comprehensive Care for People with Rare Diseases in Brazil: opportunities and challenges for professional education - Débora Gusmão Melo; Pamela Karen de Paula; Stephania de Araujo Rodrigues; Lucimar Retto da Silva de Avó; Carla Maria Ramos Germano; Marcelo Marcos Piva Demarzo (Journal of Community Genetics, 2015)

A Kinetic Characterization of (Na+, K+)-ATPase Activity in the Gills of the Pelagic Seabob Shrimp Xiphopenaeus kroyeri (Decapoda, Penaeidae) - Francisco Assis Leone; Malson Neilson Lucena; Luciana Augusto Rezende; Daniela Pereira Garçon; Marcelo Rodrigues Pinto; Fernando Luis Mantelatto; John Campbell McNamara (The Journal of Membrane Biology, 2015)

REM Sleep Deprivation Reverses Neurochemical and Other Depressive-Like Alterations Induced by Olfactory Bulbectomy - Maira J. Maturana; Cláudia Pudell; Adriano D. S. Targa; Laís S. Rodrigues; Ana Carolina D. Noseda; Mariana H. Fortes; Patrícia dos Santos; Cláudio Da Cunha; Sílvio M. Zanata; Anete C. Ferraz; Marcelo M. S. Lima (Molecular Neurobiology, 2015)

Tadpole richness in riparian areas is determined by niche-based and neutral processes - Alexandre Pinheiro de Almeida; Domingos de Jesus Rodrigues; Michel Varajão Garey; Marcelo Menin (Hydrobiologia, 2015)

Phylogeny and recombination analysis of Brazilian yellow passion fruit isolates of Cowpea aphid-borne mosaic virus: origin and relationship with hosts - Leilane K. Rodrigues; Leonardo A. Silva; Renata M. Garcêz; Alexandre L. R. Chaves; Ligia M. L. Duarte; José S. Giampani; Addolorata Colariccio; Ricardo Harakava; Marcelo Eiras (Australasian Plant Pathology, 2015)

Transcriptome analysis highlights changes in the leaves of maize plants cultivated in acidic soil containing toxic levels of Al3+ - Lucia Mattiello; Kevin Begcy; Felipe Rodrigues da Silva; Renato A. Jorge; Marcelo Menossi (Molecular Biology Reports, 2014)

Effects of Amino Acid Deletion on the Antiplasmodial Activity of Angiotensin II - Luiz Henrique Rodrigues Ferreira; Adriana Farias Silva; Marcelo Der Torossian Torres; Cibele Nicolaski Pedron; Margareth Lara Capurro; Flávio Lopes Alves; Antonio Miranda; Vani Xavier Oliveira (International Journal of Peptide Research and Therapeutics, 2014)

Replacement of wheat bran with spineless cactus (Opuntia ficus indica Mill cv Gigante) and urea in the diets of Holstein x Gyr heifers - Carolina Corrêa de Figueiredo Monteiro; Airon Aparecido Silva de Melo; Marcelo Andrade Ferreira; José Mauricio de Souza Campos; Julyana Sena Rodrigues Souza; Evannielly Thuanny dos Santos Silva; Rafael de Paula Xavier de Andrade; Emmanuelle Cordeiro da Silva (Tropical Animal Health and Production, 2014)

Early postnatal, but not late, exposure to chemical ambient pollutant 1,2-naphthoquinone increases susceptibility to pulmonary allergic inflammation at adulthood - Karen T. Santos; Juliana Florenzano; Leandro Rodrigues; Rodolfo R. Fávaro; Fernanda F. Ventura; Marcela G. Ribeiro; Simone A. Teixeira; Heloisa H. A. Ferreira; Susan D. Brain; Amílcar S. Damazo; Telma M. Zorn; Niels O. Câmara; et al. (Archives of Toxicology, 2014)

Action of growing degree days on the morphogenesis and physiological responses of calla lily - Marcelo Rodrigues; Patrícia Duarte de Oliveira Paiva; João Paulo Rodrigues Alves Delfino Barbosa; Thaís de Oliveira Fontes Mansur (Acta Physiologiae Plantarum, 2014)

Origin of the X1X1X2X2/X1X2Y sex chromosome system of Harttia punctata (Siluriformes, Loricariidae) inferred from chromosome painting and FISH with ribosomal DNA markers - Daniel Rodrigues Blanco; Marcelo Ricardo Vicari; Roberto Laridondo Lui; Roberto Ferreira Artoni; Mara Cristina de Almeida; Josiane Baccarin Traldi; Vladimir Pavan Margarido; Orlando Moreira-Filho (Genetica, 2014)

Investigation of blood parasites of pygoscelid penguins at the King George and Elephant Islands, South Shetlands Archipelago, Antarctica - Ralph Eric Thijl Vanstreels; Flavia R. Miranda; Valeria Ruoppolo; Ana Olívia de Almeida Reis; Erli Schneider Costa; Adriana Rodrigues de Lira Pessôa; João Paulo Machado Torres; Larissa Schmauder Teixeira da Cunha; Roberta da Cruz Piuco; Victor Hugo Valiati; Daniel González-Acuña; Marcelo B. Labruna; et al. (Polar Biology, 2014)

Effect of ultraviolet-B radiation in laboratory on morphological and ultrastructural characteristics and physiological parameters of selected cultivar of Oryza sativa L. - Sérgio L. de Almeida; Éder C. Schmidt; Debora Tomazi Pereira; Marianne Kreusch; Marthiellen R. de L. Felix; Luz K. P. Osorio; Roberta de Paula Martins; Alexandra Latini; Fernanda Ramlov; Fungyi Chow; Marcelo Maraschin; Ana C. Rodrigues; et al. (Protoplasma, 2013)

Metabolism, Intake, and Digestibility of Lambs Supplemented with Organic Chromium - Jose Francisco Xavier da Rocha; Adelina Rodrigues Aires; Matheus Augusto Gonçalves Nunes; Erico Marlon Moraes Flores; Gilberto Vilmar Kozloski; Agueda Castagna de Vargas; Luana D’Avila Farias; Marcelo da Silva Cecim; Marta Lizandra do Rego Leal (Biological Trace Element Research, 2013)

Metabolic and cellular alterations induced by diesel oil in Hypnea musciformis (Wulfen) J. V. Lamour. (Gigartinales, Rhodophyta) - Fernanda Ramlov; Tiago José Griebeler Carvalho; Éder Carlos Schmidt; Cintia Dalcuche Leal Martins; Marianne Gabi Kreusch; Eva Regina de Oliveira Rodrigues; Cláudia Marlene Bauer; Zenilda Laurita Bouzon; Paulo Antunes Horta; Marcelo Maraschin (Journal of Applied Phycology, 2013)

Multicompartimental Nanoparticles for Co-Encapsulation and Multimodal Drug Delivery to Tumor Cells and Neovasculature - Lívia Palmerston Mendes; Marilisa Pedroso Nogueira Gaeti; Paulo Henrique Marcelino de Ávila; Marcelo de Sousa Vieira; Bruna dos Santos Rodrigues; Renato Ivan de Ávila Marcelino; Lílian Cristina Rosa dos Santos; Marize Campos Valadares; Eliana Martins Lima (Pharmaceutical Research, 2013)

Castor beans hulls as a replacement for Tifton 85 hay in lamb diets - Rafael de Paula Xavier de Andrade; Marcelo de Andrade Ferreira; Stela Antas Urbano; Marcílio de Azevedo; Sabrina Carla Rodrigues Félix; Michelle Christina Bernardo de Siqueira; Felipe José Lins Alves; Juana Catarina Cariri Chagas (Tropical Animal Health and Production, 2013)

Physical mapping of (GATA) n and (TTAGGG) n sequences in species of Hypostomus (Siluriformes, Loricariidae) - JOSIANE BACCARIN TRALDI; DANIEL RODRIGUES BLANCO; MARCELO RICARDO VICARI; JULIANA DE FÁTIMA MARTINEZ; ROBERTO LARIDONDO LUI; ROBERTO FERREIRA ARTONI; ORLANDO MOREIRA-FILHO (Journal of Genetics, 2013)

The role of the Robertsonian rearrangements in the origin of the XX/XY1Y2 sex chromosome system and in the chromosomal differentiation in Harttia species (Siluriformes, Loricariidae) - Daniel Rodrigues Blanco; Marcelo Ricardo Vicari; Roberto Laridondo Lui; Luiz Antônio Carlos Bertollo; Josiane Baccarin Traldi; Orlando Moreira-Filho (Reviews in Fish Biology and Fisheries, 2013)

Association of methylenetetrahydrofolate reductase gene 677C > T polymorphism and Down syndrome - Marcelo Aguiar Costa-Lima; Márcia Rodrigues Amorim; Iêda Maria Orioli (Molecular Biology Reports, 2013)

Isolation and characterization of 18 microsatellites for Lycengraulis grossidens (Pisces: Clupeiformes) - Ana C. G. Mai; João P. Vieira; Alicia A. Plavan; Marcelo F. Nobrega; Leonardo E. Moraes; Fábio L. Rodrigues; Luis F. Marins (Conservation Genetics Resources, 2013)

Adolescents with chronic migraine commonly exhibit depressive symptoms - Juliana Harumi Arita; Jaime Lin; Ricardo Silva Pinho; Thais Soares Cianciarullo Minett; Maria Sylvia de Souza Vitalle; Mauro Fisberg; Mario Fernando Prieto Peres; Luiz Celso Pereira Vilanova; Marcelo Rodrigues Masruha (Acta Neurologica Belgica, 2013)

Protective Effects of Ascorbic Acid on Behavior and Oxidative Status of Restraint-Stressed Mice - Morgana Moretti; Josiane Budni; Danubia Bonfanti dos Santos; Alessandra Antunes; Juliana Felipe Daufenbach; Luana Meller Manosso; Marcelo Farina; Ana Lúcia S. Rodrigues (Journal of Molecular Neuroscience, 2013)

Reproductive isolation between diploid and tetraploid cytotypes of Libidibia ferrea (= Caesalpinia ferrea) (Leguminosae): ecological and taxonomic implications - Laís Angélica Borges; Luiz Gustavo Rodrigues Souza; Marcelo Guerra; Isabel Cristina Machado; Gwilym P. Lewis; Ariadna Valentina Lopes (Plant Systematics and Evolution, 2012)

An integrated GIS for sedimentological and geomorphological analysis of a lagoon environment. Barra de Cananéia inlet region, (Southeastern Brazil) - Luis Américo Conti; Carlos Alberto S. Araujo; Fernando S. Paolo; Roberto L. Barcellos; Marcelo Rodrigues; Michel M. Mahiques; Valdenir V. Furtado (Journal of Coastal Conservation, 2012)

Effects of flask sealing and growth regulators on in vitro propagation of neem (Azadirachta indica A. Juss.) - Marcelo Rodrigues; Thales H. F. Costa; Reginaldo Alves Festucci-Buselli; Luzimar Campos Silva; Wagner Campos Otoni (In Vitro Cellular & Developmental Biology - Plant, 2012)

Seasonal abundance of the Atlantic bobtail squid Sepiola atlantica in Galician waters (NE Atlantic) - Marcelo Rodrigues; Manuel E. Garci; Jesús S. Troncoso; Ángel Guerra (Marine Biology Research, 2011)

Heavy Metals Contamination in Century-Old Manmade Technosols of Hope Bay, Antarctic Peninsula - Marcelo Braga Bueno Guerra; Carlos Ernesto G. R. Schaefer; Paula de Freitas Rosa; Felipe N. B. Simas; Thiago T. C. Pereira; Edenir Rodrigues Pereira-Filho (Water, Air, & Soil Pollution, 2011)

Oviposition pattern and within-season spatial and temporal variation of pre-dispersal seed predation in a population of Mimosa bimucronata trees - Marcelo N. Rossi; Ligia M. da Silva Rodrigues; Marcos N. Ishino; Débora Kestring (Arthropod-Plant Interactions, 2011)

Creatine supplementation does not impair kidney function in type 2 diabetic patients: a randomized, double-blind, placebo-controlled, clinical trial - Bruno Gualano; Vitor de Salles Painelli; Hamilton Roschel; Rebeca Lugaresi; Egidio Dorea; Guilherme Giannini Artioli; Fernanda Rodrigues Lima; Maria Elizabeth Rossi da Silva; Maria Rosária Cunha; Antonio Carlos Seguro; Maria Heloisa Shimizu; Maria Concepción García Otaduy; et al. (European Journal of Applied Physiology, 2011)

Zeuxine strateumatica (Orchidaceae) goes south: a first record for Brazil - Luiz Menini Neto; Marcelo Rodrigues Miranda; David Cruz (Kew Bulletin, 2011)

Molecular characterization of a miraculin-like gene differentially expressed during coffee development and coffee leaf miner infestation - Jorge Maurício Costa Mondego; Melina Pasini Duarte; Eduardo Kiyota; Leandro Martínez; Sandra Rodrigues de Camargo; Fernanda P. De Caroli; Beatriz Santos Capela Alves; Sandra Maria Carmello Guerreiro; Maria Luiza Vilela Oliva; Oliveiro Guerreiro-Filho; Marcelo Menossi (Planta, 2011)

Karyological circumscription of Ipheion Rafinesque (Gilliesioideae, Alliaceae) - Luiz Gustavo Rodrigues Souza; Orfeo Crosa; Marcelo Guerra (Plant Systematics and Evolution, 2010)

Overexpression of the Arabidopsis anaphase promoting complex subunit CDC27a increases growth rate and organ size - Cristian Antonio Rojas; Nubia Barbosa Eloy; Marcelo de Freitas Lima; Roberta Lopes Rodrigues; Luciana Ozório Franco; Kristiina Himanen; Gerrit T. S. Beemster; Adriana Silva Hemerly; Paulo Cavalcanti Gomes Ferreira (Plant Molecular Biology, 2009)

Malassezia spp. in Acoustic Meatus of Bats (Molossus molossus) of the Amazon Region, Brazil - Rinaldo Ferreira Gandra; Walderez Gambale; Rita de Cássia Garcia Simão; Luciana da Silva Ruiz; Edson Luis Durigon; Luiz Marcelo Aranha de Camargo; Mauro Cintra Giudice; Luis Francisco Sanfilippo; Jansen de Araújo; Claudete Rodrigues Paula (Mycopathologia, 2008)

Catalase, Bax and p53 expression in the visual system of the crab Ucides cordatus following exposure to ultraviolet radiation - Nadia Campos de Oliveira Miguel; Inês Júlia R. Wajsenzon; Christina Maeda Takiya; Leonardo Rodrigues de Andrade; Giovane G. Tortelote; Marcelo Einicker-Lamas; Silvana Allodi (Cell and Tissue Research, 2007)

Biogeographical relationships among tropical forests in north‐eastern Brazil - André M. Melo Santos; Deyvson Rodrigues Cavalcanti; José Maria Cardoso da Silva; Marcelo Tabarelli (Journal of Biogeography, 2007)
Aim To use parsimony analysis of endemicity and cladistic analysis of distributions and endemism to evaluate two hypotheses addressing biogeographical relationships among Amazonia, the Caatinga forest enclaves, Pernambuco Centre and the southern Atlantic Forest. Location North‐eastern Brazil, South America. Methods To find the most parsimonious areagram we analysed a matrix composed of the presence (1) or absence (0) of 745 taxa (i.e. 293 genera and 452 species of woody plants) within 16 localities belonging to the four large regions addressed in this study. Results One most parsimonious areagram was found and it shows a basal separation between the southern Atlantic Forest and all other regions. This break is followed by a separation between all Caatinga forest enclaves (except Baturité) from a cluster composed of Baturité, the Pernambuco Centre and Amazonia. In this cluster, the most basal separation isolates Baturité from the cluster formed by localities from Amazonia and the Pernambuco Centre. The biogeographical relationships among sites could not be explained by either a random distribution of species among sites or by the geographical distance between sites. Main conclusions We found strong cladistic signal within the raw distribution and phylogenetic data used in our analysis, indicating structured species assemblages in the surveyed localities. They have resulted from the fragmentation of an ancestral biota that was once widely distributed in the region. Our results also support the hypothesis that Atlantic Forest is not a biogeographically natural area, because the Pernambuco Centre is more closely related to Amazonia than to the southern Atlantic Forest. Finally, our data do not support the notion that Caatinga forest enclaves comprise a single biogeographical region, because one Caatinga forest enclave (Baturité) is much more closely related to the cluster formed by Amazonia and the Pernambuco Centre than to other sites. These relationships suggest the occurrence of forest connections between Amazonia and the Atlantic Forests across Caatinga during several periods of the Tertiary and Quaternary. However, palaeoecological data currently available for the Caatinga region are still scarce and do not have either the spatial or temporal resolution required to reconstruct the history of connections among the forests in north‐eastern Brazil.

Endosperm-preferred Expression of Maize Genes as Revealed by Transcriptome-wide Analysis of Expressed Sequence Tags - Natalia C. Verza; Thaís Rezende e Silva; Germano Cord Neto; Fábio T. S. Nogueira; Paulo H. Fisch; Vincente E. de Rosa; Marcelo M. Rebello; André L. Vettore; Felipe Rodrigues da Silva; Paulo Arruda (Plant Molecular Biology, 2005)

Vasopressin release during endotoxaemic shock in mice lacking inducible nitric oxide synthase - Evelin C. Carnio; Angelita M. Stabile; Marcelo E. Batalhão; João Santana Silva; José Antunes-Rodrigues; Luiz G. S. Branco; Sheldon Magder (Pflügers Archiv - European Journal of Physiology, 2005)

Anther culture and cold treatment of floral buds increased symmetrical and extra nuclei frequencies in soybean pollen grains - Lia R. Rodrigues; Joo Marcelo S. Oliveira; Jorge E. A. Mariath; Leandro B. Irano; Maria Helena Bodanese-Zanettini (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Histology of embryogenic responses in soybean anther culture - Lia R. Rodrigues; Joo Marcelo S. Oliveira; Jorge E.A. Mariath; Maria Helena Bodanese-Zanettini (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Biochemical Composition of Seminal Plasma and Annual Variations in Semen Characteristics of Jundiá Rhamdia quelen (Quoy and Gaimard, Pimelodidae) - Adriana Borges; Daniele Rodrigues Siqueira; Daiane Follmann Jurinitz; Rebeca Zanini; Fernanda do Amaral; Marcelo Lacerda Grillo; Eneder Rosana Oberst; Guillermo Federico Wassermann (Fish Physiology and Biochemistry, 2005)

Resistance to thapsigargin-induced intracellular calcium mobilization in a multidrug resistant tumour cell line - Karen Wagner-Souza; Juliana Echevarria-Lima; Louise A.P. Rodrigues; Marcelo Reis; Vivan M. Rumjanek (Molecular and Cellular Biochemistry, 2003)

Phytoplankton of an eutrophic tropical reservoir: comparison of biomass estimated from counts with chlorophyll-a biomass from HPLC measurements - Marcelo Manzi Marinho; Silvana Viana Rodrigues (Hydrobiologia, 2003)

Tissue-specific regulation of BiP genes: a cis-acting regulatory domain is required for BiP promoter activity in plant meristems - Reginaldo A.A. Buzeli; Júlio C.M. Cascardo; Leonardo A.Z. Rodrigues; Maxuel O. Andrade; Raul S. Almeida; Marcelo E. Loureiro; Wagner C. Otoni; Elizabeth P.B. Fontes (Plant Molecular Biology, 2002)

Molecular characterisation of a NADH ubiquinone oxidoreductase subunit 5 from Schistosoma mansoni and inhibition of mitochondrial respiratory chain function by testosterone - Marcelo Rosado Fantappié; Antônio Galina; Ricardo Luís de Mendonça; Daniel Rodrigues Furtado; W. Evan Secor; Daniel G. Colley; Rodrigo Corrêa-Oliveira; George Freeman; Antônio Jorge Tempone; Lia Lannes de Camargo; Franklin David Rumjanek (Molecular and Cellular Biochemistry, 1999)

Characterization of a novel bacteriocin-encoding plasmid found in clinical isolates of Staphylococcus aureus - Marcelo Rodrigues Gamon; Erica Cristina Moreira; Selma Soares de Oliveira; Lucia Martins Teixeira; Maria do Carmo de Freire Bastos (Antonie van Leeuwenhoek, 1999)